Gloeotrichia echinulata genomes from the United States are nontoxigenic and likely geosmin producers - Theo W. Dreher; Robin Sleith; Edward W. Davis; Ryan S. Mueller; Peter D. Countway (Harmful Algae, 2026)

World Health Organization attribution of burden of foodborne diseases to transmission pathways and foods - Sara M. Pires; Lapo Mughini-Gras; Sandra Hoffmann; Kunihiro Kubota; Shannon E. Majowicz; Martyn D. Kirk; Lucy J. Robertson; Paul R. Torgerson; Lea S. Jakobsen; Antonio Agudo; Li Bai; Tety Rachmawati; et al. (Food Research International, 2026)

Temperature, taphonomy, or technique? Contrasting hypotheses of ancient DNA recovery from Quaternary asphaltic fossil deposits - Robin R. Singleton; Kristen M. Rayfield; Karissa S. Hughes; Ezra M. Flint; Karin A. Rice; Laura R. Tewksbury; Sean C. Campbell; Aisling B. Farrell; John R. Southon; Emily L. Lindsey; Courtney A. Hofman; Alexis M. Mychajliw (Quaternary Science Reviews, 2026)

Corrigendum to “Temperature, taphonomy, or technique? Contrasting hypotheses of ancient DNA recovery from Quaternary asphaltic fossil deposits” [Quat. Sci. Rev. 389 (2026) 110106] - Robin Singleton; Kristen M. Rayfield; Karissa S. Hughes; Ezra M. Flint; Karin A. Rice; Laura R. Tewksbury; Sean C. Campbell; Aisling B. Farrell; John R. Southon; Emily L. Lindsey; Courtney A. Hofman; Alexis M. Mychajliw (Quaternary Science Reviews, 2026)

Revisit of hydrothermal plumes along 63°- 64°E of Carlsberg Ridge: A comprehensive survey to assess physicochemical features of non-buoyant plumes - Lina L. Fernandes; Durbar Ray; S. Gautham; V.P. Akhil; Robin John; V. Yatheesh (Journal of Marine Systems, 2026)

Characterization of the reactions of β-lactoglobulin and potato proteins with chlorogenic acid using a UHPLC-ESI-MS approach - Thore H. Diefenbach; Gijs J.C. Vreeke; David S. Nielsen; Giovanni A. van Kralingen; Robin E.J. Spelbrink; Renske H. Janssen; Wouter J.C. de Bruijn; Jean-Paul Vincken (Food Research International, 2026)

Drivers of roe deer use in fragmented forest landscapes; implications for current and future management in the context of policy driven forest expansion - Saudamini Venkatesan; Benjamin M. Marshall; Mark S. Greener; Anna Kinghorn; Isla Sligo-Young; Richard Hassall; Robin Gill; Ben McKeown; Jeanette Hall; Roman Biek; Lucy Gilbert; Thomas A. Morrison; et al. (Forest Ecology and Management, 2026)

Oceanographic parameters associated with spatial occurrence of cephalopods in standardized demersal fishing trawls in the NE Atlantic - Daniel Oesterwind; Anne Marie Power; Esther Abad; Gregoire Certain; Nikolaos Fotiadis; Alexey Golikov; Ángel F. González; Vladimir Laptikhovsky; Silvia S. Monteiro; Carlos Montero-Castaño; Ana Moreno; Hassan Moustahfid; et al. (Marine Biology, 2026)
In this work, the environmental occurrence ranges of different European cephalopod species are described for the whole NE Atlantic shelf including the greater North Sea and Baltic Sea. This is done based on the environmental parameters collected in-situ during surveys that caught commercially important cephalopod species (1990–2022). Results are supplemented and compared with information available in the published literature and are discussed in relation to available habitat across the range, survey design, etc., and, in particular, which species are most likely to be affected by climate change. Our analyses illustrate that Loligo forbesii occupies a broader depth range than Loligo vulgaris and Alloteuthis spp. Because L. forbesii occurs further offshore and at greater depths, this species is likely more resilient to warming than the other loliginids in our study. Octopus vulgaris is documented in areas close to the coast with a more southerly distribution, whereas Eledone cirrhosa occurs further north and further away from the coast. Eledone cirrhosa occurs at lower temperatures and has a much broader depth range, which may provide resilience against warming. By contrast, both ommastrephid squid species ( Illex coindetii and Todaropsis eblanae ) showed a very similar tolerance to the three environmental variables (salinity, temperature, depth). This information should contribute to future species distribution modelling by allowing validation of realistic results against each species’ range, habitat requirements, and environmental ranges, while appreciating the data limitations caused by the timing and gear used in the survey cruises that supply occurrence and density data.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Modelling of atmospheric copper, iron, and manganese over Europe - N. Dubois; G. Foret; G. Siour; G. Uzu; F. Amato; J.-M. André; A. Alastuey; L.Y. Alleman; Robin Aujay-Plouzeau; S. Conil; F. Couvidat; A. Ito; et al. (Atmospheric Environment, 2026)

Potential for Manganese Oxide Driven Anaerobic Methane Oxidation in Sediments of a Seasonally Euxinic Coastal Basin - Robin Klomp; Anna J. Wallenius; Niels A. G. M. van Helmond; Wytze K. Lenstra; Olga M. Żygadłowska; Mike S. M. Jetten; Caroline P. Slomp (Estuaries and Coasts, 2026)
Methane (CH 4 ) is a strong greenhouse gas that, in marine sediments, is produced via methanogenesis and removed via oxidation with electron acceptors such as oxygen, sulfate and metal oxides . This study assesses the potential for manganese driven anaerobic oxidation of methane (Mn-AOM) in rapidly accumulating sediments in a seasonally euxinic coastal marine basin (Scharendijke basin, Lake Grevelingen, the Netherlands). Geochemical sediment and porewater profiles demonstrate that, at the study site, Mn oxides are buried in the methanic zone. Sediment incubations amended with 13 C-CH 4 and various Mn forms indicate that the Mn oxide minerals birnessite, pyrolusite and manganite can enhance CH 4 oxidation, whereas ligand bound dissolved Mn(III) does not. This is attributed to either direct Mn-AOM, where Mn oxides act as the electron acceptor, and/or indirect Mn-driven AOM via cryptic sulfur cycling. Results of 16S rRNA gene amplicon sequencing of the incubated sediment point towards a likely role for anaerobic methanotrophic archaea of the clades ANME-2ab and ANME-3 in direct and indirect Mn-driven AOM, respectively. An increase in relative abundance of the methanogen Methanosarcina in several of the incubations suggests that these versatile methanogens benefit from Mn oxide reduction. This study demonstrates potential for Mn-driven AOM in sediments from a eutrophic, seasonally euxinic coastal basin, and expands the range of electron acceptors involved in CH 4 removal in such systems.

Lag in Effective Population Size Decline Amid Demographic Collapse: A Case Study of the Delta Smelt ( Hypomesus transpacificus ) - Amanda J. Finger; Melanie E. F. LaCava; Evan W. Carson; James A. Hobbs; Tien‐Chieh Hung; Matthew L. Nobriga; Leo Polansky; Robin S. Waples (Molecular Ecology, 2026)
Effective population size ( N e ), census size ( N c ) and their ratio ( N e / N c ) are widely used indicators in conservation genetics, yet long‐term empirical data tracking of all three metrics over long time scales in wild populations remains rare. Using monitoring data from 1995 to 2020, we examined temporal dynamics of N e , N c and their relationship during the demographic collapse of Delta Smelt ( Hypomesus transpacificus ), an endangered fish endemic to the San Francisco Estuary, California, USA. We estimated N e for 21 annual cohorts using restriction site‐associated DNA sequencing data, applying the linkage disequilibrium method, temporal method and a recently developed combined method. Abundance was represented by model‐based survey indices ( N c *). N e varied substantially through time (145–1928), declining in recent years but remaining above commonly cited conservation thresholds for long‐term persistence (e.g., N e > 500) until the final years of collapse. N e was positively correlated with N c * ( r = 0.58), but the shallow slope (β = 0.25) indicates that demographic decline outpaced genetic decline. N e / N c * was consistently low (0.0001–0.056), but it increased significantly through time. Our results show that genetic erosion may lag behind demographic collapse and that N e / N c * is not constant and therefore cannot be easily inferred from either variable alone. This study demonstrates the need for additional empirical data sets to facilitate interpretation of N e , N c * and N e / N c * for the conservation of global biodiversity.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Emerging tools to advance neuroethology in butterflies and moths - Francesco Cicconardi; Max S. Farnworth; Robin Grob; Donya N. Shodja; Caroline N. Bacquet; Basil el Jundi; Arnaud Martin; Stephen H. Montgomery (Journal of Comparative Physiology A, 2026)
Butterflies and moths have played historically important roles in developing our understanding of both ecology and evolutionary biology, and neuroethology. In both contexts, the diversity of behavioral strategies and specializations displayed by different Lepidoptera make them informative case studies. However, as in neuroscience more broadly, lepidopteran neuroethology has tended to focus on intricate functional studies within a small number of the most tractable species. In contrast, ecologists and evolutionary biologists have often taken a broader view, using phylogenetic and comparative approaches to extract general patterns of diversification, and to exploit the diversity of butterflies and moths to understand general evolutionary processes. Uniting these approaches and traditions has been restricted, largely due to technical challenges of working with unestablished study systems and a lack of resources beyond basic tools. Now, however, the prospects for broader comparative studies of the neural basis of behavior within a phylogenetic and/or ecological framework are increasingly positive. This is in large part due to the emergence of new molecular sequencing approaches and associated tools. These allow for the survey of cell types, the spatial location of their soma, development of new cell-type markers for targeted analyses, and quantification of the dynamic regulation of gene expression at a tissue or cell specific level. Results of these molecular methods can be combined with technical developments in free flying behavioral experiments in tethered animals that permit neural recordings of natural behavior, and functional genetics tools that can allow for more precise manipulation of these behaviors or the neural structures that support them. Here, we review these new approaches, their potential application, and discuss how we can use them to advance the development of new, integrative systems for studying the neural basis of behavior in butterflies and moths.

The diversity of lepidopteran spatial orientation strategies – neuronal mechanisms and emerging challenges in a changing world - Robin Grob; Max S. Farnworth; Jacqueline Degen; Eric Warrant; Stephen H. Montgomery; Basil el Jundi (Journal of Comparative Physiology A, 2026)
The Lepidoptera, butterflies and moths, display an astonishing diversity of spatial orientation strategies essential for survival, reproduction, and ecological success. These spatial orientation strategies range from basic taxes to light, wind, gravity, and chemical cues, to more advanced strategies such as straight-line dispersal, multigenerational migration across continents, and complex trap-lining foraging involving long-term spatial memory. These orientation behaviours are tightly integrated with the ecological roles of lepidopterans as pollinators, prey, and bioindicators, and are supported by a flexible neuronal network. Of special interest for successful orientation are higher-order integration centres like the mushroom bodies (centres for learning and memory) and the central complex (the centre for spatial orientation and locomotion). These centres support cue integration, compass orientation, memory, and directional decision-making. However, anthropogenic stressors, including habitat fragmentation, light pollution, pesticides, and electromagnetic noise, threaten both the environmental cues and the neural systems facilitating lepidopteran navigation, with potential cascading effects on biodiversity and ecosystem health. By combining insights from behavioural ecology, neurobiology, and conservation, we aim to provide a comprehensive overview of the challenges and adaptations that shape the navigational toolkit of lepidopterans, underlining their significance as animal models for studying spatial orientation in a changing world.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Characterizing seasonal persistence of low levels of Pseudo-nitzschia australis in the Gulf of Maine with environmental DNA - Sydney M. Greenlee; Robin S. Sleith; Damian C. Brady; Peter D. Countway (Harmful Algae, 2026)

Population genetics of the endangered narrowly endemic Island Marble butterfly (Euchloe ausonides insulanus) - Kara S. Jones; Aaron W. Aunins; Colleen C. Young; Robin L. Johnson; Cheryl L. Morrison (Conservation Genetics, 2026)

Forest Ecosystem Multifunctionality: A Systematic Review of Measures and Drivers - Jenickson R. S. Costa; Pedro H. S. Brancalion; François-Xavier Joly; Laura H. P. Simões; Jonathan Bonfanti; Guerric le Maire; Agnès Robin; Joannès Guillemot (Current Forestry Reports, 2026)
Purpose of Review Forest ecosystem multifunctionality, the capacity of forests to simultaneously deliver multiple ecosystem functions and services, is being increasingly affected by pressures stemming from anthropogenic activities and climate change. Here, we conducted a systematic literature review to explore how forest ecosystem multifunctionality was evaluated in the literature, and to identify its main drivers. Recent Findings We found that the number of publications strongly increased in recent years, mostly focused on China and Europe. Abiotic drivers were most frequently examined, ranked in decreasing importance as soil properties, site features, and climate factors. Biodiversity-related drivers were the second most studied, encompassing species composition (i.e., species identity within the forest), species richness of trees, bacteria, and fungi, and stand structural diversity. Soil-related drivers were predominantly used to evaluate belowground multifunctionality, with less consideration given to their potential effects on aboveground multifunctionality. Conversely, the effects of tree and stand attributes have commonly been considered in both above- and belowground ecosystem multifunctionality. Forest ecosystem multifunctionality is often mediated by interactions among drivers, involving both above and below-ground components. Summary Tree species and soil organism diversity (including species richness and functional diversity), stand age and stand structural diversity, emerged as crucial drivers enhancing multifunctionality both above- and belowground. Our results suggest that preserving old-growth forests, promoting long-term restoration, and expanding species-diverse forests is an effective strategy for achieving multifunctional forests. Current understanding is limited by a pronounced geographical bias, limited comparability of studies, and overlooked multifunctionally drivers, especially related to the effects of soil fauna and management practices.

Unraveling unexpected results in food and feed safety controls: a comprehensive workflow - Esmer J. Jongedijk; Robin S. Wegh; Rosalie Nijssen; Michael van Dam; Samantha Sasse; Irma E.A. Bongers; Josha Jager; Marco Blokland; Milou G.M. van de Schans (Food Control, 2026)

A Comparison of Diving Behavior of Goose‐Beaked and Dense‐Beaked Whales From Tagging Studies in Multiple Ocean Basins - Jay Barlow; Robin W. Baird; Janelle Badger; Gregory S. Schorr; Erin A. Falcone; Shannon N. Coates; Peter L. Tyack; Andrew J. Read; Leigh S. Hickmott; John W. Durban; Diane Claridge; Natacha Aguilar de Soto; et al. (Marine Mammal Science, 2026)
Studies of cetacean diving behavior in multiple locations in different ocean basins allow for an assessment of variability within and among populations. We examine foraging dive behaviors of goose‐beaked whales ( Ziphius cavirostris ) and dense‐beaked whales ( Mesoplodon densirostris ) using data from 132 tagged whales in seven locations in the Pacific and Atlantic Oceans and the Mediterranean Sea. Acoustic recording tags are used to identify foraging dives by the presence of echolocation. For other tag types, foraging dives are identified based on maximum dive depth. Five parameters are used to characterize foraging dives: maximum dive depth, foraging dive duration, dive cycle duration, and the mean and standard deviation of echolocation depths. We find that differences among dives within one tagged individual are typically larger than the differences among individuals or among locations, and that differences among individuals are typically similar in magnitude to differences among locations. Regression is used to estimate the mean and standard deviation of echolocation depths from maximum dive depth for dives without acoustic data. Composite values of foraging dive parameters (and standard deviations) are estimated as the average of all study locations.

Lithologies of Dimorphos revealed by boulder morphological classes - F. Tusberti; M. Pajola; L. Penasa; A. Lucchetti; M. Massironi; G. Munaretto; J. Beccarelli; R. Pozzobon; C. Rossi; G. Poggiali; N. Murdoch; C.Q. Robin; et al. (Icarus, 2025)

Arbuscular mycorrhizal fungi dynamics in secondary shrublands of Madagascar: ecological insights for nurse plant selection in forest restoration - Rondro Harinisainana Baohanta; Martial Doret Andrianandrasana; Felana Niaina Rakoto Joseph; Vincent Porcher; Herizo Randriambanona; Voarisoa S. Randriantenaina; Irinah Ratsizafy; Robin Duponnois; Heriniaina Ramanankierana (Acta Oecologica, 2025)

The Idiot's Guide to Effective Population Size - Robin S. Waples (Molecular Ecology, 2025)
This is a reference manual for the elegant, yet hideously complex concept of effective population size ( N e ), inspired by a classic, self‐published manual of automotive repair ‘for the compleat idiot’. The Guide is timely, given the recent Kunming‐Montreal Global Biodiversity Framework, where 196 Parties committed to tracking genetic diversity—and estimating N e —for all species. N e is a human construct, but a useful one that allows us to capture diverse aspects of an organism's biology in a single number. The Guide collates in one location factual information about effective population size, with a focus on topics of practical relevance to scientists and managers studying real populations; it covers definition, computation and estimation of effective size, both demographically and genetically. As appropriate, the reader is directed to other primary sources for more details. A ‘Don't Do These Things’ section lists several ill‐advised approaches to dealing with N e , and an Appendix provides useful tools and practical suggestions for interested users. A special section considers both possibilities and challenges presented by the genomics revolution. Availability of vast numbers of genetic markers increases precision, but less than some might think, and simultaneously introduces new challenges involving filtering and bioinformatics processing. As annotated genomes become more common for non‐model species, opportunities are opened to address qualitatively different questions, including reconstructing historical changes in N e through time.

The Genomics Revolution in Nonmodel Species: Predictions vs. Reality for Salmonids - Samuel A. May; Samuel W. Rosenbaum; Devon E. Pearse; Marty Kardos; Craig R. Primmer; Diana S. Baetscher; Robin S. Waples (Molecular Ecology, 2025)
The increasing feasibility of whole‐genome sequencing has been highly anticipated, promising to transform our understanding of the biology of nonmodel species. Notably, dramatic cost reductions beginning around 2007 with the advent of high‐throughput sequencing inspired publications heralding the ‘genomics revolution’, with predictions about its future impacts. Although such predictions served as useful guideposts, value is added when statements are evaluated with the benefit of hindsight. Here, we review 10 key predictions made early in the genomics revolution, highlighting those realised while identifying challenges limiting others. We focus on predictions concerning applied aspects of genomics and examples involving salmonid species which, due to their socioeconomic and ecological significance, have been frontrunners in applications of genomics in nonmodel species. Predicted outcomes included enhanced analytical power, deeper insights into the genetic basis of phenotype and fitness variation, disease management and breeding program advancements. Although many predictions have materialised, several expectations remain unmet due to technological, analytical and knowledge barriers. Additionally, largely unforeseen advancements, including the identification and management applicability of large‐effect loci, close‐kin mark–recapture, environmental DNA and gene editing have added under‐anticipated value. Finally, emerging innovations in artificial intelligence and bioinformatics offer promising new directions. This retrospective evaluation of the impacts of the genomic revolution offers insights into the future of genomics for nonmodel species.

Core temperature responses in world-class triathletes during the Tokyo 2020 Olympics and 2019 to 2021 World Triathlon Championship Series - Jonathan S. E. Rubio; Sébastien Libicz; Robin Candau; Sébastien Racinais (German Journal of Exercise and Sport Research, 2025)

Low‐coverage sequencing and Wahlund effect severely bias estimates of inbreeding, heterozygosity and effective population size in North American wolves - Marty Kardos; Robin S. Waples (Molecular Ecology, 2025)
vonHoldt et al. ((2024), Molecular Ecology, 33, e17231) (vH24) used low‐coverage (average ~ 7X read depth) restriction site‐associated DNA sequence data to estimate individual inbreeding and heterozygosity, and recent effective population size ( N e ), in Great Lakes (GL) and Northern Rocky Mountain (RM) wolves. They concluded that RM heterozygosity rapidly declined between 1991 and 2020, and that N e declined substantially in GL and RM over the last 50 generations. Here, we evaluate the effects of low sequence coverage and sampling strategy on vH24's findings and provide general recommendations for using sequence data to evaluate inbreeding, heterozygosity and N e . Low‐coverage sequencing resulted in downwardly biased estimates of individual inbreeding and heterozygosity, and an erroneous large temporal decline in RM heterozygosity due to declining read depth through time. Additionally, vH24's sampling strategy–which combined individuals from several genetically differentiated populations and across at least eight wolf generations–is expected to have resulted in severe downward bias in estimates of recent N e for RM. We recommend using high‐coverage sequence data (15‐20X) to estimate inbreeding and heterozygosity. Carefully filtering individuals, loci and genotypes, and using genotype imputation or likelihoods can help to minimise bias when low‐coverage sequence data must be used. For estimation of contemporary N e , the marginal benefits of using more than 10 3− 10 4 loci are small, so aggressive filtering of loci with low average read depth potentially can retain most individuals without sacrificing much precision. Individuals are relatively more valuable than loci because analyses of contemporary N e should focus on roughly single‐generation samples from local breeding populations.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Marker Assisted Introgression and Evaluation of Retinol Equivalent Carotenoid in the Elite Cultivars Background from Traditional Landrace ‘Kavuni’ - Suvarna Rani Chimmili; G. Subashini; M. Raveendran; C. R. Anandakumar; Jyothi Badri; Divya Balakrishnan; S. Robin (Agricultural Research, 2025)

Diversity in Resource Use Strategies Promotes Productivity in Young Planted Tree Species Mixtures - Joel Jensen; Haben Blondeel; Joannès Guillemot; Florian Schnabel; Hernán Serrano‐León; Harald Auge; Lander Baeten; Nadia Barsoum; Jürgen Bauhus; Christel Baum; Raimundo Bermudez; Friderike Beyer; et al. (Global Change Biology, 2025)
Mixed‐species forestry is a promising approach to enhance productivity, increase carbon sequestration, and mitigate climate change. Diverse forests, composed of species with varying structures and functional trait profiles, may have higher functional and structural diversity, which are attributes relevant to a number of mechanisms that can influence productivity. However, it remains unclear whether the context‐dependent roles of functional identity, functional diversity, and structural diversity can lead to a generalized understanding of tree diversity effects on stand productivity. To address these gaps, we analyzed growth data from 83,600 trees from 89 species across 21 young tree diversity experiments spanning five continents and three biomes. Results revealed a positive saturating relationship between tree species richness and stand productivity, with reduced variability in growth rates among more diverse stands. Structural equation modeling demonstrated that functional diversity mediated the positive effects of species richness on productivity. We additionally report a negative relationship between structural diversity and productivity, which decreased with increasing species richness. When partitioning net diversity effects, we found that selection effects played a dominant role in driving the overall increase in productivity in these predominantly young stands, contributing 77% of the net diversity effect. Selection effects increased with diversity in wood density. Furthermore, acquisitive species with lower wood density and higher leaf nitrogen content had higher productivity in more diverse stands, while conservative species showed neutral to slightly negative responses to species mixing. Together, these results suggest that combining acquisitive with conservative species allows acquisitive species to drive positive selection effects while conservative species tolerate competition. Thus, contrasting resource‐use strategies can enhance productivity to optimize mixed‐species forestry, with potential for both ecological and economic benefits.

A Comparison of the Biotechnological Potential of Marine and Terrestrial Species of Two Orders of Sordariomycete Fungi - Raquel Ledo Doval; Astrid Müller; Daren W. Brown; Derek Johnson; C. Alisha Quandt; Kerrie Barry; Alicia Clum; Hope Hundley; Kurt LaButti; Anna Lipzen; Stephen J. Mondo; Robin A. Ohm; et al. (Marine Biotechnology, 2025)

New records of fishes from the Coral Sea Marine Park, Australia - Yi-Kai Tea; Tiffany L. Sih; Fenton Walsh; Timothy Bennett; Luiz A. Rocha; Ghislain Bardout; Amanda Hay; Kerryn Parkinson; Sally Reader; Indiana J. Riley; John J. Pogonoski; Jeffrey W. Johnson; et al. (Coral Reefs, 2025)
With an area covering just under 1 million km 2 , Australia’s Coral Sea Marine Park (CSMP) is among the largest marine protected areas globally. Yet, the demersal deep-reef fish fauna of the CSMP remains poorly described, due in part to its remote location, as well as its sheer size, much of which is inaccessible below conventional SCUBA diving depths. Recent remotely operated vehicle (ROV) explorations conducted by the Schmidt Ocean Institute provided an opportunity to explore the benthic ichthyofauna of deep mesophotic and rariphotic coral ecosystems. Contributions to the deep, demersal ichthyofauna of Australia’s CSMP are herein supplemented with an integrative dataset consisting of ROV imagery and specimen vouchers. Sixty-two new records of fishes from 26 families are reported from the CSMP. Of these, 45 are new Australian records, one of which is also a new family record for Australia. Four species are new records for the Southern Hemisphere, and 21 species are potentially new to science. We report new voucher material for 29 species, including several species previously identified as new for the CSMP with no voucher specimens.

Optimizing automated photo identification for population assessments - Philip T. Patton; Krishna Pacifici; Robin W. Baird; Erin M. Oleson; Jason B. Allen; Erin Ashe; Aline Athayde; Charla J. Basran; Elsa Cabrera; John Calambokidis; Júlio Cardoso; Emma L. Carroll; et al. (Conservation Biology, 2025)
Several legal acts mandate that management agencies regularly assess biological populations. For species with distinct markings, these assessments can be conducted noninvasively via capture‐recapture and photographic identification (photo‐ID), which involves processing considerable quantities of photographic data. To ease this burden, agencies increasingly rely on automated identification (ID) algorithms. Identification algorithms present agencies with an opportunity—reducing the cost of population assessments—and a challenge—propagating misidentifications into abundance estimates at a large scale. We explored several strategies for generating capture histories with an ID algorithm, evaluating trade‐offs between labor costs and estimation error in a hypothetical population assessment. To that end, we conducted a simulation study informed by 39 photo‐ID datasets representing 24 cetacean species. We fed the results into a custom optimization tool to discern the optimal strategy for each dataset. Our strategies included choosing between truly and partially automated photo‐ID and, in the case of the latter, choosing the number of suggested matches to inspect. True automation was optimal for datasets for which the algorithm identified individuals well. As identification performance declined, the optimization recommended that users inspect more suggested matches from the ID algorithm, particularly for small datasets. False negatives (i.e., individual was resighted but erroneously marked as a first capture) strongly predicted estimation error. A 2% increase in the false negative rate translated to a 5% increase in the relative bias in abundance estimates. Our framework can be used to estimate expected error of the abundance estimate, project labor effort, and find the optimal strategy for a dataset and algorithm. We recommend estimating a strategy's false negative rate before implementing the strategy in a population assessment. Our framework provides organizations with insights into the conservation benefits and consequences of automation as conservation enters a new era of artificial intelligence for population assessments.

5-MeO-DMT: An atypical psychedelic with unique pharmacology, phenomenology & risk? - Haley Maria Dourron; Charles D. Nichols; Otto Simonsson; Melissa Bradley; Robin Carhart-Harris; Peter S. Hendricks (Psychopharmacology, 2025)

Associations of anthropogenic activity and tributaries with the physicochemical, nutrient and microbial composition of the Ganga (Ganges) River, India - Gillian E. Clayton; Laura A. Richards; Bethany G. Fox; Robin M.S. Thorn; Michael J. Bowes; Daniel S. Read; Holly J. Tipper; Kieran Khamis; Tapan K. Dutta; Arun Kumar; Moushumi Hazra; Ben Howard; et al. (Water Research, 2025)

Climate media amidst technopolitical change: challenges, transformations, and new directions for research - Rachel Wetts; Hanna E. Morris; Maxwell Boykoff; Brenda McNally; James Painter; Mary Sanford; Emily P. Diamond; Marc Esteve-del-Valle; Loredana Loy; Kelly E. Perry; Urooj S. Raja; Robin Tschötschel (Climatic Change, 2025)
In this essay, we seek to provide a meta-level view of research on mediated climate change communication, taking stock of its achievements, historical and contemporary challenges, and future directions. While existing climate media scholarship has generated important insights to guide research and practice, recent empirical developments and technopolitical transformations challenge the traditional structure of climate media research. Historically, this research developed a tripartite structure where scholars have tended to focus on one of three distinct phases of the mediated communication process: (1) the production of narratives, frames, images, and other forms of communication about climate change; (2) the content and dissemination of these communication artifacts by and across media industries and institutions; and (3) these artifacts’ reception by and effects on policymakers, partisans, and publics. However, recent developments in communication technologies, media ecosystems, and the broader political landscape—including the increasing importance of social media and AI, new forms of climate obstruction, and rising antidemocratic forces across borders—have made these traditional lines of demarcation increasingly unworkable. While the lines of demarcation between production, dissemination, and reception are increasingly blurred in important new empirical phenomena, each has remained central in many scholarly works and the development of research questions. This persistence of the tripartite model, we argue, has caused climate media research to be slow to reflect the shifting dynamics of mediated climate communication today. After describing and analyzing the structural challenges that make doing more comprehensive climate media research so challenging, we conclude with proposals for new directions for scholarship that can help future research more fully contend with recent technopolitical transformations and move towards actionable research that is capable of grappling with and motivating robust responses to the complexities of climate change amid mounting authoritarian threats.

The Human Shield Hypothesis: Does Predator Avoidance of Humans Create Refuges for Prey? - Kaitlyn M. Gaynor; Eamonn I. F. Wooster; April Robin Martinig; Jennifer R. Green; Aimee Chhen; Sandra Cuadros; Ryan Gill; Gopal Khanal; Nicola Love; Rekha Marcus; C. Lauren Mills; Kwasi Wrensford; et al. (Ecology Letters, 2025)
As anthropogenic disturbance restructures ecological communities worldwide, ecologists have developed and tested hypotheses about which species “win” and “lose” in the face of human impacts. One heavily invoked paradigm is that of the human shield, which posits that predators avoid areas of human disturbance due to perceived risk from humans, and prey therefore seek refuge in these areas of perceived safety. Since its introduction in 2007, the human shield hypothesis (HSH) has gained popularity in the ecological literature, although there are more passing mentions of human shields than there are robust tests of the HSH. Here, we systematically review evidence for the HSH and evaluate how it is commonly discussed and tested. While there are several clear‐cut cases of human shields, the emergence of human shields is highly context‐dependent. By formally outlining the assumptions of the HSH, we derive predictions about what ecological and anthropogenic contexts are most likely to be conducive to human shields. Further robust studies that compete the HSH against alternative hypotheses and account for confounding factors can shed light on the role of human shields in human‐modified ecosystems and inform the conservation and management of wildlife in a changing world.

Pleistocene stratigraphy and sedimentation in the Magadi-Ewaso Nyiro Basins, South Kenya Rift - R. Bernhart Owen; Robin W. Renaut; Tim K. Lowenstein; Mona Stockhecke; Nathan Rabideaux; Kennie Leet; Andrew S. Cohen; Jennifer J. Scott; Veronica Muiruri (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Springtime upwelling conditions influence microbial communities and dissolved thiamin compounds in the California Current Ecosystem - Kelly C. Shannon; Gillian St. John; Robin Gould; Christopher Hartzell; Hailey Matthews; Elizabeth J. Brennan; Luis M. Bolaños; Steven T. Lindley; John C. Field; Nate Mantua; Rachel Johnson; Carson Jeffres; et al. (Limnology and Oceanography, 2025)
Understanding dissolved concentrations of the essential coenzyme thiamin (vitamin B 1 ) can provide insights into the biological controls on highly productive upwelling systems such as the California Current Ecosystem. To connect thiamin availability with microbial communities in the California Current Ecosystem, we measured concentrations of dissolved thiamin and its biochemically related moieties (thiamin congeners) and 16S rRNA gene‐based microbial communities during the spring. We found that strong upwelling caused a depletion of dissolved thiamin precursor compounds and abiotic degradation products relative to periods of weak upwelling. Specific microbial taxa, including species of SAR11 ecotypes, Candidatus Nitrosopumilus, and SUP05 cluster, were also significantly enriched with strong upwelling. Our data provide evidence that alterations to microbial communities in the mixed layer that occur as a result of upwelling could constrain the availability of dissolved thiamin and its chemical congeners in the California Current Ecosystem.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Preoperative physical resilience indicators and their associations with postoperative outcomes - Marjolein Klop; René J. F. Melis; G. M. E. E. Geeske Peeters; Guillaume S. C. Geuzebroek; Robin H. Heijmen; Richard J. A. van Wezel; Jurgen A. H. R. Claassen (GeroScience, 2025)
The health benefit of surgery in older adults may be outweighed by negative effects on cognitive or physical function. Physical resilience is defined as the potential for recovery after a stressor such as surgery. We assessed associations between physical resilience measured by orthostatic blood pressure (BP) and cerebral oxygenation recovery or grip work (sustained hand grip strength; GW) and postoperative outcome in two cohorts of (older) surgical patients. The first cohort (CTC) consisted of patients undergoing complex cardiothoracic surgery. The second cohort (GRR) held geriatric outpatients undergoing various surgical procedures. Outcome measures were length of stay (LoS) and postoperative complications. Negative binomial (LoS) and ordinal (complications) regression models were used to determine associations. 261 patients (113 CTC and 148 GRR) underwent surgery. Median LoS was 10 (CTC) and 5 days (GRR). Postoperative complications occurred in 80% (CTC) and 45% (GRR) of patients. In CTC, 10 mmHg higher systolic BP recovery was associated with a 12% shorter LoS (incidence rate ratio (IRR) 0.88 (95% CI 0.78–0.98)). 10 s longer sustained hand grip was associated with a 5% shorter LoS in GRR (IRR 0.95 (0.90–1.00)), but a 7% longer LoS in CTC (IRR 1.07 (1.03–1.11)). No significant associations were found with postoperative complications. Orthostatic cerebral oxygenation recovery in CTC was not significantly associated with any postoperative outcome. Our results imply that resilience indicators might be associated with LoS after surgery. Future research should seek to replicate our findings and investigate whether adding resilience parameters to preoperative assessment can support postoperative outcome prediction.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Oceanscape: A graph-based framework for autonomous coastal navigation - Eirik S. Fagerhaug; Robin T. Bye; Ottar L. Osen; Lars Ivar Hatledal (Ocean Engineering, 2025)

Predicting and assessing the impacts of COVID-19 disruption on marine science and sectors in Australia - Alistair J. Hobday; Vicki M. Walters; Robert L. Stephenson; Shane Baylis; Cindy Bessey; Fabio Boschetti; Catherine Bulman; Stephanie Contardo; Jeffrey M. Dambacher; Jemery Day; Natalie A. Dowling; Piers Dunstan; et al. (Reviews in Fish Biology and Fisheries, 2025)
By March 2020 coronavirus disease 2019 (COVID-19) was anticipated to present a major challenge to the work undertaken by scientists. This pandemic could be considered just one of the shocks that human society has had and will be likely to confront again in the future. As strategic thinking about the future can assist performance and planning of scientific research in the face of change, the pandemic presented an opportunity to evaluate the performance of marine researchers in prediction of future outcomes. In March 2020, two groups of researchers predicted outcomes for the Australian marine research sector, and then evaluated these predictions after 18 months. The self-assessed coping ability of a group experienced in ‘futures studies’ was not higher than the less-experienced group, suggesting that scientists in general may be well placed to cope with shocks. A range of changes to scientific endeavours (e.g., travel, fieldwork) and to marine sectors (e.g., fisheries, biodiversity) were predicted over the first 12–18 months of COVID-19 disruption. The predicted direction of change was generally correct (56%) or neutral (25%) for predictions related to the scientific endeavour, and correct (73%) or mixed (9%) for predictions related to sectors that are the focus of marine research. The success of this foresighting experiment suggests that the collective wisdom of scientists can be used by their organisations to consider the impact of shocks and disruptions and to better prepare for and cope with shocks. Graphical abstract Word cloud analysis of free text responses to questions about expected impact of COVID-19 on the activities associated with marine science

Multiple Lineages of Transmissible Neoplasia in the Basket Cockle ( C. nuttallii ) With Repeated Horizontal Transfer of Mitochondrial DNA - Marisa A. Yonemitsu; Jordana K. Sevigny; Lauren E. Vandepas; James L. Dimond; Rachael M. Giersch; Helen J. Gurney‐Smith; Cathryn L. Abbott; Janine Supernault; Ruth Withler; Peter D. Smith; Sydney A. Weinandt; Fiona E. S. Garrett; et al. (Molecular Ecology, 2025)
Transmissible cancers are clonal lineages of neoplastic cells able to infect multiple hosts, spreading through populations in the environment as an infectious disease. Transmissible cancers have been identified in Tasmanian devils, dogs, and bivalves. Several lineages of bivalve transmissible neoplasias (BTN) have been identified in multiple bivalve species. In 2019 in Puget Sound, Washington, USA, disseminated neoplasia was observed in basket cockles ( Clinocardium nuttallii ), a species that is important to the culture and diet of the Suquamish Tribe as well as other tribes with traditional access to the species. To test whether disseminated neoplasia in cockles is a previously unknown lineage of BTN, a nuclear locus was amplified from cockles from Agate Pass, Washington, and sequences revealed evidence of transmissible cancer in several individuals. We used a combination of cytology and quantitative PCR to screen collections of cockles from 11 locations in Puget Sound and along the Washington coastline to identify the extent of contagious cancer spread in this species. Two BTN lineages were identified in these cockles, with one of those lineages (CnuBTN1) being the most prevalent and geographically widespread. Within the CnuBTN1 lineage, multiple nuclear loci support the conclusion that all cancer samples form a single clonal lineage. However, the mitochondrial alleles in each cockle with CnuBTN1 are different from each other, suggesting mitochondrial genomes of this cancer have been replaced multiple times during its evolution, through horizontal transmission. The identification and analysis of these BTNs are critical for broodstock selection, management practices, and repopulation of declining cockle populations, which will enable continued cultural connection and dietary use of the cockles by Coast Salish Tribes.

A spatially explicit assessment of factors shaping attitudes toward African elephant conservation - Sarah L. Carroll; Susanne M. Vogel; Purity Nititi Taek; Clevers Tumuti; Divya Vasudev; Varun R. Goswami; Jake Wall; Stephen Mwiu; Robin S. Reid; Jonathan Salerno (Conservation Biology, 2025)
Conservation plans that explicitly account for the social landscape where people and wildlife co‐occur can yield more effective and equitable conservation practices and outcomes. Yet, social data remain underutilized, often because social data are treated as aspatial or are analyzed with approaches that do not quantify uncertainty or address bias in self‐reported data. We conducted a survey (questionnaires) of 177 households in a multiuse landscape in the Kenya–Tanzania borderlands. In a mixed‐methods approach, we used Bayesian hierarchical models to quantify and map local attitudes toward African elephant ( Loxodonta africana ) conservation while accounting for response bias and then combined inference from attitude models with thematic analysis of open‐ended responses and cointerpretation of results with local communities to gain deeper understanding of what explains attitudes of people living with wildlife. Model estimates showed that believing elephants have sociocultural value increased the probability of respondents holding positive attitudes toward elephant conservation in general (mean increase = 0.31 [95% credible interval, CrI, 0.02–0.67]), but experiencing negative impacts from any wildlife species lowered the probability of respondents holding a positive attitude toward local elephant conservation (mean decrease = −0.20 [95% CrI −0.42 to 0.03]). Qualitative data revealed that safety and well‐being concerns related to the perceived threats that elephants pose to human lives and livelihoods, and limited incentives to support conservation on community and private lands lowered positive local attitude probabilities and contributed to negative perceptions of human–elephant coexistence. Our spatially explicit modeling approach revealed fine‐scale variation in drivers of conservation attitudes that can inform targeted conservation planning. Our results suggest that approaches focused on sustaining existing sociocultural values and relationships with wildlife, investing in well‐being, and implementing species‐agnostic approaches to wildlife impact mitigation could improve conservation outcomes in shared landscapes.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Klebsiella pneumoniae in stranded California sea lions (Zalophus californianus) of Central California between 2017-2022 - Sydney N. Zotto; Robin C. Dunkin; Juliana D. Limon; Maia S. Smith; Lisabet M. Hortensius; Margaret E. Martinez; Pádraig J. Duignan; Cara Field; Esteban Soto; Dane Whitaker; Carlos Rios; Maurice Byukusenge; et al. (Frontiers in Marine Science, 2025)
Klebsiella pneumoniae is a Gram-negative, facultative anaerobic, and non-motile bacillus frequently observed in mammals. A hypermucoviscous (HMV) phenotype of K. pneumoniae is reported in stranded California sea lions (CSL) causing pleuritis and bronchopneumonia as a persistent cause of strandings. We describe an increase in cases of HMV and non-HMV K. pneumoniae in stranded CSLs along the California coast between 2017 to 2022. 2,146 live-stranded CSLs were rescued by The Marine Mammal Center (Sausalito, California). 47 of these tested positive for K. pneumoniae , with a rise in annual incidence from 0.92% (3/331) in 2017 to 8.5% (14/165) and 7.2% (23/320) in 2021 and 2022, respectively. These strandings occurred across 965 kilometers along the North-Central California coast from Bodega Bay, Sonoma, to Avila Beach, San Luis Obispo. A similar pattern was observed in beach-cast CSL carcasses by the Long Marine Laboratory (LML) Stranding Network in Santa Cruz, California who had 8 CSLs test positive for K. pneumoniae with an annual incidence rate of 2.0% (1/50) and 10.1% (7/69) in 2021 and 2022, respectively, with no cases reported prior to 2021. We applied whole-genome sequencing (WGS) to 8 isolates obtained by LML in 2022. WGS analysis revealed high nucleotide similarity between any pair of isolates. Multilocus Sequence Typing showed that all isolates belonged to Sequence type 65 and contained the K2 polysaccharide capsule and siderophore aerobactin, which are all characteristics of hypervirulent K. pneumoniae. We discuss possible causes for this trend and a need for research on K. pneumoniae in free-ranging CSLs in California.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

A quantitative modeling framework to understand the physiology of the hypothalamic-pituitary-adrenal axis and interaction with cortisol replacement therapy - Davide Bindellini; Robin Michelet; Linda B. S. Aulin; Johanna Melin; Uta Neumann; Oliver Blankenstein; Wilhelm Huisinga; Martin J. Whitaker; Richard Ross; Charlotte Kloft (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
Congenital adrenal hyperplasia (CAH) is characterized by impaired adrenal cortisol production. Hydrocortisone (synthetic cortisol) is the drug-of-choice for cortisol replacement therapy, aiming to mimic physiological cortisol circadian rhythm. The hypothalamic-pituitary-adrenal (HPA) axis controls cortisol production through the pituitary adrenocorticotropic hormone (ACTH) and feedback mechanisms. The aim of this study was to quantify key mechanisms involved in the HPA axis activity regulation and their interaction with hydrocortisone therapy. Data from 30 healthy volunteers was leveraged: Endogenous ACTH and cortisol concentrations without any intervention as well as cortisol concentrations measured after dexamethasone suppression and single dose administration of (i) 0.5–10 mg hydrocortisone as granules, (ii) 20 mg hydrocortisone as granules and intravenous bolus. A stepwise model development workflow was used: A newly developed model for endogenous ACTH and cortisol was merged with a refined hydrocortisone pharmacokinetic model. The joint model was used to simulate ACTH and cortisol trajectories in CAH patients with varying degrees of enzyme deficiency, with or without hydrocortisone administration, and healthy individuals. Time-dependent ACTH-driven endogenous cortisol production and cortisol-mediated feedback inhibition of ACTH secretion processes were quantified and implemented in the model. Comparison of simulated ACTH and cortisol trajectories between CAH patients and healthy individuals showed the importance of administering hydrocortisone before morning ACTH secretion peak time to suppress ACTH overproduction observed in untreated CAH patients. The developed framework allowed to gain insights on the physiological mechanisms of the HPA axis regulation, its perturbations in CAH and interaction with hydrocortisone administration, paving the way towards cortisol replacement therapy optimization. Graphical Abstract

Sex-specific variation in species interactions matters in ecological communities - Elena Gissi; Maurice Codespoti Goodman; Robin Elahi; Jamie M. McDevitt-Irwin; Natalie S. Arnoldi; Nur Arafeh-Dalmau; Christopher J. Knight; Carolina Olguín-Jacobson; Melissa Palmisciano; Ceyenna M. Tillman; Giulio A. De Leo; Fiorenza Micheli (Trends in Ecology & Evolution, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Plastic pollution and human pathogens: Towards a conceptual shift in risk management at bathing water and beach environments - David M. Oliver; Rebecca Metcalf; Davey L. Jones; Sabine Matallana-Surget; David N. Thomas; Peter Robins; Constance L. Tulloch; Benjamin M. Cotterell; Gwion Williams; Joseph A. Christie-Oleza; Richard S. Quilliam (Water Research, 2024)

Investigating the application of organic geochemical techniques to tropical Anjohibe (Madagascar) stalagmites - Robin R. Dawson; Isla S. Castañeda; Stephen J. Burns; Jeffrey M. Salacup; Nick Scroxton; David McGee; Peterson Faina; Laurie R. Godfrey; Lovasoa Ranivoharimanana (Organic Geochemistry, 2024)

Probabilistic assessment of deep geothermal resources in the Cornubian Batholith and their development in Cornwall and Devon, United Kingdom - Aysegul Turan; Christopher S Brown; Robin Shail; Ingo Sass (Geothermics, 2024)

Tropical forest succession increases tree taxonomic and functional richness but decreases evenness - Masha T. van der Sande; Lourens Poorter; Géraldine Derroire; Mario Marcos do Espirito Santo; Madelon Lohbeck; Sandra C. Müller; Radika Bhaskar; Michiel van Breugel; Juan Manuel Dupuy‐Rada; Sandra M. Durán; Catarina C. Jakovac; Horacio Paz; et al. (Global Ecology and Biogeography, 2024)
Aim Successional changes in functional diversity provide insights into community assembly by indicating how species are filtered into local communities based on their traits. Here, we assess successional changes in taxonomic and functional richness, evenness and redundancy along gradients of climate, soil pH and forest cover. Location Neotropics. Time period Last 0–100 years. Major taxa studied Trees. Methods We used 22 forest chronosequence studies and 676 plots across the Neotropics to analyse successional changes in Hill's taxonomic and functional diversity of trees, and how these successional changes vary with continental‐scale gradients in precipitation, soil pH and surrounding forest cover. Results Taxonomic and functional richness and functional redundancy increased, while taxonomic and functional evenness decreased over time. Functional richness and evenness changed strongly when not accounting for taxonomic richness, but changed more weakly after statistically accounting for taxonomic richness, indicating that changes in functional diversity are largely driven by taxonomic richness. Nevertheless, the successional increases in functional richness when correcting for taxonomic richness may indicate that environmental heterogeneity and limiting similarity increase during succession. The taxonomically‐independent successional decreases in functional evenness may indicate that stronger filtering and competition select for dominant species with similar trait values, while many rare species and traits are added to the community. Such filtering and competition may also lead to increased functional redundancy. The changes in taxonomically‐independent functional diversity varied with resource availability and were stronger in harsh, resource‐poor environments, but weak in benign, productive environments. Hence, in resource‐poor environments, environmental filtering and facilitation are important, whereas in productive environments, weaker abiotic filtering allows for high initial functional diversity and weak successional changes. Main conclusion We found that taxonomic and functional richness and functional redundancy increased and taxonomic and functional evenness decreased during succession, mainly caused by the increasing number of rare species and traits due to the arrival of new species and due to changing (a)biotic filters.

Female mountain gorillas form enduring social relationships - Riley N. Derby; Winnie Eckardt; Tara S. Stoinski; Robin E. Morrison; Aaron A. Sandel (Animal Behaviour, 2024)

Tree demographic strategies largely overlap across succession in Neotropical wet and dry forest communities - Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Dylan Craven; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Bruno Hérault; Catarina C. Jakovac; et al. (Ecology, 2024)
Secondary tropical forests play an increasingly important role in carbon budgets and biodiversity conservation. Understanding successional trajectories is therefore imperative for guiding forest restoration and climate change mitigation efforts. Forest succession is driven by the demographic strategies—combinations of growth, mortality and recruitment rates—of the tree species in the community. However, our understanding of demographic diversity in tropical tree species stems almost exclusively from old‐growth forests. Here, we assembled demographic information from repeated forest inventories along chronosequences in two wet (Costa Rica, Panama) and two dry (Mexico) Neotropical forests to assess whether the ranges of demographic strategies present in a community shift across succession. We calculated demographic rates for >500 tree species while controlling for canopy status to compare demographic diversity (i.e., the ranges of demographic strategies) in early successional (0–30 years), late successional (30–120 years) and old‐growth forests using two‐dimensional hypervolumes of pairs of demographic rates. Ranges of demographic strategies largely overlapped across successional stages, and early successional stages already covered the full spectrum of demographic strategies found in old‐growth forests. An exception was a group of species characterized by exceptionally high mortality rates that was confined to early successional stages in the two wet forests. The range of demographic strategies did not expand with succession. Our results suggest that studies of long‐term forest monitoring plots in old‐growth forests, from which most of our current understanding of demographic strategies of tropical tree species is derived, are surprisingly representative of demographic diversity in general, but do not replace the need for further studies in secondary forests.

Risk-based public health impact assessment for drinking water contamination emergencies - Taler S. Bixler; M. Robin Collins; Weiwei Mo (Science of The Total Environment, 2024)

Food Insecurity Among Aging SNAP Participants and Eligible Nonparticipants in Two Predominantly Low-Income Black Neighborhoods: Implications for SNAP Enrollment and Outreach for Older Adults - Sameer M. Siddiqi; Jonathan Cantor; Madhumita Ghosh Dastidar; Robin Beckman; Andrea S. Richardson; Matthew Baird; Rachel M. Burns; Tamara Dubowitz (Journal of the Academy of Nutrition and Dietetics, 2024)

Cretaceous beetles of the Jinju Formation (Coleoptera): An overview of the Jinju Formation, its coleopteran diversity, and past and future research - Soo Bin Lee; Yan-Da Li; Chenyang Cai; Michael S. Engel; Gi Soo Nam; Jong Kyun Park; André Nel; Josh Jenkins Shaw; Corentin Jouault; Andrei Legalov; Robin Kundrata (Journal of Asia-Pacific Entomology, 2024)

MAST® D72C test: a novel option for ESBL, AmpC and carbapenemase detection - C. C. Noubam-Tchatat; E. Maurin; S. Proust; R. Beyrouthy; R. Bonnet; Frederic Robin (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Petrogenesis of volcanic rocks from the Quaternary Eifel volcanic fields, Germany: detailed insights from combined trace-element and Sr–Nd–Hf–Pb–Os isotope data - Mike W. Jansen; Carsten Münker; Josua J. Pakulla; Eric Hasenstab-Dübeler; Christian S. Marien; Toni Schulz; Maria Kirchenbaur; Kathrin P. Schneider; Robin Tordy; Vera Schmitt; Frank Wombacher (Contributions to Mineralogy and Petrology, 2024)
Quaternary rocks from the East and West Eifel volcanic fields in western Germany are a key suite of intraplate volcanic rocks that can provide insights into volcanism of the Central European Volcanic Province (CEVP) and into continental intraplate volcanism in general. We present a comprehensive dataset for Eifel lavas including isotope as well as major and trace element data for 59 samples covering representative compositions of the different volcanic fields. In line with previous studies, the lavas are all SiO 2 -undersaturated, alkaline-rich and mainly comprise primitive basanites, melilitites, and nephelinites (Mg# ≥ 57). Geochemical compositions of samples from both volcanic subfields display distinct differences in their trace-element as well as radiogenic isotope compositions, largely confirming previous subdivisions. Coupled trace-element and radiogenic Sr–Nd–Hf–Pb–Os isotope compositions can now provide firm evidence for spatially heterogeneous mantle sources and compositionally distinct magmatic pulses. Within the West Eifel Field, Sr–Nd–Pb isotope compositions of the younger (≤80 ka), ONB-suite (olivine-nephelinite-basanite) are similar to FOZO (FOcal ZOne) or the EAR (European Asthenospheric Reservoir) and resemble compositions that have been previously reported from plume-sourced ocean island basalts (OIB). In marked difference, older (700 Ma to 80 ka) volcanic rocks from the F-suite (Foidite) in the West Eifel field and from the entire east Eifel Field tap a more enriched mantle component, as illustrated by more radiogenic Sr isotope ( 86 Sr/ 87 Sr up to 0.705408) and variable Pb isotope compositions ( 206 Pb/ 204 Pb = 18.61–19.70, 207 Pb/ 204 Pb = 15.62–15.67 and 208 Pb/ 204 Pb = 38.89–39.76). Combined trace-element compositions of ONB-suite samples are in good agreement with results from batch melting models suggesting a hybrid composition of Eifel magmas formed through mixing 10% of a FOZO-like melt with 90% of a DMM-like melt, similar to melts from the Tertiary HEVF. However, radiogenic Sr–Nd–Pb isotope compositions of F-suite and EEVF and some ONB lavas require the admixture of melts from lithospheric mantle sources. Elevated Nb/Ta and Lu/Hf ratios in combination with variable 187 Os/ 188 Os ratios can now demonstrate the presence of residual carbonated eclogite components, either in the lithosphere or in the asthenospheric mantle. Finally, by combining geochemical and temporal constraints of Tertiary and Quaternary volcanism it becomes evident that CEVP volcanism in central and western Germany has resulted from compositionally distinct magmatic pulses that tap separate mantle sources. Although the presence of a mantle plume can neither be fully confirmed nor excluded, plume-like melt pulses which partially tap carbonated eclogite domains that interact to variable extents with the lithosphere provide a viable explanation for the temporal and compositional cyclicity of CEVP volcanism.

Luminescence Thermometry Based on the Upconversion Luminescence from the Stark Sublevels of BaY2F8:Yb3+, Tm3+ Phosphor - Ashwini K. Sharma; Govind B. Nair; S. J. Dhoble; Robin E. Kroon; J. J. Terblans; H. C. Swart (Journal of Fluorescence, 2024)
Visible and near-infrared (NIR) upconversion luminescence (UCL) emissions originating from the BaY 2 F 8 : Yb 3+ , Tm 3+ systems were investigated under a laser excitation at 980 nm. The BaY 2 F 8 :20 mol% Yb 3+ , x mol% Tm 3+ and BaY 2 F 8 : y mol% Yb 3+ , 0.5 mol% Tm 3+ phosphors showed prominent UCL at 800 and 810 nm. The optimized doping concentrations of Yb 3+ and Tm 3+ in the BaY 2 F 8 host matrix were evaluated, their spectroscopic properties were determined, and studies on their temperature-dependent behaviour were carried out. The temperature-sensing properties were studied by generating the fluorescence intensity ratio (FIR) of the UCL peaks originating from the thermally-coupled energy levels of the Tm 3+ ions. The Stark sublevels of 1 G 4 level of Tm 3+ ions were utilized to estimate the temperature-sensing abilities of the phosphor. Graphical Abstract

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Fungal endophytes of the invasive grass Eragrostis lehmanniana shift metabolic expression in response to native and invasive grasses - Taylor A. Portman; A. Elizabeth Arnold; Robin G. Bradley; Jeffrey S. Fehmi; Craig Rasmussen; Malak M. Tfaily (Fungal Ecology, 2024)

Characterizing northern white-cedar communities in harvested and unharvested lowland forests of Michigan, USA - Robin Michigiizhigookwe Clark; Christopher R. Webster; Laura S. Kenefic; Christel C. Kern; Rodney A. Chimner (Wetlands Ecology and Management, 2024)

Biologically Important Areas II for cetaceans within U.S. and adjacent waters - West Coast Region - John Calambokidis; Michaela A. Kratofil; Daniel M. Palacios; Barbara A. Lagerquist; Gregory S. Schorr; M. Bradley Hanson; Robin W. Baird; Karin A. Forney; Elizabeth A. Becker; R. Cotton Rockwood; Elliott L. Hazen (Frontiers in Marine Science, 2024)
Here we update U.S. West Coast Biologically Important Areas (BIAs) that were published in 2015 using new data and approaches. Additionally, BIAs were delineated for two species that were not delineated in the 2015 BIAs: fin whales and Southern Resident killer whales (SRKW). While harbor porpoise BIAs remained the same, substantial changes were made for other species including identifying both larger overall areas (parent BIAs) and smaller core areas (child BIAs). For blue, fin, and humpback whales we identified, delineated, and scored BIAs using the overlap between the distribution and relative density from three data sources, leveraging the strengths and weaknesses of these approaches: 1) habitat density models based on Southwest Fisheries Science Center (SWFSC) line-transect data from systematic ship surveys conducted through 2018, 2) satellite tag data from deployments conducted by three research groups, and 3) sightings of feeding behavior from non-systematic effort mostly associated with small-boat surveys for photo-identification conducted by Cascadia Research Collective. While the previous BIAs were based solely on a more subjective assignment from only the small boat sightings, here we incorporate the other two data sources and use a more rigorous, quantitative approach to identify higher density areas and integrate the data types. This resulted in larger, better-supported, objective BIAs compared to the previous effort. Our methods are also more consistent with the delineation of BIAs in other regions. For SRKWs, the parent BIA was based on a modification of the Critical Habitat boundaries defined by the National Oceanographic and Atmospheric Administration (NOAA) and the Department of Fisheries and Oceans (DFO) Canada; a core BIA highlighting areas of intensified use was identified using both NOAA’s Critical Habitat and kernel density analyses of satellite tag data. Gray whale BIAs were re-evaluated for the migratory corridor of Eastern North Pacific gray whales, for Pacific Coast Feeding Group feeding areas, and for gray whales that feed regularly in Puget Sound.

Controls on Quaternary geochemical and mineralogical variability in the Koora Basin and South Kenya Rift - R. Bernhart Owen; Nathan Rabideaux; Jordon Bright; Carolina Rosca; Robin W. Renaut; Richard Potts; Anna K. Behrensmeyer; Alan L. Deino; Andrew S. Cohen; Veronica Muiruri; René Dommain (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Comparative evaluation of management modules against Maydis leaf blight disease in maize (Zea mays) - Sumit Kumar Aggarwal; K. S. Hooda; Harleen Kaur; Robin Gogoi; Prashant Chauhan; P. K. Bagaria; Pardeep Kumar; Mukesh Choudhary; Rahul Kumar Tiwari; Milan Kumar Lal (European Journal of Plant Pathology, 2024)

Decrease of the spatial variability and local dimension of the Euro-Atlantic eddy-driven jet stream with global warming - Robin Noyelle; Vivien Guette; Akim Viennet; Bénédicte Colnet; Davide Faranda; Andreia N. S. Hisi; Pascal Yiou (Climate Dynamics, 2024)

Determination of biogeochemical rate constants for Chilika Lake, a tropical brackish water lagoon on the east coast of India - Sivaji Patra; Charan Kumar Basuri; Pradipta R. Muduli; Vishnu Vardhan Kanuri; Robin R. S.; Ganguly Dipnarayan; Abhilash K. R.; Lovaraju Avvari; Uma Sankar Panda; Dash S. K.; Ramana Murthy M. V. (Frontiers in Marine Science, 2024)

Predicting potential spawning areas of European bass, Dicentrarchus labrax, in the Irish and Celtic seas - H. Lincoln; P.E. Robins; S-B. Wilmes; S. Pérez-Mayol; A. Moore; S. Simpson; A. Goward-Brown; C. Heney; S. Malham; B. Morales-Nin; N. Hold; I.D. McCarthy (Fisheries Research, 2024)

Vasorelaxant effect of a phenylethylamine analogue based on schwarzinicine A an alkaloid isolated from the leaves of Ficus schwarzii - Kayatri Govindaraju; Yin Ying Mak; Fong Kai Lee; Claudia C. Bauer; Kuan Hon Lim; Robin S. Bon; Cin Kong; Sue Mian Then; Kang Nee Ting (Phytochemistry Letters, 2024)

Household Food Insecurity and Maternal-Toddler Fruit and Vegetable Dietary Concordance - Carol Duh-Leong; Robin Ortiz; Mary Jo Messito; Michelle W. Katzow; Christina N. Kim; Radhika Teli; Rachel S. Gross (Journal of Nutrition Education and Behavior, 2024)

Testate amoebae (Arcellinida, Amoebozoa) community diversity in New England bogs and fens assessed through lineage-specific amplicon sequencing - Olivia K. Dufour; Evie Hoffman; Robin S. Sleith; Laura A. Katz; Agnes K.M. Weiner; Taylor R. Sehein (European Journal of Protistology, 2024)

Microplastics in oral healthcare products (OHPs) and their environmental health risks and mitigation measures - G.B Protyusha; Kavitha B; R.S Robin; Nithin A; T.R Ineyathendral; S. Shruthi Shivani; Anandavelu I; Shyam Sivasamy; V. Deepak Samuel; Purvaja R (Environmental Pollution, 2024)

The Association of Upper Airway Anatomy with Brain Structure: The Multi-Ethnic Study of Atherosclerosis - Robin M. Nance; Alison E. Fohner; Robyn L. McClelland; Susan Redline; R. Nick Bryan; Lisa Desiderio; Mohamad Habes; WT Longstreth, Jr; Richard J. Schwab; Andrew S. Wiemken; Susan R. Heckbert (Brain Imaging and Behavior, 2024)

Uncovering the genetic architecture of parallel evolution - Maddie E. James; Robin N. Allsopp; Jeffrey S. Groh; Avneet Kaur; Melanie J. Wilkinson; Daniel Ortiz‐Barrientos (Molecular Ecology, 2023)
Identifying the genetic architecture underlying adaptive traits is exceptionally challenging in natural populations. This is because associations between traits not only mask the targets of selection but also create correlated patterns of genomic divergence that hinder our ability to isolate causal genetic effects. Here, we examine the repeated evolution of components of the auxin pathway that have contributed to the replicated loss of gravitropism (i.e. the ability of a plant to bend in response to gravity) in multiple populations of the Senecio lautus species complex in Australia. We use a powerful approach which combines parallel population genomics with association mapping in a Multiparent Advanced Generation Inter‐Cross (MAGIC) population to break down genetic and trait correlations to reveal how adaptive traits evolve during replicated evolution. We sequenced auxin and shoot gravitropism‐related gene regions in 80 individuals from six natural populations (three parallel divergence events) and 133 individuals from a MAGIC population derived from two of the recently diverged natural populations. We show that artificial tail selection on gravitropism in the MAGIC population recreates patterns of parallel divergence in the auxin pathway in the natural populations. We reveal a set of 55 auxin gene regions that have evolved repeatedly during the evolution of the species, of which 50 are directly associated with gravitropism divergence in the MAGIC population. Our work creates a strong link between patterns of genomic divergence and trait variation contributing to replicated evolution by natural selection, paving the way to understand the origin and maintenance of adaptations in natural populations.

Challenges and opportunities in the use of ponds and pondscapes as Nature-based Solutions - M. Cuenca-Cambronero; M. Blicharska; J.-A. Perrin; T. A. Davidson; B. Oertli; M. Lago; M. Beklioglu; M. Meerhoff; M. Arim; J. Teixeira; L. De Meester; J. Biggs; et al. (Hydrobiologia, 2023)
Ponds and “pondscapes” (networks of ponds) are crucial habitats for biodiversity and for delivering multiple benefits to humans, so-called “Nature’s Contribution to People”, such as climate mitigation and adaptation to climate change, creation, and maintenance of habitat for biodiversity, water purification, flood mitigation and cultural benefits (e.g., recreational possibilities). However, ponds are not often considered as Nature-based Solutions to provide all these benefits. In addition, there is insufficient knowledge on how to manage and restore ponds to maximise their role to increase the resilience of ecosystems and society to climate change. To facilitate improved implementation of ponds as Nature-based Solutions for the delivery of a wide range of Nature Contributions to People, it is important to generate and integrate biodiversity, ecosystems, societal, economic and policy knowledge. Hence, there is a need for evidence-based guidance to support the broader use of ponds. Here, we review the role of ponds and pondscapes in delivering Nature’s Contributions to People and provide an overview of the challenges and opportunities for their broader implementation as Nature-based Solutions. Finally, we propose a conceptual framework that can help the implementation of pond Nature-based Solutions, and that outlines future research needs.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Herbivorous Grass Carp (Ctenopharyngodon idella) Exhibit Greater Olfactory Response to Amino Acids Than Filter-Feeding Bighead (Hypophthalmichthys nobilis) and Silver Carp (Hypophthalmichthys molitrix) - Mark L. Wildhaber; Benjamin M. West; Karlie K. Ditter; Alex S. Peterson; Robin D. Calfee; Zachary D. Beaman (Fishes, 2023)
Due to their invasiveness in North America, grass (Ctenopharyngodon idella), bighead (Hypophthalmichthys nobilis), and silver carp (Hypophthalmichthys molitrix) are management priorities. Comparing electrophysiological responses to olfactory cues, such as amino acids, could help identify stimuli to facilitate management efforts (i.e., repellants or baits). We assessed olfactory response magnitude to individual amino acids between fish species using electro-olfactogram recording techniques (EOG). We measured EOG responses (peak EOG magnitude) of juvenile grass (n = 21), bighead (n = 21), and silver carp (n = 22) to 10−4 molar amino acid solutions containing one of L-alanine, L-arginine, L-aspartic acid, L-asparagine, L-glutamine, or L-glutamic acid. Amino acid EOG responses differed across species; grass carp had the greatest mean EOG response. Statistical analyses showed no inter- or intra-specific differences in EOG response among amino acids. The greater EOG response of grass carp matched their selective grazing habits compared to more passive, generalist-tending, filter-feeding bighead and silver carp. All amino acids elicited significant EOG responses in all species, meaning they are candidates for future behavioral research. Such research could explore the management potential of amino acids, testing if amino acids are attractants or deterrents that could facilitate the removal of these fishes by congregating and/or directing movement.

Vulnerability and resilience of living marine resources to the Deepwater Horizon oil spill: an overview - Steven A. Murawski; Patrick T. Schwing; William F. Patterson; Tracey T. Sutton; Paul A. Montagna; Rosanna J. Milligan; Samantha B. Joye; Len Thomas; Joshua P. Kilborn; Claire B. Paris; Robin Faillettaz; David S. Portnoy; et al. (Frontiers in Marine Science, 2023)
The 2010 Deepwater Horizon (DWH) oil well blowout in the Gulf of Mexico (GoM) was the largest and perhaps most consequential accidental marine oil spill in global history. This paper provides an overview of a Research Topic consisting of four additional papers that: (1) assemble time series data for ecosystem components in regions impacted by the spill, and (2) interpret temporal changes related to the vulnerability of species and ecosystems to DWH and the ensuing resilience to perturbation. Time series abundance data for many taxa pre-date DWH, often by decades, thus allowing an assessment of population- and community-level impacts. We divided the north central GoM into four interconnected “eco-types”: the coastal/nearshore, continental shelf, open-ocean pelagic and deep benthic. Key taxa in each eco-type were evaluated for their vulnerability to the circumstances of the DWH spill based on population overlap with oil, susceptibility to oil contamination, and other factors, as well their imputed resilience to population-level impacts, based on life history metrics, ecology and post-spill trajectories. Each taxon was scored as low, medium, or high for 13 vulnerability attributes and 11 resilience attributes to produce overall vulnerability and resilience scores, which themselves were also categorical (i.e., low, medium, or high). The resulting taxon-specific V-R scores provide important guidance on key species to consider and monitor in the event of future spills similar to DWH. Similar analyses may also guide resource allocation to collect baseline data on highly vulnerable taxa or those with low resilience potential in other ecosystems. For some species, even a decade of observation has been insufficient to document recovery given chronic, long-term exposure to DWH oil remaining in all eco-types and because of impacts to the reproductive output of long-lived species. Due to the ongoing threats of deep-water blowouts, continued surveillance of populations affected by DWH is warranted to document long-term recovery or change in system state. The level of population monitoring in the open-ocean and deep benthic eco-types has historically been low and is inconsistent with the continued migration of the oil industry to the ultra-deep (≥1,500 m) where the majority of leasing, exploration, and production now occurs.

Solar wind driven influences on the Martian oxygen corona: Constraints on atmospheric sputtering from a synthesis of MAVEN measurements during solar minimum - Robin Ramstad; David A. Brain; Yaxue Dong; Jasper S. Halekas; James M. McFadden; David L. Mitchell; Jared Espley; Francis G. Eparvier; Bruce M. Jakosky (Icarus, 2023)

Woronichinia naegeliana: A common nontoxigenic component of temperate freshwater cyanobacterial blooms with 30% of its genome in transposons - Theo W. Dreher; Robin Matthews; Edward W. Davis; Ryan S. Mueller (Harmful Algae, 2023)

A Letter to Your Care Providers: Implementation and Analysis of a Letter-based Advance Care Planning Initiative for Gynecologic Oncology Patients - Catherine N. Zivanov; Anne Coogan; Robin R. Lane; Sara G. Lin; Sarah C. Reed; Marc A. Robinson; Mohana Karlekar; Lauren S. Prescott; Alaina J. Brown (Journal of Cancer Education, 2023)

Successional shifts in tree demographic strategies in wet and dry Neotropical forests - Nadja Rüger; Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Dylan Craven; Bruno Hérault; et al. (Global Ecology and Biogeography, 2023)
Aim Tropical forest succession and associated changes in community composition are driven by species demographic rates, but how demographic strategies shift during succession remains unclear. Our goal was to identify generalities in demographic trade‐offs and successional shifts in demographic strategies across Neotropical forests that cover a large rainfall gradient and to test whether the current conceptual model of tropical forest succession applies to wet and dry forests. Location Mexico and Central America. Time period 1985–2018. Major taxa studied Trees. Methods We used repeated forest inventory data from two wet and two dry forests to quantify demographic rates of 781 tree species. For each forest, we explored the main demographic trade‐offs and assigned tree species to five demographic groups by performing a weighted principal components analysis to account for differences in sample size. We aggregated the basal area and abundance across demographic groups to identify successional shifts in demographic strategies over the entire successional gradient from very young ( Results Across all forests, we found two demographic trade‐offs, namely the growth–survival trade‐off and the stature–recruitment trade‐off, enabling the data‐driven assignment of species to five demographic strategies. Fast species dominated early in succession and were then replaced by long‐lived pioneers in three forests. Intermediate and slow species increased in basal area over succession in all forests, but, in contrast to the current conceptual model, long‐lived pioneers continued to dominate until the old‐growth stage in all forests. The basal area of short‐lived breeders was low across all successional stages. Main conclusions The current conceptual model of Neotropical forest succession should be revised to incorporate the dominance of long‐lived pioneers in late‐successional and old‐growth forests. Moreover, the definition of consistent demographic strategies that show clear dominance shifts across succession substantially improves the mechanistic understanding and predictability of Neotropical forest succession.

Anthropogenic nitrogen pollution threats and challenges to the health of South Asian coral reefs - Stuart C. Painter; Yuri Artioli; Fathimath Hana Amir; Jessica Arnull; Raja S. Ganeshram; Nizam Ibrahim; V. Deepak Samuel; R.S. Robin; R. Raghuraman; R. Purvaja; R. Ramesh; Arjan Rajasuriya; et al. (Frontiers in Marine Science, 2023)
Nitrogen pollution is a widespread and growing problem in the coastal waters of South Asia yet the ecological impacts on the region’s coral ecosystems are currently poorly known and understood. South Asia hosts just under 7% of global coral reef coverage but has experienced significant and widespread coral loss in recent decades. The extent to which this coral ecosystem decline at the regional scale can be attributed to the multiple threats posed by nitrogen pollution has been largely overlooked in the literature. Here, we assess the evidence for nitrogen pollution impacts on corals in the central Indian Ocean waters of India, Sri Lanka and the Maldives. We find that there is currently limited evidence with which to clearly demonstrate widespread impacts on coral reefs from nitrogen pollution, including from its interactions with other stressors such as seawater warming. However, this does not prove there are no significant impacts, but rather it reflects the paucity of appropriate observations and related understanding of the range of potential impacts of nitrogen pollution at individual, species and ecosystem levels. This situation presents significant research, management and conservation challenges given the wide acceptance that such pollution is problematic. Following from this, we recommend more systematic collection and sharing of robust observations, modelling and experimentation to provide the baseline on which to base prescient pollution control action.

Wild Australian magpies learn to pull intact, not broken, strings to obtain food - Robin D. Johnsson; Papillon S. Veillet; Farley Connelly; John A. Endler; Timothy C. Roth; John A. Lesku (Behavioral Ecology and Sociobiology, 2023)
The string-pulling paradigm is an approach commonly used in the study of animal cognition to investigate problem-solving abilities. This test involves an out-of-reach reward that can only be acquired through pulling a string. Australian magpies ( Gymnorhina tibicen tyrannica ) can solve cognitive tasks requiring associative and reversal learning, spatial memory, and inhibitory control. Nonetheless, whether magpies can pass a test of means-end understanding—the string-pull test—is unclear. We tested wild magpies on a string-pulling task with five configurations, including a long loose string that required several pulls to obtain food, a short string that only required a single pull to complete, and two short strings—one intact and connected to the food reward; the other broken and unable to yield food when pulled. Of the 11 magpies tested, none solved the long string task at first presentation. Two naïve birds and three, subsequently trained, birds succeeded at the short string. Once proficient at the short string, four of these five birds then solved the long string task; in addition, three learned to choose a functional, intact string over a non-functional, broken string. Overall, these observations provide evidence that Australian magpies have the ability to solve string-pulling tasks but it remains unclear whether they do so by trial-and-error or if they possess means-end understanding. Significance statement We found, for the first time, that wild, free-ranging Australian magpies can learn to solve different versions of a string-pulling task; a version with a short string, a long string, and two strings next to each other where one of them was broken and non-functional (broken string task). Some magpies spontaneously solved the task with the short string, where other magpies required training, and magpies only managed to solve the task with the long string after they had succeeded on the short string task. Furthermore, some of the magpies solved the broken string task but required a high number of trials to do so. Overall, our findings show that Australian magpies have the ability to solve string-pulling tasks but it remains unclear whether they do so by trial-and-error or if they understand causal relations between objects.

Correction to: Plant-litter-soil feedbacks in common grass species are slightly negative and only marginally modified by litter exposed to insect herbivory - Jonathan R. De Long; Robin Heinen; S. Emilia Hannula; Renske Jongen; Katja Steinauer; T. Martijn Bezemer (Plant and Soil, 2023)

Plant-litter-soil feedbacks in common grass species are slightly negative and only marginally modified by litter exposed to insect herbivory - Jonathan R. De Long; Robin Heinen; S. Emilia Hannula; Renske Jongen; Katja Steinauer; T. Martijn Bezemer (Plant and Soil, 2023)
Purpose Insect herbivory affects plant growth, nutrient and secondary metabolite concentrations and litter quality. Changes to litter quality due to insect herbivory can alter decomposition, with knock on effects for plant growth mediated through the plant-litter-soil feedback pathway. Methods Using a multi-phase glasshouse experiment, we tested how changes in shoot and root litter quality of fast- and slow-growing grass caused by insect herbivores affect the performance of response plants in the soil in which the litter decomposed. Results We found that insect herbivory resulted in marginal changes to litter quality and did not affect growth when plants were grown with fast- versus slow-growing litter. Overall, presence of litter resulted in reduced root and shoot growth and this effect was significantly more negative in shoots versus roots. However, this effect was minimal, with a loss of c. 1.4% and 3.1% dry weight biomass in roots versus shoots, respectively. Further, shoot litter exposed to insect herbivory interacted with response plant identity to affect root growth. Conclusions Our results suggest that whether litter originates from plant tissues exposed to insect herbivory or not and its interaction with fast- versus slow-growing grasses is of little importance, but species-specific responses to herbivory-conditioned litter can occur. Taken collectively, the overall role of the plant-litter-soil feedback pathway, as well as its interaction with insect herbivory, is unlikely to affect broader ecosystem processes in this system.

Peering down the sink: A review of isoprene metabolism by bacteria - Robin A. Dawson; Andrew T. Crombie; Robert S. Jansen; Thomas J. Smith; Tim Nichol; Colin Murrell (Environmental Microbiology, 2023)
Isoprene (2‐methyl‐1,3‐butadiene) is emitted to the atmosphere each year in sufficient quantities to rival methane (>500 Tg C yr −1 ), primarily due to emission by trees and other plants. Chemical reactions of isoprene with other atmospheric compounds, such as hydroxyl radicals and inorganic nitrogen species (NO x ), have implications for global warming and local air quality, respectively. For many years, it has been estimated that soil‐dwelling bacteria consume a significant amount of isoprene (~20 Tg C yr −1 ), but the mechanisms underlying the biological sink for isoprene have been poorly understood. Studies have indicated or confirmed the ability of diverse bacterial genera to degrade isoprene, whether by the canonical iso ‐type isoprene degradation pathway or through other less well‐characterized mechanisms. Here, we review current knowledge of isoprene metabolism and highlight key areas for further research. In particular, examples of isoprene‐degraders that do not utilize the isoprene monooxygenase have been identified in recent years. This has fascinating implications both for the mechanism of isoprene uptake by bacteria, and also for the ecology of isoprene‐degraders in the environments.

Prediction of the severity of Dothistroma needle blight in radiata pine using plant based traits and narrow band indices derived from UAV hyperspectral imagery - Michael S. Watt; Tomás Poblete; Dilshan de Silva; Honey Jane C. Estarija; Robin J.L. Hartley; Ellen Mae C. Leonardo; Peter Massam; Henning Buddenbaum; Pablo J. Zarco-Tejada (Agricultural and Forest Meteorology, 2023)

Direct rain splash and downwearing of internal surfaces as an important erosion process in alluvial gully development - James S. Daley; John R. Spencer; Andrew P. Brooks; Justin C. Stout; Robin Thwaites (CATENA, 2023)

Experimental shake table validation of damping behaviour in inerter-based dampers - Predaricka Deastra; David J. Wagg; Neil D. Sims; Robin S. Mills (Bulletin of Earthquake Engineering, 2023)

Pathways of methane removal in the sediment and water column of a seasonally anoxic eutrophic marine basin - Olga M. Żygadłowska; Jessica Venetz; Robin Klomp; Wytze K. Lenstra; Niels A. G. M. van Helmond; Thomas Röckmann; Anna J. Wallenius; Paula Dalcin Martins; Annelies J. Veraart; Mike S. M. Jetten; Caroline P. Slomp (Frontiers in Marine Science, 2023)
Methane (CH 4 ) is a key greenhouse gas. Coastal areas account for a major proportion of marine CH 4 emissions. Eutrophication and associated bottom water hypoxia enhance CH 4 production in coastal sediments. Here, we assess the fate of CH 4 produced in sediments at a site in a seasonally anoxic eutrophic coastal marine basin (Scharendijke, Lake Grevelingen, the Netherlands) in spring (March) and late summer (September) in 2020. Removal of CH 4 in the sediment through anaerobic oxidation with sulfate ( S O 4 2 - ) is known to be incomplete in this system, as confirmed here by only slightly higher values of δ 13 C-CH 4 and δD-CH 4 in the porewater in the shallow sulfate-methane-transition zone (~5-15 cm sediment depth) when compared to deeper sediment layers. In March 2020, when the water column was fully oxygenated, CH 4 that escaped from the sediment was at least partially removed in the bottom water through aerobic oxidation. In September 2020, when the water column was anoxic below ~35 m water depth, CH 4 accumulated to high concentrations (up to 73 µmol L -1 ) in the waters below the oxycline. The sharp counter gradient in oxygen and CH 4 concentrations at ~35 m depth and increase in δ 13 C-CH 4 and δD-CH 4 above the oxycline indicate mostly aerobic water column removal of CH 4 . Water column profiles of particulate and dissolved Fe and Mn suggest redox cycling of both metals at the oxycline, pointing towards a potential role of metal oxides in CH 4 removal. Water column profiles of N H 4 + and N O 3 - indicate removal of both solutes near the oxycline. Analyses of 16S rRNA gene sequences retrieved from the water column reveal the presence of aerobic CH 4 oxidizing bacteria ( Methylomonadaceae ) and anaerobic methanotrophic archaea ( Methanoperedenaceae ), with the latter potentially capable of N O 3 - and/or metal-oxide dependent CH 4 oxidation, near the oxycline. Overall, our results indicate sediment and water column removal of CH 4 through a combination of aerobic and anaerobic pathways, which vary seasonally. Some of the CH 4 appears to escape from the surface waters to the atmosphere, however. We conclude that eutrophication may make coastal waters a more important source of CH 4 to the atmosphere than commonly assumed.

Integration of multi-scale porosimetry and multi-modal imaging in the study of structure-transport relationships in porous catalyst pellets - Suleiman Mousa; Vladimir Novak; Robin S. Fletcher; Monica Garcia; Norman Macleod; Martin Corfield; Sean P. Rigby (Chemical Engineering Journal, 2023)

Neuroimaging is the new “spatial omic”: multi-omic approaches to neuro-inflammation and immuno-thrombosis in acute ischemic stroke - Benjamin Maïer; Amy S. Tsai; Jakob F. Einhaus; Jean-Philippe Desilles; Benoît Ho-Tin-Noé; Benjamin Gory; Marina Sirota; Richard Leigh; Robin Lemmens; Gregory Albers; Jean-Marc Olivot; Mikael Mazighi; et al. (Seminars in Immunopathology, 2023)

Towards a genetic theory of island biogeography: Inferring processes from multidimensional community‐scale data - Isaac Overcast; Guillaume Achaz; Robin Aguilée; Carmelo Andújar; Paula Arribas; Thomas J. Creedy; Evan P. Economo; Rampal S. Etienne; Rosemary Gillespie; Claire Jacquet; Flora Jay; Susan Kennedy; et al. (Global Ecology and Biogeography, 2023)
Background MacArthur and Wilson's theory of island biogeography has been a foundation for obtaining testable predictions from models of community assembly and for developing models that integrate across scales and disciplines. Historically, however, these developments have focused on integration across ecological and macroevolutionary scales and on predicting patterns of species richness, abundance distributions, trait data and/or phylogenies. The distribution of genetic variation across species within a community is an emerging pattern that contains signatures of past population histories, which might provide an historical lens for the study of contemporary communities. As intraspecific genetic diversity data become increasingly available at the scale of entire communities, there is an opportunity to integrate microevolutionary processes into our models, moving towards development of a genetic theory of island biogeography. Motivation/goal We aim to promote the development of process‐based biodiversity models that predict community genetic diversity patterns together with other community‐scale patterns. To this end, we review models of ecological, microevolutionary and macroevolutionary processes that are best suited to the creation of unified models, and the patterns that these predict. We then discuss ongoing and potential future efforts to unify models operating at different organizational levels, with the goal of predicting multidimensional community‐scale data including a genetic component. Main conclusions Our review of the literature shows that despite recent efforts, further methodological developments are needed, not only to incorporate the genetic component into existing island biogeography models, but also to unify processes across scales of biological organization. To catalyse these developments, we outline two potential ways forward, adopting either a top‐down or a bottom‐up approach. Finally, we highlight key ecological and evolutionary questions that might be addressed by unified models including a genetic component and establish hypotheses about how processes across scales might impact patterns of community genetic diversity.

Multiple modules for the management of banded leaf and sheath blight of maize in India - S. K. Aggarwal; K. S. Hooda; P. K. Bagaria; Harleen Kaur; Robin Gogoi; Prashant Chauhan; R. P. Singh (Indian Phytopathology, 2022)

Corrigendum: Associations between cyanobacteria and indices of secondary production in the western basin of Lake Erie - James H. Larson; Mary Anne Evans; Robert J. Kennedy; Sean W. Bailey; Keith A. Loftin; Zachary R. Laughrey; Robin A. Femmer; Jeff S. Schaeffer; William B. Richardson; Timothy T. Wynne; J. C. Nelson; Joseph W. Duris (Limnology and Oceanography, 2022)
In the last year, we became aware that data used in our above‐referenced manuscript from 2018 published in Limnology and Oceanography contained significant errors. In the 2018 manuscript, we found that indices of secondary production were negatively correlated to indices of cyanobacterial abundance and toxicity. Unfortunately, one of our indices of cyanobacterial abundance (biovolume) and our measurement of toxicity (microcystin concentration) were inaccurate in the data we used in the 2018 manuscript. Upon discovering these errors, we immediately began correcting the repositories where these data were available. Having corrected those data repositories, we are now reporting on the re‐analysis of the data using the methods previously described in the 2018 manuscript. Although the relationships are slightly different, our interpretation is that the conclusions of the 2018 manuscript are still valid using the corrected data. The data errors we experienced were traced to a spreadsheet that was used to share data among the research team, which had errors caused by mistakes in copy‐pasting formulas instead of data and ‘inadvertent’ edits that were saved by the spreadsheet's auto‐save function. We apologize to the scientific community for these errors.

A dynamic spike threshold with correlated noise predicts observed patterns of negative interval correlations in neuronal spike trains - Robin S. Sidhu; Erik C. Johnson; Douglas L. Jones; Rama Ratnam (Biological Cybernetics, 2022)
Negative correlations in the sequential evolution of interspike intervals (ISIs) are a signature of memory in neuronal spike-trains. They provide coding benefits including firing-rate stabilization, improved detectability of weak sensory signals, and enhanced transmission of information by improving signal-to-noise ratio. Primary electrosensory afferent spike-trains in weakly electric fish fall into two categories based on the pattern of ISI correlations: non-bursting units have negative correlations which remain negative but decay to zero with increasing lags (Type I ISI correlations), and bursting units have oscillatory (alternating sign) correlation which damp to zero with increasing lags (Type II ISI correlations). Here, we predict and match observed ISI correlations in these afferents using a stochastic dynamic threshold model. We determine the ISI correlation function as a function of an arbitrary discrete noise correlation function $${{\,R\,}}_k$$ R k , where k is a multiple of the mean ISI. The function permits forward and inverse calculations of the correlation function. Both types of correlation functions can be generated by adding colored noise to the spike threshold with Type I correlations generated with slow noise and Type II correlations generated with fast noise. A first-order autoregressive (AR) process with a single parameter is sufficient to predict and accurately match both types of afferent ISI correlation functions, with the type being determined by the sign of the AR parameter. The predicted and experimentally observed correlations are in geometric progression. The theory predicts that the limiting sum of ISI correlations is $$-0.5$$ - 0.5 yielding a perfect DC-block in the power spectrum of the spike train. Observed ISI correlations from afferents have a limiting sum that is slightly larger at $$-0.475 ± 0.04$$ - 0.475 ± 0.04 ( $$\text {mean} ± \text {s.d.}$$ mean ± s.d. ). We conclude that the underlying process for generating ISIs may be a simple combination of low-order AR and moving average processes and discuss the results from the perspective of optimal coding.

Association between toxic and essential metals in blood and global DNA methylation among electronic waste workers in Agbogbloshie, Ghana - Ibrahim Issah; John Arko-Mensah; Laura S. Rozek; Katie R. Zarins; Duah Dwomoh; Thomas P. Agyekum; Niladri Basu; Stuart Batterman; Thomas G. Robins; Julius N. Fobil (Environmental Science and Pollution Research, 2022)

Chemical control of post-flowering stalk rot of maize with new fungicide formulations - Robin Gogoi; N. S. Sipani; S. N. Rai (Indian Phytopathology, 2022)

One hundred years of advances in volcano seismology and acoustics - Robin S. Matoza; Diana C. Roman (Bulletin of Volcanology, 2022)
Since the 1919 foundation of the International Association of Volcanology and Chemistry of the Earth’s Interior (IAVCEI), the fields of volcano seismology and acoustics have seen dramatic advances in instrumentation and techniques, and have undergone paradigm shifts in the understanding of volcanic seismo-acoustic source processes and internal volcanic structure. Some early twentieth-century volcanological studies gave equal emphasis to barograph (infrasound and acoustic-gravity wave) and seismograph observations, but volcano seismology rapidly outpaced volcano acoustics and became the standard geophysical volcano-monitoring tool. Permanent seismic networks were established on volcanoes (for example) in Japan, the Philippines, Russia, and Hawai‘i by the 1950s, and in Alaska by the 1970s. Large eruptions with societal consequences generally catalyzed the implementation of new seismic instrumentation and led to operationalization of research methodologies. Seismic data now form the backbone of most local ground-based volcano monitoring networks worldwide and play a critical role in understanding how volcanoes work. The computer revolution enabled increasingly sophisticated data processing and source modeling, and facilitated the transition to continuous digital waveform recording by about the 1990s. In the 1970s and 1980s, quantitative models emerged for long-period (LP) event and tremor sources in fluid-driven cracks and conduits. Beginning in the 1970s, early models for volcano-tectonic (VT) earthquake swarms invoking crack tip stresses expanded to involve stress transfer into the wall rocks of pressurized dikes. The first deployments of broadband seismic instrumentation and infrasound sensors on volcanoes in the 1990s led to discoveries of new signals and phenomena. Rapid advances in infrasound technology; signal processing, analysis, and inversion; and atmospheric propagation modeling have now established the role of regional (15–250 km) and remote (> 250 km) ground-based acoustic systems in volcano monitoring. Long-term records of volcano-seismic unrest through full eruptive cycles are providing insight into magma transport and eruption processes and increasingly sophisticated forecasts. Laboratory and numerical experiments are elucidating seismo-acoustic source processes in volcanic fluid systems, and are observationally constrained by increasingly dense geophysical field deployments taking advantage of low-power, compact broadband, and nodal technologies. In recent years, the fields of volcano geodesy, seismology, and acoustics (both atmospheric infrasound and ocean hydroacoustics) are increasingly merging. Despite vast progress over the past century, major questions remain regarding source processes, patterns of volcano-seismic unrest, internal volcanic structure, and the relationship between seismic unrest and volcanic processes.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Exploring ecosystem‐based management in the North Atlantic - Mark Dickey‐Collas; Jason S. Link; Paul Snelgrove; J. Murray Roberts; M. Robin Anderson; Ellen Kenchington; Alida Bundy; Margaret M. (Peg) Brady; Rebecca L. Shuford; Howard Townsend; Anna Rindorf; Murray A. Rudd; et al. (Journal of Fish Biology, 2022)
The United States, the EU and Canada established a trilateral working group on the ecosystem approach to ocean health and stressors under the Atlantic Ocean Research Alliance. Recognizing the Atlantic Ocean as a shared resource and responsibility, the working group sought to advance understanding of the Atlantic Ocean and its dynamic systems to improve ocean health, enhance ocean stewardship and promote the sustainable use and management of its resources. This included consideration of multiple ocean‐use sectors such as fishing, shipping, tourism and offshore energy. The working group met for 4 years and worked through eight steps that covered the development of common language as a basis for collaboration, challenges of stakeholder engagement, review of the governance mandates, exploring the links between sectors and ecosystems effects, identifying gaps in knowledge and uptake of science, identification of tools for ecosystem‐based management, customary best practice for tool development and communication of key research priorities. The key findings were that ecosystem‐based management enables new benefits and opportunities, and that we need to make the business case. Further findings were that adequate mandates and effective tools exist for ecosystem‐based management, and that ecosystem‐based management urgently requires integration of human dimensions, so we must diversify the conversation. In addition, it was found that stakeholders do not see their stake in ecosystem‐based management, so greater engagement with stakeholders and targeting of ocean literacy is required and a sustainable future requires a sustained investment in ecosystem‐based management, so long‐term commitment is key.

Two hundred and five newly assembled mitogenomes provide mixed evidence for rivers as drivers of speciation for Amazonian primates - Mareike C. Janiak; Felipe E. Silva; Robin M. D. Beck; Dorien de Vries; Lukas F. K. Kuderna; Nicole S. Torosin; Amanda D. Melin; Tomàs Marquès‐Bonet; Ian B. Goodhead; Mariluce Messias; Maria N. F. da Silva; Iracilda Sampaio; et al. (Molecular Ecology, 2022)
Mitochondrial DNA remains a cornerstone for molecular ecology, especially for study species from which high‐quality tissue samples cannot be easily obtained. Methods using mitochondrial markers are usually reliant on reference databases, but these are often incomplete. Furthermore, available mitochondrial genomes often lack crucial metadata, such as sampling location, limiting their utility for many analyses. Here, we assembled 205 new mitochondrial genomes for platyrrhine primates, most from the Amazon and with known sampling locations. We present a dated mitogenomic phylogeny based on these samples along with additional published platyrrhine mitogenomes, and use this to assess support for the long‐standing riverine barrier hypothesis (RBH), which proposes that river formation was a major driver of speciation in Amazonian primates. Along the Amazon, Negro, and Madeira rivers, we found mixed support for the RBH. While we identified divergences that coincide with a river barrier, only some occur synchronously and also overlap with the proposed dates of river formation. The most compelling evidence is for the Amazon river potentially driving speciation within bearded saki monkeys ( Chiropotes spp.) and within the smallest extant platyrrhines, the marmosets and tamarins. However, we also found that even large rivers do not appear to be barriers for some primates, including howler monkeys ( Alouatta spp.), uakaris ( Cacajao spp.), sakis ( Pithecia spp.), and robust capuchins ( Sapajus spp.). Our results support a more nuanced, clade‐specific effect of riverine barriers and suggest that other evolutionary mechanisms, besides the RBH and allopatric speciation, may have played an important role in the diversification of platyrrhines.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Climate variability and aridity modulate the role of leaf shelters for arthropods: A global experiment - Gustavo Q. Romero; Thiago Gonçalves‐Souza; Tomas Roslin; Robert J. Marquis; Nicholas A.C. Marino; Vojtech Novotny; Tatiana Cornelissen; Jerome Orivel; Shen Sui; Gustavo Aires; Reuber Antoniazzi; Wesley Dáttilo; et al. (Global Change Biology, 2022)
Current climate change is disrupting biotic interactions and eroding biodiversity worldwide. However, species sensitive to aridity, high temperatures, and climate variability might find shelter in microclimatic refuges, such as leaf rolls built by arthropods. To explore how the importance of leaf shelters for terrestrial arthropods changes with latitude, elevation, and climate, we conducted a distributed experiment comparing arthropods in leaf rolls versus control leaves across 52 sites along an 11,790 km latitudinal gradient. We then probed the impact of short‐ versus long‐term climatic impacts on roll use, by comparing the relative impact of conditions during the experiment versus average, baseline conditions at the site. Leaf shelters supported larger organisms and higher arthropod biomass and species diversity than non‐rolled control leaves. However, the magnitude of the leaf rolls’ effect differed between long‐ and short‐term climate conditions, metrics (species richness, biomass, and body size), and trophic groups (predators vs. herbivores). The effect of leaf rolls on predator richness was influenced only by baseline climate, increasing in magnitude in regions experiencing increased long‐term aridity, regardless of latitude, elevation, and weather during the experiment. This suggests that shelter use by predators may be innate, and thus, driven by natural selection. In contrast, the effect of leaf rolls on predator biomass and predator body size decreased with increasing temperature, and increased with increasing precipitation, respectively, during the experiment. The magnitude of shelter usage by herbivores increased with the abundance of predators and decreased with increasing temperature during the experiment. Taken together, these results highlight that leaf roll use may have both proximal and ultimate causes. Projected increases in climate variability and aridity are, therefore, likely to increase the importance of biotic refugia in mitigating the effects of climate change on species persistence.

Predicting landscape‐scale biodiversity recovery by natural tropical forest regrowth - Pablo V. Prieto; Jacob J. Bukoski; Felipe S. M. Barros; Hawthorne L. Beyer; Alvaro Iribarrem; Pedro H. S. Brancalion; Robin L. Chazdon; David B. Lindenmayer; Bernardo B. N. Strassburg; Manuel R. Guariguata; Renato Crouzeilles (Conservation Biology, 2022)
Natural forest regrowth is a cost‐effective, nature‐based solution for biodiversity recovery, yet different socioenvironmental factors can lead to variable outcomes. A critical knowledge gap in forest restoration planning is how to predict where natural forest regrowth is likely to lead to high levels of biodiversity recovery, which is an indicator of conservation value and the potential provisioning of diverse ecosystem services. We sought to predict and map landscape‐scale recovery of species richness and total abundance of vertebrates, invertebrates, and plants in tropical and subtropical second‐growth forests to inform spatial restoration planning. First, we conducted a global meta‐analysis to quantify the extent to which recovery of species richness and total abundance in second‐growth forests deviated from biodiversity values in reference old‐growth forests in the same landscape. Second, we employed a machine‐learning algorithm and a comprehensive set of socioenvironmental factors to spatially predict landscape‐scale deviation and map it. Models explained on average 34% of observed variance in recovery (range 9–51%). Landscape‐scale biodiversity recovery in second‐growth forests was spatially predicted based on socioenvironmental landscape factors (human demography, land use and cover, anthropogenic and natural disturbance, ecosystem productivity, and topography and soil chemistry); was significantly higher for species richness than for total abundance for vertebrates (median range‐adjusted predicted deviation 0.09 vs. 0.34) and invertebrates (0.2 vs. 0.35) but not for plants (which showed a similar recovery for both metrics [0.24 vs. 0.25]); and was positively correlated for total abundance of plant and vertebrate species (Pearson r = 0.45, p = 0.001). Our approach can help identify tropical and subtropical forest landscapes with high potential for biodiversity recovery through natural forest regrowth.

Volcano infrasound: progress and future directions - Leighton M. Watson; Alexandra M. Iezzi; Liam Toney; Sean P. Maher; David Fee; Kathleen McKee; Hugo D. Ortiz; Robin S. Matoza; Julia E. Gestrich; Jordan W. Bishop; Alex J. C. Witsil; Jacob F. Anderson; et al. (Bulletin of Volcanology, 2022)
Over the past two decades (2000–2020), volcano infrasound (acoustic waves with frequencies less than 20 Hz propagating in the atmosphere) has evolved from an area of academic research to a useful monitoring tool. As a result, infrasound is routinely used by volcano observatories around the world to detect, locate, and characterize volcanic activity. It is particularly useful in confirming subaerial activity and monitoring remote eruptions, and it has shown promise in forecasting paroxysmal activity at open-vent systems. Fundamental research on volcano infrasound is providing substantial new insights on eruption dynamics and volcanic processes and will continue to do so over the next decade. The increased availability of infrasound sensors will expand observations of varied eruption styles, and the associated increase in data volume will make machine learning workflows more feasible. More sophisticated modeling will be applied to examine infrasound source and propagation effects from local to global distances, leading to improved infrasound-derived estimates of eruption properties. Future work will use infrasound to detect, locate, and characterize moving flows, such as pyroclastic density currents, lahars, rockfalls, lava flows, and avalanches. Infrasound observations will be further integrated with other data streams, such as seismic, ground- and satellite-based thermal and visual imagery, geodetic, lightning, and gas data. The volcano infrasound community should continue efforts to make data and codes accessible and to improve diversity, equity, and inclusion in the field. In summary, the next decade of volcano infrasound research will continue to advance our understanding of complex volcano processes through increased data availability, sensor technologies, enhanced modeling capabilities, and novel data analysis methods that will improve hazard detection and mitigation.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

The natural history of OTOF-related auditory neuropathy spectrum disorders: a multicenter study - Ryan K. Thorpe; Hela Azaiez; Peina Wu; Qiuju Wang; Lei Xu; Pu Dai; Tao Yang; G. Bradley Schaefer; B. Robert Peters; Kenny H. Chan; Krista S. Schatz; Joann Bodurtha; et al. (Human Genetics, 2022)

Evidence for near-source nonlinear propagation of volcano infrasound from Strombolian explosions at Yasur Volcano, Vanuatu - Sean P. Maher; Robin S. Matoza; Arthur Jolly; Catherine de Groot-Hedlin; Kent L. Gee; David Fee; Alexandra M. Iezzi (Bulletin of Volcanology, 2022)
Volcanic eruption source parameters may be estimated from acoustic pressure recordings dominant at infrasonic frequencies (< 20 Hz), yet uncertainties may be high due in part to poorly understood propagation dynamics. Linear acoustic propagation of volcano infrasound is commonly assumed, but nonlinear processes such as wave steepening may distort waveforms and obscure the sourcing process in recorded waveforms. Here we use a previously developed frequency-domain nonlinearity indicator to quantify spectral changes due to nonlinear propagation primarily in 80 signals from explosions at Yasur Volcano, Vanuatu. We find evidence for $$\le$$ ≤ 10 −3 dB/m spectral energy transfer in the band 3–9 Hz for signals with amplitude on the order of several hundred Pa at 200–400 m range. The clarity of the nonlinear spectral signature increases with waveform amplitude, suggesting stronger nonlinear changes for greater source pressures. We observe similar results in application to synthetics generated through finite-difference wavefield simulations of nonlinear propagation, although limitations of the model complicate direct comparison to the observations. Our results provide quantitative evidence for nonlinear propagation that confirms previous interpretations made on the basis of qualitative observations of asymmetric waveforms.

Subtle structures with not‐so‐subtle functions: A data set of arthropod constructs and their host plants - Cássio Cardoso Pereira; Samuel Novais; Milton Barbosa; Daniel Negreiros; Thiago Gonçalves‐Souza; Tomas Roslin; Robert Marquis; Nicholas Marino; Vojtech Novotny; Jerome Orivel; Shen Sui; Gustavo Aires; et al. (Ecology, 2022)
The construction of shelters on plants by arthropods might influence other organisms via changes in colonization, community richness, species composition, and functionality. Arthropods, including beetles, caterpillars, sawflies, spiders, and wasps often interact with host plants via the construction of shelters, building a variety of structures such as leaf ties, tents, rolls, and bags; leaf and stem galls, and hollowed out stems. Such constructs might have both an adaptive value in terms of protection (i.e., serve as shelters) but may also exert a strong influence on terrestrial community diversity in the engineered and neighboring hosts via colonization by secondary occupants. Although different traits of the host plant (e.g., physical, chemical, and architectural features) may affect the potential for ecosystem engineering by insects, such effects have been, to a certain degree, overlooked. Further analyses of how plant traits affect the occurrence of shelters may therefore enrich our understanding of the organizing principles of plant‐based communities. This data set includes more than 1000 unique records of ecosystem engineering by arthropods, in the form of structures built on plants. All records have been published in the literature, and span both natural structures (91% of the records) and structures artificially created by researchers (9% of the records). The data were gathered between 1932 and 2021, across more than 50 countries and several ecosystems, ranging from polar to tropical zones. In addition to data on host plants and engineers, we aggregated data on the type of constructs and the identity of inquilines using these structures. This data set highlights the importance of these subtle structures for the organization of terrestrial arthropod communities, enabling hypotheses testing in ecological studies addressing ecosystem engineering and facilitation mediated by constructs. There are no copyright restrictions and please cite this paper when using the data in publications.

Compensatory responses to increased mechanical abnormalities in COPD during sleep - Nicolle J. Domnik; Devin B. Phillips; Matthew D. James; Grace A. Ayoo; Sarah M. Taylor; Robin E. Scheeren; Amanda T. Di Luch; Kathryn M. Milne; Sandra G. Vincent; Amany F. Elbehairy; Sophie J. Crinion; Helen S. Driver; et al. (European Journal of Applied Physiology, 2022)

Trends in volcano seismology: 2010 to 2020 and beyond - Weston A. Thelen; Robin S. Matoza; Alicia J. Hotovec-Ellis (Bulletin of Volcanology, 2022)

Close‐kin methods to estimate census size and effective population size - Robin S. Waples; Pierre Feutry (Fish and Fisheries, 2022)
The last two decades have witnessed rapid developments and increasing interest in use of: (1) genetic methods to estimate effective population size ( N e ) and (2) close‐kin mark–recapture (CKMR) methods to estimate abundance based on the incidence of close relatives. Whereas N e estimation methods have been applied to a wide range of taxa, all CKMR applications to date have been for aquatic species. These two fields of inquiry have developed largely independently, and this is unfortunate because deeper insights can be gained by joint evaluation of eco‐evolutionary processes. In this synthesis, we use simple analytical models and simulated pedigree data to illustrate how various factors (life‐history traits; patterns of variation in individual reproductive success; experimental design; stochasticity; marker type) can affect the performance of the estimators. We show that the N e / N ratio and the probability of a close‐kin match both depend on a vector of parental weights that specify relative probabilities that different individuals will produce offspring. Although age‐specific vital rates are central to both methodologies, for CKMR they can potentially bias abundance estimates unless properly accounted for, whereas they represent the signals of genetic drift that N e estimation methods depend upon. Coordinating N e and CKMR estimation methods using the same or overlapping datasets would facilitate joint evaluation of both the ecological and evolutionary consequences of abundance.

Systematic assessment of acquisition and data-processing parameters in the suspect screening of veterinary drugs in archive matrices using LC-HRMS - Larissa J. M. Jansen; Rosalie Nijssen; Yvette J. C. Bolck; Robin S. Wegh; Milou G. M. van de Schans; Bjorn J. A. Berendsen (Food Additives & Contaminants: Part A, 2022)

From anecdotes to quantification: advances in characterizing volcanic eruption impacts on the built environment - Natalia Irma Deligne; Susanna F. Jenkins; Elinor S. Meredith; George T. Williams; Graham S. Leonard; Carol Stewart; Thomas M. Wilson; Sébastien Biass; Daniel M. Blake; Russell J. Blong; Costanza Bonadonna; Rodrigo Calderon B.; et al. (Bulletin of Volcanology, 2022)

Establishment of a microsatellite genetic baseline for North American Atlantic sturgeon (Acipenser o. oxyrhinchus) and range-wide analysis of population genetics - Shannon L. White; David C. Kazyak; Tanya L. Darden; Daniel J. Farrae; Barbara A. Lubinski; Robin L. Johnson; Michael S. Eackles; Matthew T. Balazik; Harold M. Brundage; Adam G. Fox; Dewayne A. Fox; Christian H. Hager; et al. (Conservation Genetics, 2021)

Global DNA (LINE-1) methylation is associated with lead exposure and certain job tasks performed by electronic waste workers - Ibrahim Issah; John Arko-Mensah; Laura S. Rozek; Katie R. Zarins; Thomas P. Agyekum; Duah Dwomoh; Niladri Basu; Stuart Batterman; Thomas G. Robins; Julius N. Fobil (International Archives of Occupational and Environmental Health, 2021)

Global high-throughput genotyping of organellar genomes reveals insights into the origin and spread of invasive starry stonewort (Nitellopsis obtusa) - Robin S. Sleith; Kenneth G. Karol (Biological Invasions, 2021)
Aquatic invasive species are damaging to native ecosystems. Preventing their spread and achieving comprehensive control measures requires an understanding of the genetic structure of an invasive population. Organellar genomes (plastid and mitochondrial) are useful for population level analyses of invasive plant distributions. In this study we generate complete organellar reference genomes using PacBio sequencing, then use these reference sequences for SNP calling of high-throughput, multiplexed, Illumina based organellar sequencing of fresh and historical samples from across the native and invasive range of Nitellopsis obtusa (Desv. in Loisel.) J.Groves, an invasive macroalgae. The data generated by the analytical pipeline we develop indicate introduction to North America from Western Europe. A single nucleotide transversion in the plastid genome separates a group of five samples from Michigan and Wisconsin that either resulted from introductions of two closely related genotypes or a mutation that has arisen in the invasive range. This transversion will serve as a useful tool to understand how Nitellopsis obtusa moves across the landscape. The methods and analyses described here are broadly applicable to invasive and native plant and algae species, and allow efficient genotyping of variable quality samples, including 100-year-old herbarium specimens, to determine population structure and geographic distributions.

Anticipating and Adapting to the Future Impacts of Climate Change on the Health, Security and Welfare of Low Elevation Coastal Zone (LECZ) Communities in Southeastern USA - Thomas Allen; Joshua Behr; Anamaria Bukvic; Ryan S. D. Calder; Kiki Caruson; Charles Connor; Christopher D’Elia; David Dismukes; Robin Ersing; Rima Franklin; Jesse Goldstein; Jonathon Goodall; et al. (Journal of Marine Science and Engineering, 2021)
Low elevation coastal zones (LECZ) are extensive throughout the southeastern United States. LECZ communities are threatened by inundation from sea level rise, storm surge, wetland degradation, land subsidence, and hydrological flooding. Communication among scientists, stakeholders, policy makers and minority and poor residents must improve. We must predict processes spanning the ecological, physical, social, and health sciences. Communities need to address linkages of (1) human and socioeconomic vulnerabilities; (2) public health and safety; (3) economic concerns; (4) land loss; (5) wetland threats; and (6) coastal inundation. Essential capabilities must include a network to assemble and distribute data and model code to assess risk and its causes, support adaptive management, and improve the resiliency of communities. Better communication of information and understanding among residents and officials is essential. Here we review recent background literature on these matters and offer recommendations for integrating natural and social sciences. We advocate for a cyber-network of scientists, modelers, engineers, educators, and stakeholders from academia, federal state and local agencies, non-governmental organizations, residents, and the private sector. Our vision is to enhance future resilience of LECZ communities by offering approaches to mitigate hazards to human health, safety and welfare and reduce impacts to coastal residents and industries.

Mitigating potential public health problems associated with edible cannabis products through adequate regulation: A landscape analysis - Aurash J. Soroosh; Robin Henderson; Lori Dodson; Clifford S. Mitchell; Jed W. Fahey (Critical Reviews in Food Science and Nutrition, 2021)

Status of health and conservation classification of tropical coral reefs in Lakshadweep archipelago - M. Gopi; J. Joyson Joe Jeevamani; S. Goutham; Nina Tabitha Simon; V. Deepak Samuel; K. R. Abhilash; R. S. Robin; G. Hariharan; R. Muruganandam; P. Krishnan; R. Purvaja; R. Ramesh (Wetlands Ecology and Management, 2021)

Spatial–Temporal Growth, Distribution, and Diffusion of Marine Microplastic Research and National Plastic Policies - Lyda S. T. Harris; Jackson Fennell; Robin J. Fales; Emily Carrington (Water, Air, & Soil Pollution, 2021)

Numerical modelling approach for the feasibility of shore protection measures along the coast of Kavaratti Island, Lakshadweep archipelago - T Pearlin Sam Jinoj; Subbareddy Bonthu; R S Robin; K K Idrees Babu; K Arumugam; R Purvaja; R Ramesh (Journal of Earth System Science, 2021)

Seismo-acoustic characterisation of the 2018 Ambae (Manaro Voui) eruption, Vanuatu - Iseul Park; Arthur Jolly; Robin S. Matoza; Ben Kennedy; Geoff Kilgour; Richard Johnson; Esline Garaebiti; Sandrine Cevuard (Bulletin of Volcanology, 2021)
A new episode of unrest and phreatic/phreatomagmatic/magmatic eruptions occurred at Ambae volcano, Vanuatu, in 2017–2018. We installed a multi-station seismo-acoustic network consisting of seven 3-component broadband seismic stations and four 3-element (26–62 m maximum inter-element separation) infrasound arrays during the last phase of the 2018 eruption episode, capturing at least six reported major explosions towards the end of the eruption episode. The observed volcanic seismic signals are generally in the passband 0.5–10 Hz during the eruptive activity, but the corresponding acoustic signals have relatively low frequencies (< 1 Hz). Apparent very-long-period (< 0.2 Hz) seismic signals are also observed during the eruptive episode, but we show that they are generated as ground-coupled airwaves and propagate with atmospheric acoustic velocity. We observe strongly coherent infrasound waves at all acoustic arrays during the eruptions. Using waveform similarity of the acoustic signals, we detect previously unreported volcanic explosions at the summit vent region based on constant-celerity reverse-time-migration (RTM) analysis. The detected acoustic bursts are temporally related to shallow seismic volcanic tremor (frequency content of 5–10 Hz), which we characterise using a simplified amplitude ratio method at a seismic station pair with different distances from the vent. The amplitude ratio increased at the onset of large explosions and then decreased, which is interpreted as the seismic source ascent and descent. The ratio change is potentially useful to recognise volcanic unrest using only two seismic stations quickly. This study reiterates the value of joint seismo-acoustic data for improving interpretation of volcanic activity and reducing ambiguity in geophysical monitoring.

Remote hydroacoustic-infrasonic detection and characterization of Anak Krakatau eruptive activity leading to, during, and following the December 2018 flank collapse and tsunami - Kaelynn M. Rose; Robin S. Matoza (Bulletin of Volcanology, 2021)
A climactic eruption phase on December 22, 2018, triggered the collapse of the southwest flank and summit of Anak Krakatau stratovolcano, generating a tsunami which struck the coastlines of Sumatra and Java. We employ a selection of remote moored hydroacoustic (H08S, 3307 km; H01W, 3720 km) and infrasonic (IS06, 1156 km; IS07, 3475 km; IS52, 3638 km) stations of the International Monitoring System (IMS) to investigate eruptive activity preceding, during, and after the climactic eruption phase. We observe 6 months of co-eruptive intermittent infrasound at IS06 and powerful infrasound from the climactic eruption on IS06 and IS52. The climactic eruption phase was not detected hydroacoustically, but we observe a ~ 12-day swarm of hydroacoustic signals beginning 24 days before the flank collapse event that we attribute to sustained submarine eruptive activity at Anak Krakatau. We perform hydroacoustic waveform and envelope multiplet analysis to assess event similarity during the hydroacoustic swarm. Hydroacoustic waveforms are not well-correlated, but envelopes with a main pulse duration of ~ 20-s are correlated, with 88.7% of 247 events grouping into two multiplets using a threshold correlation coefficient of 0.75. The repetitive envelopes indicate a repetitive impulsive volcanic process, either underwater submarine explosions or volcanic earthquakes in the solid Earth coupled to the water column from the Sunda Shelf. This study further underscores the potential of remote acoustic technology for detecting and characterizing eruptions at submarine or partially submerged volcanoes.

Adult male Cuvier's beaked whales ( Ziphius cavirostris ) engage in prolonged bouts of synchronous diving - William R. Cioffi; Nicola J. Quick; Heather J. Foley; Danielle M. Waples; Zachary T. Swaim; Jeanne M. Shearer; Daniel L. Webster; Ari S. Friedlaender; Brandon L. Southall; Robin W. Baird; Douglas P. Nowacek; Andrew J. Read (Marine Mammal Science, 2021)
Studies of the social behavior of Cuvier's beaked whales ( Ziphius cavirostris ) are challenging because of their deep‐water habitat usually far from shore and the limited time they spend at the surface. The sociality of these deepest diving mammals is of interest, however, especially for our understanding of how social systems evolve in extreme habitats. High levels of scarring suggest that males compete agonistically for access to females and so we predicted that associations among adult males would be unstable due to competitive exclusion. We tested this prediction by evaluating the diving behavior of animals within social groups off Cape Hatteras, North Carolina, considering diving synchrony a proxy for group membership. Using data from satellite‐linked depth‐recording tags, we found that adult male–male pairs showed extended periods of synchrony in diving behavior, while all pairs that included an adult male with an individual of another age and/or sex dove synchronously for less than a day. We assessed three hypotheses to explain these surprising results: sexual segregation; extended bouts of male–male competition; and the presence of male alliances. Finally, we considered testable predictions to distinguish among these explanations.

Remote Predictions of Mahi-Mahi (Coryphaena hippurus) Spawning in the Open Ocean Using Summarized Accelerometry Data - Lela S. Schlenker; Robin Faillettaz; John D. Stieglitz; Chi Hin Lam; Ronald H. Hoenig; Georgina K. Cox; Rachael M. Heuer; Christina Pasparakis; Daniel D. Benetti; Claire B. Paris; Martin Grosell (Frontiers in Marine Science, 2021)
Identifying complex behaviors such as spawning and fine-scale activity is extremely challenging in highly migratory fish species and is becoming increasingly critical knowledge for fisheries management in a warming ocean. Habitat use and migratory pathways have been extensively studied in marine animals using pop-up satellite archival tags (PSATs), but high-frequency data collected on the reproductive and swimming behaviors of marine fishes has been limited by the inability to remotely transmit these large datasets. Here, we present the first application of remotely transmitted acceleration data to predict spawning and discover drivers of high activity in a wild and highly migratory pelagic fish, the mahi-mahi ( Coryphaena hippurus ). Spawning events were predicted to occur at nighttime, at a depth distinct from non-spawning periods, primarily between 27.5 and 30°C, and chiefly at the new moon phase in the lunar cycle. Moreover, throughout their large-scale migrations, mahi-mahi exhibited behavioral thermoregulation to remain largely between 27 and 28°C and reduced their relative activity at higher temperatures. These results show that unveiling fine-scale activity patterns are necessary to grasp the ecology of highly mobile species. Further, our study demonstrates that critical, and new, ecological information can be extracted from PSATs, greatly expanding their potential to study the reproductive behavior and population connectivity in highly migratory fishes.

Combined visual and biochemical analyses confirm depositor and diet for Neolithic coprolites from Skara Brae - Andrzej A. Romaniuk; Elsa Panciroli; Michael Buckley; Manasij Pal Chowdhury; Carla Willars; Jeremy S. Herman; Lore G. Troalen; Alexandra N. Shepherd; David V. Clarke; Alison Sheridan; Bart E. van Dongen; Ian B. Butler; et al. (Archaeological and Anthropological Sciences, 2020)
Coprolites (fossilized faeces) can provide valuable insights into species’ diet and related habits. In archaeozoological contexts, they are a potential source of information on human-animal interactions as well as human and animal subsistence. However, despite a broad discussion on coprolites in archaeology, such finds are rarely subject to detailed examination by researchers, perhaps due to the destructive nature of traditional analytical methods. Here, we have examined coprolitic remains from the Neolithic (third millennium BCE) settlement at Skara Brae, Orkney, using a range of modern methods: X-ray computed tomography, scanning electron microscopy, lipid and protein analysis (shotgun proteomics of the coprolite matrix as well as collagen peptide mass fingerprinting of isolated bone fragments). This combined approach minimised destructiveness of sampling, leaving sufficient material for subsequent study, while providing more information than traditional morphological examination alone. Based on gross visual examination, coprolites were predominantly attributed to domestic dogs ( Canis familiaris ), with morphologically identified bone inclusions derived from domestic sheep ( Ovis aries ) and common voles ( Microtus arvalis ). Partial dissection of a coprolite provided bone samples containing protein markers akin to those of domestic sheep. Considering the predominance of vertebral and distal limb bone fragments, Skara Brae dogs were probably consuming human butchery or meal refuse, either routinely fed to them or scavenged. The presumably opportunistic consumption of rodents may also have played a role in pest control.

Degradable hyaluronic acid/chitosan polyelectrolyte multilayers with marine fouling-release properties - Wenfa Yu; Robin Wanka; John A. Finlay; Jessica L. Clarke; Anthony S. Clare; Axel Rosenhahn (Biofouling, 2020)

A Synthesis of Marine Monitoring Methods With the Potential to Enhance the Status Assessment of the Baltic Sea - Leoni Mack; Jenni Attila; Eva Aylagas; Arne Beermann; Angel Borja; Daniel Hering; Maria Kahlert; Florian Leese; Robin Lenz; Maiju Lehtiniemi; Antonia Liess; Urmas Lips; et al. (Frontiers in Marine Science, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

A rapid and sensitive method to detect SARS-CoV-2 virus using targeted-mass spectrometry - Praveen Singh; Rahul Chakraborty; Robin Marwal; V. S. Radhakrishan; Akash Kumar Bhaskar; Himanshu Vashisht; Mahesh S. Dhar; Shalini Pradhan; Gyan Ranjan; Mohamed Imran; Anurag Raj; Uma Sharma; et al. (Journal of Proteins and Proteomics, 2020)

Effects of crosslink density in zwitterionic hydrogel coatings on their antifouling performance and susceptibility to silt uptake - Julian Koc; Eric Schönemann; Robin Wanka; Nick Aldred; Anthony S. Clare; Harrison Gardner; Geoffrey W. Swain; Kelli Hunsucker; Andre Laschewsky; Axel Rosenhahn (Biofouling, 2020)

Leaf stripping: an alternative strategy to manage banded leaf and sheath blight of maize - Harleen Kaur; Sanjay Kumar; K. S. Hooda; Robin Gogoi; Pravin Bagaria; R. P. Singh; Rakesh Mehra; Ashwani Kumar (Indian Phytopathology, 2020)

Identification and Analysis of Nitrogen Dioxide Concentration for Air Quality Prediction Using Seasonal Autoregression Integrated with Moving Average - S. R. Mani Sekhar; G. M. Siddesh; Anjaneya Tiwari; Anay Khator; Robin Singh (Aerosol Science and Engineering, 2020)

Plant community composition steers grassland vegetation via soil legacy effects - Robin Heinen; S. Emilia Hannula; Jonathan R. De Long; Martine Huberty; Renske Jongen; Anna Kielak; Katja Steinauer; Feng Zhu; T. Martijn Bezemer (Ecology Letters, 2020)
Soil legacy effects are commonly highlighted as drivers of plant community dynamics and species co‐existence. However, experimental evidence for soil legacy effects of conditioning plant communities on responding plant communities under natural conditions is lacking. We conditioned 192 grassland plots using six different plant communities with different ratios of grasses and forbs and for different durations. Soil microbial legacies were evident for soil fungi, but not for soil bacteria, while soil abiotic parameters did not significantly change in response to conditioning. The soil legacies affected the composition of the succeeding vegetation. Plant communities with different ratios of grasses and forbs left soil legacies that negatively affected succeeding plants of the same functional type. We conclude that fungal‐mediated soil legacy effects play a significant role in vegetation assembly of natural plant communities.

Co-eruptive tremor from Bogoslof volcano: seismic wavefield composition at regional distances - Matthew M. Haney; David Fee; Kathleen F. McKee; John J. Lyons; Robin S. Matoza; Aaron G. Wech; Gabrielle Tepp; Cheryl Searcy; T. Dylan Mikesell (Bulletin of Volcanology, 2020)

Age, geological setting, and paragenesis of heavy rare earth element mineralization of the Tanami region, Western Australia - Teimoor Nazari-Dehkordi; Carl Spandler; Nicholas H. S. Oliver; Robin Wilson (Mineralium Deposita, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Observable, low-order dynamical controls on thresholds of the Atlantic meridional overturning circulation - Richard A. Wood; José M. Rodríguez; Robin S. Smith; Laura C. Jackson; Ed Hawkins (Climate Dynamics, 2019)

Economics of public health programs for underserved populations: a review of economic analysis of the National Breast and Cervical Cancer Early Detection Program - Jaya S. Khushalani; Justin G. Trogdon; Donatus U. Ekwueme; K. Robin Yabroff (Cancer Causes & Control, 2019)

Prevalence and Genetic Diversity of Toxoplasma gondii in Free-Ranging Chickens from the Caribbean - C. M. Hamilton; R. Robins; R. Thomas; C. Oura; S. Oliveira; I. Villena; E. A. Innes; F. Katzer; P. J. Kelly (Acta Parasitologica, 2019)

Vortioxetine reverses medial prefrontal cortex-mediated cognitive deficits in male rats induced by castration as a model of androgen deprivation therapy for prostate cancer - Alexandra M. Sharp; Suphada Lertphinyowong; Samantha S. Yee; Denisse Paredes; Jonathan Gelfond; Teresa L. Johnson-Pais; Robin J. Leach; Michael Liss; April L. Risinger; Anna C. Sullivan; Ian M. Thompson; David A. Morilak (Psychopharmacology, 2019)

Determination of antimony and barium in UK air quality samples as indicators of non-exhaust traffic emissions - S. L. Goddard; K. R. Williams; C. Robins; R. J. C. Brown (Environmental Monitoring and Assessment, 2019)

Hyperspectral VNIR-spectroscopy and imagery as a tool for monitoring herbicide damage in wilding conifers - Rebecca C. Scholten; Joachim Hill; Willy Werner; Henning Buddenbaum; Jonathan P. Dash; Mireia Gomez Gallego; Carol A. Rolando; Grant D. Pearse; Robin Hartley; Honey Jane Estarija; Michael S. Watt (Biological Invasions, 2019)

Ubiquity or not ubiquity: That is the question - Robin S. Sleith; Laura A. Katz (Molecular Ecology, 2019)
The nature of population structure in eukaryotic microbes has been the subject of intense debate, but until recently the tools to test these hypotheses were either problematic (e.g., allozymes that cannot detect all genetic changes) or beyond financial and technological limits of most laboratories (e.g., high throughput sequencing). In a recent issue of Molecular Ecology , Craig et al. (2019) use a genomic approach to investigate the population structure of a model alga, the chlorophyte Chlamydomonas reinhardtii (Figure 1). Using high throughput sequencing, read mapping, and variant calling, they detected strong signals of differentiation at a continental scale, while local patterns of admixture were complex. Population genomic techniques such as these have not been used extensively in studies of microbial eukaryotes and the fields of conservation genetics and evolution stand to benefit vastly from the adoption of these techniques to studies of diverse protist lineages.

Persistence of antibody response in chikungunya - Shweta Chelluboina; S. Robin; S. Aswathyraj; G. Arunkumar (VirusDisease, 2019)

More than a checkbox: engaging youth in disaster risk reduction and resilience in Canada - Robin S. Cox; Tiffany T. Hill; Tamara Plush; Cheryl Heykoop; Crystal Tremblay (Natural Hazards, 2019)

Continental drift, plateau uplift, and the evolutions of monsoon and arid regions in Asia, Africa, and Australia during the Cenozoic - Xiaodong Liu; Buwen Dong; Zhi-Yong Yin; Robin S. Smith; Qingchun Guo (Science China Earth Sciences, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Biogeographic context dependence of trophic cascade strength in bromeliad food webs - Robin M. LeCraw; Diane S. Srivastava (Ecology, 2019)
Ecosystem functions and the biomass of lower trophic levels are frequently controlled by predators. The strength of top‐down control in these trophic cascades can be affected by the identity and diversity of predators, prey, and resources, as well as environmental conditions such as temperature, moisture, and nutrient loading, which can all impact interaction strength between trophic levels. Few studies have been able to replicate a complete community over a large geographic area to compare the full trophic cascade in a manipulative experiment. Here, we identify geographic dependency in trophic cascade strength, and the driving factors and specific mechanisms behind it, by combining geographically replicated experiments with a novel approach of community analogues of common garden and transplant experiments. We studied a predator–detritivore–detritus food web in bromeliads in Puerto Rico, Costa Rica, and Brazil. We found that interaction strengths between resources, consumers, and predators were strongly site‐specific, but the exact mechanism differed between trophic levels. Large bodied predators created strong interaction strengths between predator and consumer trophic levels, reducing consumer abundance regardless of the geographic location, whereas small‐bodied predators created weak interactions with no impact on consumer abundances in any site. In contrast, the interaction strength between consumers and resources varied among sites, depending on the dominant species of leaf detritus. More labile leaf species in Costa Rica created a strong consumer–resource interaction and therefore strong trophic cascade, whereas tougher leaf species in Brazil created a weak consumer–resource interaction, and an overall weaker trophic cascade. Our study highlights the importance of replicating experiments over geographic scales to understand general patterns of ecological processes.

Molecular analysis and new records of the invasive polychaete Boccardia proboscidea (Annelida: Spionidae) - VASILY I. RADASHEVSKY; VICTORIA V. PANKOVA; VASILY V. MALYAR; TATYANA V. NERETINA; ROBIN S. WILSON; TIM M. WORSFOLD; MARÍA E. DIEZ; LESLIE H. HARRIS; STÉPHANE HOURDEZ; CÉLINE LABRUNE; CÉLINE HOUBIN; BRITTA KIND; et al. (Mediterranean Marine Science, 2019)
The spionid polychaete Boccardia proboscidea Hartman, 1940 is a tube-dweller and shell/stone-borer widely occurring in temperate waters across the world and considered invasive in many areas. It was originally described from California, USA, and later reported from Pacific Canada, the Asian Pacific, Australia, New Zealand, Argentina, South Africa, and northern Europe. The Bayesian inference analysis of sequence data of three gene fragments (836 bp in total) of the mitochondrial 16S rDNA, nuclear 28S rDNA, and Histone 3 has shown that individuals from the Pacific coasts of Canada and the USA, Argentina, Australia, South Africa, the United Kingdom, and Mediterranean France were genetically very similar (maximal average p-distance value, 0.49%, was between 16S rDNA sequences). We consider these individuals to be conspecific and report the earliest records of B. proboscidea from the UK and a possible first Mediterranean record in the Gulf of Lion. The high 16S haplotype diversity of B. proboscidea detected in the north-eastern Pacific suggests a native distribution for the species in the northern Pacific and subsequent introductions through human activities to other parts of the world. The histories of these introductions are reviewed and the hypotheses about times and places of introductions are updated.

Molecular analysis and new records of the invasive polychaete Boccardia proboscidea (Annelida: Spionidae) - VASILY I. RADASHEVSKY; VICTORIA V. PANKOVA; VASILY V. MALYAR; TATYANA V. NERETINA; ROBIN S. WILSON; TIM M. WORSFOLD; MARÍA E. DIEZ; LESLIE H. HARRIS; STÉPHANE HOURDEZ; CÉLINE LABRUNE; CÉLINE HOUBIN; BRITTA KIND; et al. (Mediterranean Marine Science, 2019)
The spionid polychaete Boccardia proboscidea Hartman, 1940 is a tube-dweller and shell/stone-borer widely occurring in temperate waters across the world and considered invasive in many areas. It was originally described from California, USA, and later reported from Pacific Canada, the Asian Pacific, Australia, New Zealand, Argentina, South Africa, and northern Europe. The Bayesian inference analysis of sequence data of three gene fragments (836 bp in total) of the mitochondrial 16S rDNA, nuclear 28S rDNA, and Histone 3 has shown that individuals from the Pacific coasts of Canada and the USA, Argentina, Australia, South Africa, the United Kingdom, and Mediterranean France were genetically very similar (maximal average p-distance value, 0.49%, was between 16S rDNA sequences). We consider these individuals to be conspecific and report the earliest records of B. proboscidea from the UK and a possible first Mediterranean record in the Gulf of Lion. The high 16S haplotype diversity of B. proboscidea detected in the north-eastern Pacific suggests a native distribution for the species in the northern Pacific and subsequent introductions through human activities to other parts of the world. The histories of these introductions are reviewed and the hypotheses about times and places of introductions are updated.

Phenotypic and physiological characterization of maize inbred lines resistant and susceptible to maydis leaf blight - C. Manjunatha; Robin Gogoi; Bhupinder Singh; B. Jeevan; S. N. Rai; Pradeep Kumar Singh (Indian Phytopathology, 2019)

The evolution of microendemism in a reef fish ( Hypoplectrus maya ) - Benjamin M. Moran; Kosmas Hench; Robin S. Waples; Marc P. Höppner; Carole C. Baldwin; William Owen McMillan; Oscar Puebla (Molecular Ecology, 2019)
Marine species tend to have extensive distributions, which are commonly attributed to the dispersal potential provided by planktonic larvae and the rarity of absolute barriers to dispersal in the ocean. Under this paradigm, the occurrence of marine microendemism without geographic isolation in species with planktonic larvae poses a dilemma. The recently described Maya hamlet ( Hypoplectrus maya , Serranidae) is exactly such a case, being endemic to a 50‐km segment of the Mesoamerican Barrier Reef System (MBRS). We use whole‐genome analysis to infer the demographic history of the Maya hamlet and contrast it with the sympatric and pan‐Caribbean black ( H. nigricans ), barred ( H. puella ) and butter ( H. unicolor ) hamlets, as well as the allopatric but phenotypically similar blue hamlet ( H. gemma ). We show that H. maya is indeed a distinct evolutionary lineage, with genomic signatures of inbreeding and a unique demographic history of continuous decrease in effective population size since it diverged from congeners just ~3,000 generations ago. We suggest that this case of microendemism may be driven by the combination of a narrow ecological niche and restrictive oceanographic conditions in the southern MBRS, which is consistent with the occurrence of an unusually high number of marine microendemics in this region. The restricted distribution of the Maya hamlet, its decline in both census and effective population sizes, and the degradation of its habitat place it at risk of extinction. We conclude that the evolution of marine microendemism can be a fast and dynamic process, with extinction possibly occurring before speciation is complete.

A gene for resistance to the Varroa mite (Acari) in honey bee ( Apis mellifera ) pupae - Benjamin H. Conlon; Adriana Aurori; Alexandru‐Ioan Giurgiu; John Kefuss; Daniel S. Dezmirean; Robin F. A. Moritz; Jarkko Routtu (Molecular Ecology, 2019)
Social insect colonies possess a range of defences which protect them against highly virulent parasites and colony collapse. The host–parasite interaction between honey bees ( Apis mellifera ) and the mite Varroa destructor is unusual, as honey bee colonies are relatively poorly defended against this parasite. The interaction has existed since the mid‐20th Century, when Varroa switched host to parasitize A. mellifera . The combination of a virulent parasite and relatively naïve host means that, without acaricides, honey bee colonies typically die within 3 years of Varroa infestation. A consequence of acaricide use has been a reduced selective pressure for the evolution of Varroa resistance in honey bee colonies. However, in the past 20 years, several natural‐selection‐based breeding programmes have resulted in the evolution of Varroa ‐resistant populations. In these populations, the inhibition of Varroa' s reproduction is a common trait. Using a high‐density genome‐wide association analysis in a Varroa ‐resistant honey bee population, we identify an ecdysone ‐induced gene significantly linked to resistance. Ecdysone both initiates metamorphosis in insects and reproduction in Varroa . Previously, using a less dense genetic map and a quantitative trait loci analysis, we have identified Ecdysone ‐related genes at resistance loci in an independently evolved resistant population. Varroa cannot biosynthesize ecdysone but can acquire it from its diet. Using qPCR, we are able to link the expression of ecdysone ‐linked resistance genes to Varroa 's meals and reproduction. If Varroa co‐opts pupal compounds to initiate and time its own reproduction, mutations in the host's ecdysone pathway may represent a key selection tool for honey bee resistance and breeding.

Identification and characterization of a novel anti-inflammatory lipid isolated from Mycobacterium vaccae, a soil-derived bacterium with immunoregulatory and stress resilience properties - David G. Smith; Roberta Martinelli; Gurdyal S. Besra; Petr A. Illarionov; Istvan Szatmari; Peter Brazda; Mary A. Allen; Wenqing Xu; Xiang Wang; László Nagy; Robin D. Dowell; Graham A. W. Rook; et al. (Psychopharmacology, 2019)

Late Quaternary sea‐level change and evolution of Belfast Lough, Northern Ireland: new offshore evidence and implications for sea‐level reconstruction - Ruth M. K. Plets; S. Louise Callard; J. Andrew G. Cooper; Joseph T. Kelley; Daniel F. Belknap; Robin J. Edwards; Antony J. Long; Rory J. Quinn; Derek W. T. Jackson (Journal of Quaternary Science, 2019)
The interplay of eustatic and isostatic factors causes complex relative sea‐level (RSL) histories, particularly in paraglacial settings. In this context the past record of RSL is important in understanding ice‐sheet history, earth rheology and resulting glacio‐isostatic adjustment. Field data to develop sea‐level reconstructions are often limited to shallow depths and uncertainty exists as to the veracity of modelled sea‐level curves. We use seismic stratigraphy, 39 vibrocores and 26 radiocarbon dates to investigate the deglacial history of Belfast Lough, Northern Ireland, and reconstruct past RSL. A typical sequence of till, glacimarine and Holocene sediments is preserved. Two sea‐level lowstands (both max. −40 m) are recorded at c. 13.5 and 11.5k cal a bp . Each is followed by a rapid transgression and subsequent periods of RSL stability. The first transgression coincides temporally with a late stage of Meltwater Pulse 1a and the RSL stability occurred between c. 13.0 and c. 12.2k cal a bp (Younger Dryas). The second still/slowstand occurred between c. 10.3 and c. 11.5k cal a bp . Our data provide constraints on the direction and timing of RSL change during deglaciation. Application of the Depth of Closure concept adds an error term to sea‐level reconstructions based on seismic stratigraphic reconstructions.

Toreforant, an orally active histamine H4-receptor antagonist, in patients with active rheumatoid arthritis despite methotrexate: mechanism of action results from a phase 2, multicenter, randomized, double-blind, placebo-controlled synovial biopsy study - David L. Boyle; Samuel E. DePrimo; Cesar Calderon; Dion Chen; Paul J. Dunford; William Barchuk; Gary S. Firestein; Robin L. Thurmond (Inflammation Research, 2019)

Assessment of resistance to rice tungro disease in popular rice varieties in India by introgression of a transgene against Rice tungro bacilliform virus - G. Kumar; M. Jyothsna; P. Valarmathi; S. Roy; A. Banerjee; J. Tarafdar; B. K. Senapati; S. Robin; S. Manonmani; R. Rabindran; I. Dasgupta (Archives of Virology, 2019)

Conserving Dry Old-Growth Forest in Central Oregon, USA - Andrew Merschel; Robin S Vora; Tom Spies (Journal of Forestry, 2019)

The emerging pathogen of chestnut Gnomoniopsis castaneae: the challenge posed by a versatile fungus - G. Lione; R. Danti; P. Fernandez-Conradi; J. V. Ferreira-Cardoso; F. Lefort; G. Marques; J. B. Meyer; S. Prospero; L. Radócz; C. Robin; T. Turchetti; A. M. Vettraino; et al. (European Journal of Plant Pathology, 2019)

Ocean circulation drifts in multi-millennial climate simulations: the role of salinity corrections and climate feedbacks - Jennifer E. Dentith; Ruza F. Ivanovic; Lauren J. Gregoire; Julia C. Tindall; Robin S. Smith (Climate Dynamics, 2019)

Microplastic ingestion ubiquitous in marine turtles - Emily M. Duncan; Annette C. Broderick; Wayne J. Fuller; Tamara S. Galloway; Matthew H. Godfrey; Mark Hamann; Colin J. Limpus; Penelope K. Lindeque; Andrew G. Mayes; Lucy C. M. Omeyer; David Santillo; Robin T. E. Snape; et al. (Global Change Biology, 2019)
Despite concerns regarding the environmental impacts of microplastics, knowledge of the incidence and levels of synthetic particles in large marine vertebrates is lacking. Here, we utilize an optimized enzymatic digestion methodology, previously developed for zooplankton, to explore whether synthetic particles could be isolated from marine turtle ingesta. We report the presence of synthetic particles in every turtle subjected to investigation ( n = 102) which included individuals from all seven species of marine turtle, sampled from three ocean basins (Atlantic [ATL]: n = 30, four species; Mediterranean (MED): n = 56, two species; Pacific (PAC): n = 16, five species). Most particles ( n = 811) were fibres (ATL: 77.1% MED: 85.3% PAC: 64.8%) with blue and black being the dominant colours. In lesser quantities were fragments (ATL: 22.9%: MED: 14.7% PAC: 20.2%) and microbeads (4.8%; PAC only; to our knowledge the first isolation of microbeads from marine megavertebrates). Fourier transform infrared spectroscopy (FT‐IR) of a subsample of particles ( n = 169) showed a range of synthetic materials such as elastomers (MED: 61.2%; PAC: 3.4%), thermoplastics (ATL: 36.8%: MED: 20.7% PAC: 27.7%) and synthetic regenerated cellulosic fibres (SRCF; ATL: 63.2%: MED: 5.8% PAC: 68.9%). Synthetic particles being isolated from species occupying different trophic levels suggest the possibility of multiple ingestion pathways. These include exposure from polluted seawater and sediments and/or additional trophic transfer from contaminated prey/forage items. We assess the likelihood that microplastic ingestion presents a significant conservation problem at current levels compared to other anthropogenic threats.

Role of prolonged blood culture incubation in infective endocarditis diagnosis - Madiha Fida; Brenda L. Dylla; M. Rizwan Sohail; Bobbi S. Pritt; Audrey N. Schuetz; Robin Patel (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Modulation of the aggregation of an amyloidogenic sequence by flanking-disordered region in the intrinsically disordered antigen merozoite surface protein 2 - Wei Zhang; Jiahai Zhang; Christopher A. MacRaild; Raymond S. Norton; Robin F. Anders; Xuecheng Zhang (European Biophysics Journal, 2019)

Estimating effective population size of large marine populations, is it feasible? - Florianne Marandel; Pascal Lorance; Olivier Berthelé; Verena M. Trenkel; Robin S. Waples; Jean‐Baptiste Lamy (Fish and Fisheries, 2019)
Sustainable exploitation of marine populations is a challenging task relying on information about their current and past abundance. Fisheries‐related data can be scarce and unreliable making them unsuitable for quantitative modelling. One fishery independent method that has attracted attention in this context consists in estimating the effective population size ( N e ), a concept founded in population genetics. We reviewed recent empirical studies on N e and carried out a simulation study to evaluate the feasibility of estimating N e in large fish populations with the currently available methods. The detailed review of 26 studies found that published empirical N e values were very similar despite differences in species and total population sizes ( N ). Genetic simulations for an age‐structured fish population were carried out for a range of population and samples sizes, and N e was estimated using the Linkage Disequilibrium method. The results showed that already for medium‐sized populations (1 million individuals) and common sample sizes (50 individuals), negative estimates were likely to occur which for real applications is commonly interpreted as indicating very large (infinite) N e . Moreover, on average, N e estimates were negatively biased. The simulations further indicated that around 1% of the total number of individuals might have to be sampled to ensure sufficiently precise estimates of N e . For large marine populations, this implies rather large samples (several thousands to millions of individuals). If however such large samples were to be collected, many more population parameters than only N e could be estimated.

Potential impacts of climate change on storage conditions for commercial agriculture: an example for potato production in Michigan - Julie A. Winkler; Logan Soldo; Ying Tang; Todd Forbush; David S. Douches; Chris M. Long; Courtney P. Leisner; C. Robin Buell (Climatic Change, 2018)

Neutral variation does not predict immunogenetic variation in the European grayling ( Thymallus thymallus) —implications for management - J. Vanessa Huml; Martin I. Taylor; W. Edwin Harris; Robin Sen; Jonathan S. Ellis (Molecular Ecology, 2018)
Preservation of genetic diversity is critical to successful conservation, and there is increasing demand for the inclusion of ecologically meaningful genetic information in management decisions. Supportive breeding programmes are increasingly implemented to combat declines in many species, yet their effect on adaptive genetic variation is understudied. This is despite the fact that supportive breeding may interfere with natural evolutionary processes. Here, we assessed the performance of neutral and adaptive markers (major histocompatibility complex; MHC ) to inform management of European grayling ( Thymallus thymallus ), which routinely involves supplementation of natural populations with hatchery‐reared fish (stocking). This study is the first to characterize MH II DAA and DAB loci in grayling and to investigate immune genetic variation in relation to management practice in this species. High‐throughput Illumina sequencing of “introduced,” “stocked native” and “non‐stocked native” populations revealed significantly higher levels of allelic richness and heterozygosity for MH markers than microsatellites exclusively in non‐stocked native populations. Likewise, significantly lower differentiation at the MH II than for microsatellites was apparent when considering non‐stocked native populations, but not stocked populations. We developed a simulation model to test the effects of relaxation of selection during the early life stage within captivity. Dependent on the census population size and stocking intensity, there may be long‐term effects of stocking on MH II , but not neutral genetic diversity. This is consistent with our empirical results. This study highlights the necessity for considering adaptive genetic variation in conservation decisions and raises concerns about the efficiency of stocking as a management practice.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Human Neural Stem Cell Extracellular Vesicles Improve Tissue and Functional Recovery in the Murine Thromboembolic Stroke Model - Robin L. Webb; Erin E. Kaiser; Shelley L. Scoville; Tyler A. Thompson; Sumbul Fatima; Chirayukumar Pandya; Karishma Sriram; Raymond L. Swetenburg; Kumar Vaibhav; Ali S. Arbab; Babak Baban; Krishnan M. Dhandapani; et al. (Translational Stroke Research, 2018)

Stomach contents and diel diving behavior of melon‐headed whales ( Peponocephala electra ) in Hawaiian waters - Kristi L. West; William A. Walker; Robin W. Baird; Daniel L. Webster; Gregory S. Schorr (Marine Mammal Science, 2018)

New records of the rare North American endemic Chara brittonii (Characeae), with comments on its distribution - Kenneth G. Karol; Mitchell S. Alix; Robin W. Scribailo; Paul M. Skawinski; Robin S. Sleith; Joseph A. Sardina; John D. Hall (Brittonia, 2018)

Ecological correlates of the spatial co‐occurrence of sympatric mammalian carnivores worldwide - Courtney L. Davis; Lindsey N. Rich; Zach J. Farris; Marcella J. Kelly; Mario S. Di Bitetti; Yamil Di Blanco; Sebastian Albanesi; Mohammad S. Farhadinia; Navid Gholikhani; Sandra Hamel; Bart J. Harmsen; Claudia Wultsch; et al. (Ecology Letters, 2018)
The composition of local mammalian carnivore communities has far‐reaching effects on terrestrial ecosystems worldwide. To better understand how carnivore communities are structured, we analysed camera trap data for 108 087 trap days across 12 countries spanning five continents. We estimate local probabilities of co‐occurrence among 768 species pairs from the order Carnivora and evaluate how shared ecological traits correlate with probabilities of co‐occurrence. Within individual study areas, species pairs co‐occurred more frequently than expected at random. Co‐occurrence probabilities were greatest for species pairs that shared ecological traits including similar body size, temporal activity pattern and diet. However, co‐occurrence decreased as compared to other species pairs when the pair included a large‐bodied carnivore. Our results suggest that a combination of shared traits and top‐down regulation by large carnivores shape local carnivore communities globally.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Effect of hydration status on pesticide uptake in anurans following exposure to contaminated soils - Donna A. Glinski; W. Matthew Henderson; Robin J. Van Meter; S. Thomas Purucker (Environmental Science and Pollution Research, 2018)

Impact of choice of future climate change projection on growth chamber experimental outcomes: a preliminary study in potato - Courtney P. Leisner; Joshua C. Wood; Brieanne Vaillancourt; Ying Tang; Dave S. Douches; C. Robin Buell; Julie A. Winkler (International Journal of Biometeorology, 2018)

Associations between cyanobacteria and indices of secondary production in the western basin of Lake Erie - James H. Larson; Mary Anne Evans; Robert J. Kennedy; Sean W. Bailey; Keith A. Loftin; Zachary R. Laughrey; Robin A. Femmer; Jeff S. Schaeffer; William B. Richardson; Timothy T. Wynne; J. C. Nelson; Joseph W. Duris (Limnology and Oceanography, 2018)
Large lakes provide a variety of ecological services to surrounding cities and communities. Many of these services are supported by ecological processes that are threatened by the increasing prevalence of cyanobacterial blooms which occur as aquatic ecosystems experience cultural eutrophication. Over the past 10 yr, Lake Erie experienced cyanobacterial blooms of increasing severity and frequency, which have resulted in impaired drinking water for the surrounding communities. Cyanobacterial blooms may impact ecological processes that support other services, but many of these impacts have not been documented. Secondary production (production of primary consumers) is an important process that supports economically important higher trophic levels. Cyanobacterial blooms may influence secondary production because cyanobacteria are a poor‐quality food resource and cyanotoxins may be harmful to consumers. Over 3 yr at 34 sites across the western basin of Lake Erie, we measured three indices of secondary production that focus on the dominant bivalve taxa: (1) growth of a native unionid mussel, (2) the size of young‐of‐year dreissenid mussels, and (3) the mass of colonizing animals on a Hester‐Dendy sampler. Associations between these indices and cyanobacterial data were estimated to assess whether cyanobacteria are associated with variation in secondary production in the western basin of Lake Erie. The results suggest cyanobacterial abundance alone is only weakly associated with secondary production, but that cyanotoxins have a larger effect on secondary production. Given recurring late‐summer cyanobacterial blooms, this impact on secondary production has the potential to undermine Lake Erie's ability to sustain important ecosystem services.

Adapting clonally propagated crops to climatic changes: a global approach for taro (Colocasia esculenta (L.) Schott) - V. Lebot; V. Tuia; A. Ivancic; G. V. H. Jackson; F. Saborio; G. Reyes; S. Rodriguez; G. Robin; R. Traoré; L. Aboagye; J. Onyeka; W. van Rensburg; et al. (Genetic Resources and Crop Evolution, 2018)

Improvement of cowpea productivity by rhizobial and mycorrhizal inoculation in Burkina Faso - Hadou Haro; Kadidia B. Sanon; Christine Le Roux; Robin Duponnois; Alfred S. Traoré (Symbiosis, 2018)

Digestive enzyme ratios are good indicators of hatchling yolk reserve and digestive gland maturation in early life stages of cuttlefish Sepia officinalis L.: application of these new tools in ecology and aquaculture - Georges Safi; A. S. Martinez; C. Le Pabic; E. Le Bihan; J. P. Robin; N. Koueta (Journal of Comparative Physiology B, 2018)

Projecting Marine Mammal Distribution in a Changing Climate - Gregory K. Silber; Matthew D. Lettrich; Peter O. Thomas; Jason D. Baker; Mark Baumgartner; Elizabeth A. Becker; Peter Boveng; Dorothy M. Dick; Jerome Fiechter; Jaume Forcada; Karin A. Forney; Roger B. Griffis; et al. (Frontiers in Marine Science, 2017)

Banded Leaf and Sheath Blight of Maize: Historical Perspectives, Current Status and Future Directions - K. S. Hooda; M. K. Khokhar; H. Parmar; Robin Gogoi; Deeksha Joshi; S. S. Sharma; O. P. Yadav (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Non-targeted workflow for identification of antimicrobial compounds in animal feed using bioassay-directed screening in combination with liquid chromatography-high resolution mass spectrometry - Robin S. Wegh; Bjorn J. A. Berendsen; Wilma D. M. Driessen-Van Lankveld; Mariël G. Pikkemaat; Tina Zuidema; Leen A. Van Ginkel (Food Additives & Contaminants: Part A, 2017)

Deciphering the enigma of undetected species, phylogenetic, and functional diversity based on Good‐Turing theory - Anne Chao; Chun‐Huo Chiu; Robert K. Colwell; Luiz Fernando S. Magnago; Robin L. Chazdon; Nicholas J. Gotelli (Ecology, 2017)
Estimating the species, phylogenetic, and functional diversity of a community is challenging because rare species are often undetected, even with intensive sampling. The Good‐Turing frequency formula, originally developed for cryptography, estimates in an ecological context the true frequencies of rare species in a single assemblage based on an incomplete sample of individuals. Until now, this formula has never been used to estimate undetected species, phylogenetic, and functional diversity. Here, we first generalize the Good‐Turing formula to incomplete sampling of two assemblages. The original formula and its two‐assemblage generalization provide a novel and unified approach to notation, terminology, and estimation of undetected biological diversity. For species richness, the Good‐Turing framework offers an intuitive way to derive the non‐parametric estimators of the undetected species richness in a single assemblage, and of the undetected species shared between two assemblages. For phylogenetic diversity, the unified approach leads to an estimator of the undetected Faith's phylogenetic diversity ( PD , the total length of undetected branches of a phylogenetic tree connecting all species), as well as a new estimator of undetected PD shared between two phylogenetic trees. For functional diversity based on species traits, the unified approach yields a new estimator of undetected Walker et al.'s functional attribute diversity ( FAD , the total species‐pairwise functional distance) in a single assemblage, as well as a new estimator of undetected FAD shared between two assemblages. Although some of the resulting estimators have been previously published (but derived with traditional mathematical inequalities), all taxonomic, phylogenetic, and functional diversity estimators are now derived under the same framework. All the derived estimators are theoretically lower bounds of the corresponding undetected diversities; our approach reveals the sufficient conditions under which the estimators are nearly unbiased, thus offering new insights. Simulation results are reported to numerically verify the performance of the derived estimators. We illustrate all estimators and assess their sampling uncertainty with an empirical dataset for Brazilian rain forest trees. These estimators should be widely applicable to many current problems in ecology, such as the effects of climate change on spatial and temporal beta diversity and the contribution of trait diversity to ecosystem multi‐functionality.

Modelling small groundwater systems: experiences from the Braunton Burrows and Ainsdale coastal dune systems, UK - Corinna Abesser; Derek Clarke; Andrew G. Hughes; Nick S. Robins (Journal of Coastal Conservation, 2017)

A conceptual snapsot of a big coastal dune aquifer: Magilligan, Northern Ireland - N. S. Robins; P. Wilson (Journal of Coastal Conservation, 2017)

Depth of soil compaction predominantly affects rice yield reduction by reproductive-stage drought at varietal screening sites in Bangladesh, India, and Nepal - Suresh Prasad Singh; Abhinav Jain; M. S. Anantha; Santosh Tripathi; Subarna Sharma; Santosh Kumar; Archana Prasad; Bhawana Sharma; Biswajit Karmakar; Rudra Bhattarai; Sankar Prasad Das; Shravan K. Singh; et al. (Plant and Soil, 2017)

Assessing global patterns in mammalian carnivore occupancy and richness by integrating local camera trap surveys - Lindsey N. Rich; Courtney L. Davis; Zach J. Farris; David A. W. Miller; Jody M. Tucker; Sandra Hamel; Mohammad S. Farhadinia; Robin Steenweg; Mario S. Di Bitetti; Kanchan Thapa; Mamadou D. Kane; S. Sunarto; et al. (Global Ecology and Biogeography, 2017)
Aim Biodiversity loss is a major driver of ecosystem change, yet the ecological data required to detect and mitigate losses are often lacking. Recently, camera trap surveys have been suggested as a method for sampling local wildlife communities, because these observations can be collated into a global monitoring network. To demonstrate the potential of camera traps for global monitoring, we assembled data from multiple local camera trap surveys to evaluate the interchange between fine‐ and broad‐scale processes impacting mammalian carnivore communities. Location Argentina, Belize, Botswana, Canada, Indonesia, Iran, Madagascar, Nepal, Norway, Senegal, South Africa, and the U.S.A. Methods We gathered camera trap data, totalling > 100,000 trap nights, from across five continents. To analyse local and species‐specific responses to anthropogenic and environmental variables, we fitted multispecies occurrence models to each study area. To analyse global‐level responses, we then fitted a multispecies, multi‐area occurrence model. Results We recorded 4,805 detections of 96 mammalian carnivore species photographed across 1,714 camera stations located in 12 countries. At the global level, our models revealed that carnivore richness and occupancy within study areas was positively associated with prey availability. Occupancy within study areas also tended to increase with greater protection and greater distances to roads. The strength of these relationships, however, differed among countries. Main conclusions We developed a research framework for leveraging global camera trap data to evaluate patterns of mammalian carnivore occurrence and richness across multiple spatial scales. Our research highlights the importance of intact prey populations and protected areas in conserving carnivore communities. Our research also highlights the potential of camera traps for monitoring wildlife communities and provides a case study for how this can be achieved on a global scale. We encourage greater integration and standardization among camera trap studies worldwide, which would help inform effective conservation planning for wildlife populations both locally and globally.

Performance of IUCN proxies for generation length - Han Chi Fung; Robin S. Waples (Conservation Biology, 2017)
One of the criteria used by the International Union for Conservation of Nature (IUCN) to assess threat status is the rate of decline in abundance over 3 generations or 10 years, whichever is longer. The traditional method for calculating generation length ( T ) uses age‐specific survival and fecundity, but these data are rarely available. Consequently, proxies that require less information are often used, which introduces potential biases. The IUCN recommends 2 proxies based on adult mortality rate, = α + 1/ d , and reproductive life span, = α + z * RL, where α is age at first reproduction, d is adult mortality rate, RL is reproductive life span, and z is a coefficient derived from data for comparable species. We used published life tables for 78 animal and plant populations to evaluate precision and bias of these proxies by comparing and with true generation length. Mean error rates in estimating T were 31% for and 20% for , but error rates for were 16% when we subtracted 1 year ( ), as suggested by theory; also provided largely unbiased estimates regardless of the true generation length. Performance of depends on compilation of detailed data for comparable species, but our results suggest taxonomy is not a reliable indicator of comparability. All 3 proxies depend heavily on a reliable estimate of age at first reproduction, as we illustrated with 2 test species. The relatively large mean errors for all proxies emphasized the importance of collecting the detailed life‐history information necessary to calculate true generation length. Unfortunately, publication of such data is less common than it was decades ago. We identified generic patterns of age‐specific change in vital rates that can be used to predict expected patterns of bias from applying .

Physical mapping of 35S rRNA genes and genome size variation in polyploid series of Sisyrinchium micranthum and S. rosulatum (Iridaceae: Iridoideae) - L. O. Tacuatiá; E. Kaltchuk-Santos; T. T. Souza-Chies; L. Eggers; E. R. Forni-Martins; F. Pustahija; O. Robin; S. Siljak-Yakovlev (Plant Biosystems, 2017)

Successful suction‐cup tagging of a small delphinid species, Stenella attenuata : Insights into whistle characteristics - Tammy L. Silva; T. Aran Mooney; Laela S. Sayigh; Robin W. Baird; Peter L. Tyack (Marine Mammal Science, 2017)

Demographic Drivers of Aboveground Biomass Dynamics During Secondary Succession in Neotropical Dry and Wet Forests - Danaë M. A. Rozendaal; Robin L. Chazdon; Felipe Arreola-Villa; Patricia Balvanera; Tony V. Bentos; Juan M. Dupuy; J. Luis Hernández-Stefanoni; Catarina C. Jakovac; Edwin E. Lebrija-Trejos; Madelon Lohbeck; Miguel Martínez-Ramos; Paulo E. S. Massoca; et al. (Ecosystems, 2017)

Purging putative siblings from population genetic data sets: a cautionary view - Robin S. Waples; Eric C. Anderson (Molecular Ecology, 2017)
Interest has surged recently in removing siblings from population genetic data sets before conducting downstream analyses. However, even if the pedigree is inferred correctly, this has the potential to do more harm than good. We used computer simulations and empirical samples of coho salmon to evaluate strategies for adjusting samples to account for family structure. We compared performance in full samples and sibling‐reduced samples of estimators of allele frequency ( ), population differentiation ( ) and effective population size ( ). Results: (i) unless simulated samples included large family groups together with a component of unrelated individuals, removing siblings generally reduced precision of and ; (ii) based on the linkage disequilibrium method was largely unbiased using full random samples but became increasingly upwardly biased under aggressive purging of siblings. Under nonrandom sampling (some families over‐represented), using full samples was downwardly biased; removing just the right ‘Goldilocks’ fraction of siblings could produce an unbiased estimate, but this sweet spot varied widely among scenarios; (iii) weighting individuals based on the inferred pedigree (to produce a best linear unbiased estimator, BLUE) maximized precision of when the inferred pedigree was correct but performed poorly when the pedigree was wrong; (iv) a variant of sibling removal that leaves intact small sibling groups appears to be more robust to errors in inferences about family structure. Our results illustrate the complex challenges posed by presence of family structure, suggest that no single optimal solution exists and argue for caution in adjusting population genetic data sets for the presence of putative siblings without fully understanding the consequences.

Assessments of species’ vulnerability to climate change: from pseudo to science - Alisa A. Wade; Brian K. Hand; Ryan P. Kovach; Clint C. Muhlfeld; Robin S. Waples; Gordon Luikart (Biodiversity and Conservation, 2017)

Trends and management implications of human‐influenced life‐history changes in marine ectotherms - Asta Audzijonyte; Elizabeth Fulton; Malcolm Haddon; Fay Helidoniotis; Alistair J Hobday; Anna Kuparinen; John Morrongiello; Anthony DM Smith; Judy Upston; Robin S Waples (Fish and Fisheries, 2016)
Evidence is accumulating that many marine ectotherms are undergoing rapid changes in their life‐history characteristics. These changes have been variously attributed to fisheries‐induced evolution, inhibited adult growth rate due to oxygen limitation at higher temperatures, and plastic responses to density dependence or changes in ocean productivity. Here, we review the diverse underlying mechanisms by which plastic and evolutionary responses to climate change and fisheries are likely to produce similar life‐history trends in harvested marine ectotherms, leading to faster life‐histories with earlier maturation and smaller adult size‐at‐age. While mechanistically understanding these growth and maturation changes may be difficult, it is becoming clear that changing life‐histories will lead to modified population dynamics, productivity and natural mortality of the affected species. We discuss how the observed and expected life‐history changes could affect the assumptions and uncertainty within single and multispecies models currently used in marine ecosystem management, highlighting that models which allow for dynamic life‐history traits often report significantly different estimates of stock biomass. Given that both climate‐ and harvest‐induced life‐history changes are likely to intensify and possibly amplify each other, there is an urgent need to adequately assess the implications of faster life‐histories for marine ecosystem management. This is especially true for data‐poor stocks, where growth and maturation are not regularly assessed. Targeted monitoring can be used to inform responsive management, but for improved sustainability outcomes, a precautionary approach to management that is robust to life‐history trends is advised.

The extreme capsule fiber complex in humans and macaque monkeys: a comparative diffusion MRI tractography study - Rogier B. Mars; Sean Foxley; Lennart Verhagen; Saad Jbabdi; Jérôme Sallet; MaryAnn P. Noonan; Franz-Xaver Neubert; Jesper L. Andersson; Paula L. Croxson; Robin I. M. Dunbar; Alexandre A. Khrapitchev; Nicola R. Sibson; et al. (Brain Structure and Function, 2016)

Making sense of genetic estimates of effective population size - Robin S. Waples (Molecular Ecology, 2016)
The last decade has seen an explosion of interest in use of genetic markers to estimate effective population size, N e . Effective population size is important both theoretically ( N e is a key parameter in almost every aspect of evolutionary biology) and for practical application ( N e determines rates of genetic drift and loss of genetic variability and modulates the effectiveness of selection, so it is crucial to consider in conservation). As documented by Palstra & Fraser ( ), most of the recent growth in N e estimation can be attributed to development or refinement of methods that can use a single sample of individuals (the older temporal method requires at least two samples separated in time). As with other population genetic methods, performance of new N e estimators is typically evaluated with simulated data for a few scenarios selected by the author(s). Inevitably, these initial evaluations fail to fully consider the consequences of violating simplifying assumptions, such as discrete generations, closed populations of constant size and selective neutrality. Subsequently, many researchers studying natural or captive populations have reported estimates of N e for multiple methods; often these estimates are congruent, but that is not always the case. Because true N e is rarely known in these empirical studies, it is difficult to make sense of the results when estimates differ substantially among methods. What is needed is a rigorous, comparative analysis under realistic scenarios for which true N e is known. Recently, Gilbert & Whitlock ( ) did just that for both single‐sample and temporal methods under a wide range of migration schemes. In the current issue of Molecular Ecology, Wang ( ) uses simulations to evaluate performance of four single‐sample N e estimators. In addition to assessing effects of true N e , sample size, and number of loci, Wang also evaluated performance under changing abundance, physical linkage and genotyping errors, as well as for some alternative life histories (high rates of selfing; haplodiploids). Wang showed that the sibship frequency (SF) and linkage disequilibrium (LD) methods perform dramatically better than the heterozygote excess and molecular coancestry methods under most scenarios (see Fig. 1, modified from figure 2 in Wang ), and he also concluded that SF is generally more versatile than LD. This article represents a truly Herculean effort, and results should be of considerable value to researchers interested in applying these methods to real‐world situations.

When is a forest a forest? Forest concepts and definitions in the era of forest and landscape restoration - Robin L. Chazdon; Pedro H. S. Brancalion; Lars Laestadius; Aoife Bennett-Curry; Kathleen Buckingham; Chetan Kumar; Julian Moll-Rocek; Ima Célia Guimarães Vieira; Sarah Jane Wilson (Ambio, 2016)

Influence of suspended particulate matter on nutrient biogeochemistry of a tropical shallow lagoon, Chilika, India - Sivaji Patra; A. V. Raman; D. Ganguly; R. S. Robin; P. R. Muduli; VishnuVardhan Kanuri; K. R. Abhilash; B. Charan Kumar; B. R. Subramanian (Limnology, 2016)

Evaluation of virus resistance and agronomic performance of rice cultivar ASD 16 after transfer of transgene against Rice tungro bacilliform virus by backcross breeding - P. Valarmathi; G. Kumar; S. Robin; S. Manonmani; I. Dasgupta; R. Rabindran (Virus Genes, 2016)

Erratum to: Analysis of pediatric airway morphology using statistical shape modeling - Stephen M. Humphries; Kendall S. Hunter; Robin Shandas; Robin R. Deterding; Emily M. DeBoer (Medical & Biological Engineering & Computing, 2016)

Analysis of pediatric airway morphology using statistical shape modeling - Stephen M. Humphries; Kendall S. Hunter; Robin Shandas; Robin R. Deterding; Emily M. DeBoer (Medical & Biological Engineering & Computing, 2016)

How to Replicate the Functions and Biodiversity of a Threatened Tree Species? The Case of Fraxinus excelsior in Britain - Ruth J. Mitchell; Robin J. Pakeman; Alice Broome; Joan K. Beaton; Paul E. Bellamy; Rob W. Brooker; Chris J. Ellis; Alison J. Hester; Nick G. Hodgetts; Glenn R. Iason; Nick A. Littlewood; Gabor Pozsgai; et al. (Ecosystems, 2016)

Irreducible uncertainty in near-term climate projections - Ed Hawkins; Robin S. Smith; Jonathan M. Gregory; David A. Stainforth (Climate Dynamics, 2016)

Genetics of wide compatible gene and variability studies in rice (Oryza sativa L.) - S. REVATHI; K. SAKTHIVEL; S. MANONMANI; M. UMADEVI; R. USHAKUMARI; S. ROBIN (Journal of Genetics, 2016)

Middle Eocene-Early Miocene larger foraminifera from Dhofar (Oman) and Socotra Island (Yemen) - J. Serra-Kiel; A. Gallardo-Garcia; Ph. Razin; J. Robinet; J. Roger; C. Grelaud; S. Leroy; C. Robin (Arabian Journal of Geosciences, 2016)

Trematode diversity in freshwater fishes of the Globe II: ‘New World’ - Anindo Choudhury; M. Leopoldina Aguirre-Macedo; Stephen S. Curran; Margarita Ostrowski de Núñez; Robin M. Overstreet; Gerardo Pérez-Ponce de León; Cláudia Portes Santos (Systematic Parasitology, 2016)

Mesoscopic Fluorescence Molecular Tomography for Evaluating Engineered Tissues - Mehmet S. Ozturk; Chao-Wei Chen; Robin Ji; Lingling Zhao; Bao-Ngoc B. Nguyen; John P. Fisher; Yu Chen; Xavier Intes (Annals of Biomedical Engineering, 2016)

Fire fit: assessing comprehensive fitness and injury risk in the fire service - Gerald S. Poplin; Denise J. Roe; Jefferey L. Burgess; Wayne F. Peate; Robin B. Harris (International Archives of Occupational and Environmental Health, 2016)

Recovery rates of bottlenose dolphin ( Tursiops truncatus ) carcasses estimated from stranding and survival rate data - James V. Carretta; Kerri Danil; Susan J. Chivers; David W. Weller; David S. Janiger; Michelle Berman‐Kowalewski; Keith M. Hernandez; James T. Harvey; Robin C. Dunkin; David R. Casper; Shelbi Stoudt; Maureen Flannery; et al. (Marine Mammal Science, 2016)
Recovery of cetacean carcasses provides data on levels of human‐caused mortality, but represents only a minimum count of impacts. Counts of stranded carcasses are negatively biased by factors that include at‐sea scavenging, sinking, drift away from land, stranding in locations where detection is unlikely, and natural removal from beaches due to wave and tidal action prior to detection. We estimate the fraction of carcasses recovered for a population of coastal bottlenose dolphins ( Tursiops truncatus ), using abundance and survival rate data to estimate annual deaths in the population. Observed stranding numbers are compared to expected deaths to estimate the fraction of carcasses recovered. For the California coastal population of bottlenose dolphins, we estimate the fraction of carcasses recovered to be 0.25 (95% CI = 0.20–0.33). During a 12 yr period, 327 animals (95% CI = 253–413) were expected to have died and been available for recovery, but only 83 carcasses attributed to this population were documented. Given the coastal habits of California coastal bottlenose dolphins, it is likely that carcass recovery rates of this population greatly exceed recovery rates of more pelagic dolphin species in the region.

First observed wild birth and acoustic record of a possible infanticide attempt on a common bottlenose dolphin ( Tursiops truncatus ) - Robin M. Perrtree; Laela S. Sayigh; Allison Williford; Alessandro Bocconcelli; Mary Carla Curran; Tara M. Cox (Marine Mammal Science, 2016)

Application of airborne LiDAR to investigate rates of recession in rocky coast environments - Claire S. Earlie; Gerd Masselink; Paul E. Russell; Robin K. Shail (Journal of Coastal Conservation, 2015)

Identification and characterization of Fusarium spp. associated with root rots of field pea in North Dakota - Kishore Chittem; Febina M. Mathew; Matthew Gregoire; Robin S. Lamppa; Yen Wei Chang; Samuel G. Markell; Carl A. Bradley; Tharcisse Barasubiye; Rubella S. Goswami (European Journal of Plant Pathology, 2015)

Development and applications of a DNA labeling method with magnetic nanoparticles to study the role of horizontal gene transfer events between bacteria in soil pollutant bioremediation processes - J. Pivetal; M. Frénéa-Robin; N. Haddour; C. Vézy; L. F. Zanini; G. Ciuta; N. M. Dempsey; F. Dumas-Bouchiat; G. Reyne; S. Bégin-Colin; D. Felder-Flesh; C. Ghobril; et al. (Environmental Science and Pollution Research, 2015)

Pesticide Uptake Across the Amphibian Dermis Through Soil and Overspray Exposures - Robin J. Van Meter; Donna A. Glinski; W. Matthew Henderson; A. Wayne Garrison; Mike Cyterski; S. Thomas Purucker (Archives of Environmental Contamination and Toxicology, 2015)

New Caledonia: a Pleistocene refugium for rain forest lineages of relict angiosperms - Robin Pouteau; Santiago Trueba; Taylor S. Feild; Sandrine Isnard (Journal of Biogeography, 2015)
Aim In New Caledonia, relictual angiosperm lineages are over‐represented. However, the mechanisms responsible for such a distribution remain unclear. Two key hypotheses are that: (1) the diversity reflects adaptation to ultramafic substrates that ecologically filtered plant colonists; and (2) the diversity stems from wet climatic conditions that have persisted in New Caledonia during the late Quaternary while Australia and some nearby islands experienced widespread extinction events. Here, we investigate which hypothesis better explains the disharmony of relict angiosperms in New Caledonia. Location New Caledonia (South West Pacific Ocean). Methods We built species distribution models from herbarium data to determine the environmental correlates for 60 relict angiosperm taxa. Environmental variables used to characterize habitats included vegetation, substrate, and climate variables. We then tested whether the variety of xylem conduit structures borne by New Caledonian relict angiosperms, which is expected to affect plant hydraulic capacity, was correlated with habitat preference. Finally, we analysed species prevalence on different substrates and projected habitat size and distribution to the Last Glacial Maximum ( LGM ). Results We found a clear habitat preference among relict angiosperms for rain forests located on non‐ultramafic substrates, with the exception of taxa bearing true vessels with simple perforation plates, which harboured a wider habitat breadth. We also showed that these rain forest habitats experienced a range reduction and an eastward shift during the LGM , forming two refugial areas located on the warm and rainy east coast of Grande Terre. Main conclusions Prevalence of relict angiosperms in habitats characterized by low evaporative demand appears to be related to xylem hydraulic limitations. The disharmony of relict angiosperms in New Caledonia therefore arose from the persistence of rain forests in the island despite global fluctuations in climate during the Quaternary that affected floras in the region. Our study offers a new model to explain why certain angiosperm families are disharmonically represented in New Caledonia.

High site fidelity, strong associations, and long‐term bonds: Short‐finned pilot whales off the island of Hawai‘i - Sabre D. Mahaffy; Robin W. Baird; Daniel J. McSweeney; Daniel L. Webster; Gregory S. Schorr (Marine Mammal Science, 2015)
Studies of short‐finned pilot whales suggest they travel in stable mixed‐sex groups composed of strongly associated individuals; however, temporal analyses of social structure are lacking. To examine site fidelity, association patterns, and temporal relationships, we analyzed data from 267 encounters of this species off the island of Hawai‘i from 2003 through 2007, identifying 448 distinctive individuals (68.1% seen more than once). About 72% of the whales were linked by association into a single social network, suggesting the possibility of multiple populations using the area. Sighting histories suggested that only some individuals exhibit high site fidelity. Individuals demonstrated preferential associations and community division was strongly supported by average‐linkage hierarchical cluster analysis of the association data. Nine longitudinally stable social units composed of key individuals and their constant companions were identified. Qualitative assignment of age and sex classes of unit members indicated that some segregation between adult males and female/calf pairs may occur. Temporal analyses of individuals encountered on the same day indicate stable long‐term associations. Differential patterns of residency and site fidelity were unexpected and may be indicative of multiple populations around the main Hawaiian Islands. The presence of a resident population demonstrating strong, long‐term site fidelity and associations off Hawai‘i Island may warrant special management considerations.

The use of Depletion Methods to assess Mediterranean cephalopod stocks under the current EU Data Collection Framework - S. KELLER; J.-P. ROBIN; M. VALLS; M. GRAS; M. CABANELLAS-REBOREDO; A. QUETGLAS (Mediterranean Marine Science, 2015)
Fuelled by the raising importance of cephalopod fisheries in Europe, there have been demands from scientists and stakeholders for their assessment and management. However, little has been done to improve the data collection in order to analyse cephalopod populations under the EU Data Collection Framework (DCF). While the DCF allows member states to design flexible national sampling programmes, it establishes the minimum data requirements (MDR) each state is obliged to fulfil. In this study, it was investigated whether such MDR currently set by the DCF allow the application of depletion models (DMs) to assess European cephalopod stocks. Squid and cuttlefish fisheries from the western Mediterranean were used as a case study. This exercise sheds doubt on the suitability of the MDR to properly assess and manage cephalopod stocks by means of DMs. Owing to the high plasticity of life-history traits in cephalopod populations, biological parameters should be estimated during the actual depletion period of the fished stocks, in contrast with the triennial sampling established by the DCF. In order to accurately track the depletion event, the rapid growth rates of cephalopods implies that their populations should be monitored at shorter time scales (ideally weekly or biweekly) instead of quarterly as required by the DCF. These measures would not demand additional resources of the ongoing DCF, but a redistribution of sampling efforts during the depletion period. Such changes in the sampling scheme could be designed and undertaken by the member states or directly integrated as requirements.

Mathematical Models to Explore Potential Effects of Supersaturation and Precipitation on Oral Bioavailability of Poorly Soluble Drugs - Mary S. Kleppe; Kelly M. Forney-Stevens; Roy J. Haskell; Robin H. Bogner (The AAPS Journal, 2015)

Unraveling the nutritional and therapeutic properties of ‘Kavuni’ a traditional rice variety of Tamil Nadu - R. Valarmathi; M. Raveendran; S. Robin; N. Senthil (Journal of Plant Biochemistry and Biotechnology, 2015)

Influence of nutrient input on the trophic state of a tropical brackish water lagoon - D Ganguly; Sivaji Patra; Pradipta R Muduli; K Vishnu Vardhan; Abhilash K R; R S Robin; B R Subramanian (Journal of Earth System Science, 2015)

Invertebrate diversity of the unexplored marine western margin of Australia: taxonomy and implications for global biodiversity - Gary C. B. Poore; Lynda Avery; Magda Błażewicz-Paszkowycz; Joanna Browne; Niel L. Bruce; Sarah Gerken; Chris Glasby; Elizabeth Greaves; Anna W. McCallum; David Staples; Anna Syme; Joanne Taylor; et al. (Marine Biodiversity, 2015)

Distribution of Nitellopsis obtusa (Characeae) in New York, U.S.A. - Robin S. Sleith; Amy J. Havens; Robert A. Stewart; Kenneth G. Karol (Brittonia, 2015)

Brainstem Opioidergic System Is Involved in Early Response to Experimental SAH - Justin S. Cetas; Robin McFarlane; Kassi Kronfeld; Phoebe Smitasin; Jesse J. Liu; Jeffrey S. Raskin (Translational Stroke Research, 2015)

Reply to “Letter to the Editor: Consistency Among Musculoskeletal Models: Caveat Utilitor” - David W. Wagner; Vahagn Stepanyan; James M. Shippen; Matthew S. DeMers; Robin S. Gibbons; Brian J. Andrews; Graham H. Creasey; Gary S. Beaupre (Annals of Biomedical Engineering, 2015)

Productivity enhances benthic species richness along an oligotrophic I ndian O cean continental margin - Anna W. McCallum; Skipton Woolley; Magda Błażewicz‐Paszkowycz; Joanna Browne; Sarah Gerken; Rudy Kloser; Gary C. B. Poore; David Staples; Anna Syme; Joanne Taylor; Genefor Walker‐Smith; Alan Williams; et al. (Global Ecology and Biogeography, 2015)
Aims Marine soft sediments cover much of the deep ocean and are one of the largest habitats in the world, yet much of our understanding about their diversity is based on sampling in the N orth A tlantic. The deep‐sea benthos provides a simplified environment in which to explore the processes which maintain species richness. Here we investigate the influence of energy and habitat complexity on benthic species richness along an oligotrophic continental margin within the I ndian O cean. Location The upper continental margin of western A ustralia ( c . 13–35° S , 100–1000 m depth). Methods We examined the species richness of selected polychaetes ( A nnelida) and crustaceans in sediment grab samples. We used generalized linear models and hierarchical partitioning to examine the relationship and relative importance of temperature, productivity (particulate organic carbon flux, net primary productivity and depth) and habitat complexity (sediment particle size diversity and grain size) on species richness at 51 sites. Results In contrast to benthic studies in the N orth A tlantic, we found that species richness was higher on the shelf than on the slope. Species richness was positively correlated with net primary productivity; this relationship was influenced by high species richness in two areas where oceanic mixing is known to enhance primary productivity. Habitat heterogeneity and temperature were less influential. Main conclusion This study represents one of the first extensive quantitative studies of deep‐water benthos in the I ndo‐ W est P acific, and provides further evidence that bathymetric gradients of species richness are variable between regions, probably due to variation in local oceanography and productivity regimes. Our findings provide support for the overriding influence of productivity on species richness, even over relatively small ranges in depth and productivity. As climate change is expected to modify biogeochemical fluxes to the deep seafloor, this is likely to affect the communities of deep‐sea fauna.

Mismatch repair deficient-crypts in non-neoplastic colonic mucosa in Lynch syndrome: insights from an illustrative case - Jinru Shia; Zsofia K. Stadler; Martin R. Weiser; Efsevia Vakiani; Robin Mendelsohn; Arnold J. Markowitz; Moshe Shike; C. Richard Boland; David S. Klimstra (Familial Cancer, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Food web complexity and stability across habitat connectivity gradients - Robin M. LeCraw; Pavel Kratina; Diane S. Srivastava (Oecologia, 2014)

Treatment of potato tubers with the synthetic cytokinin 1-(α-ethylbenzyl)-3-nitroguanidine results in rapid termination of endodormancy and induction of transcripts associated with cell proliferation and growth - Michael Campbell; Jeffrey Suttle; David S. Douches; C. Robin Buell (Functional & Integrative Genomics, 2014)

How pastoralism changes savanna vegetation: impact of old pastoral settlements on plant diversity and abundance in south-western Kenya - Ville Vuorio; Andrew Muchiru; Robin S. Reid; Joseph O. Ogutu (Biodiversity and Conservation, 2014)

Erratum to: Marker assisted backcross breeding approach to improve blast resistance in Indian rice (Oryza sativa) variety ADT43 - Balakrishnan Divya; S. Robin; R. Rabindran; N. Senthil; M. Raveendran; A. John Joel (Euphytica, 2014)

Marker assisted backcross breeding approach to improve blast resistance in Indian rice (Oryza sativa) variety ADT43 - Balakrishnan Divya; S. Robin; R. Rabindran; S. Senthil; M. Raveendran; A. John Joel (Euphytica, 2014)

Pathogen-associated self-medication behavior in the honeybee Apis mellifera - Bogdan I. Gherman; Andreas Denner; Otilia Bobiş; Daniel S. Dezmirean; Liviu A. Mărghitaş; Helge Schlüns; Robin F. A. Moritz; Silvio Erler (Behavioral Ecology and Sociobiology, 2014)

Combined transgenic expression of Punica granatum conjugase (FADX) and FAD2 desaturase in high linoleic acid Arabidopsis thaliana mutant leads to increased accumulation of punicic acid - Elzbieta Mietkiewska; Robin Miles; Aruna Wickramarathna; Ariff Firman Sahibollah; Michael S. Greer; Guanqun Chen; Randall J. Weselake (Planta, 2014)

Biodiversity patterns of nutrient-rich fish ponds and implications for conservation - A. Wezel; B. Oertli; V. Rosset; F. Arthaud; B. Leroy; R. Smith; S. Angélibert; G. Bornette; D. Vallod; J. Robin (Limnology, 2014)

A substitution mutation in OsCCD7 cosegregates with dwarf and increased tillering phenotype in rice - KRISHNANAND P. KULKARNI; CHANDRAPAL VISHWAKARMA; SARADA P. SAHOO; JOHN M. LIMA; MANOJ NATH; PRASAD DOKKU; RAJESH N. GACCHE; TRILOCHAN MOHAPATRA; S. ROBIN; N. SARLA; M. SESHASHAYEE; ASHOK K. SINGH; et al. (Journal of Genetics, 2014)

Gene interactions and genetics of blast resistance and yield attributes in rice (Oryza sativa L.) - B. DIVYA; A. BISWAS; S. ROBIN; R. RABINDRAN; A. JOHN JOEL (Journal of Genetics, 2014)

Transcriptome analysis of salinity responsiveness in contrasting genotypes of finger millet (Eleusine coracana L.) through RNA-sequencing - Hifzur Rahman; N. Jagadeeshselvam; R. Valarmathi; B. Sachin; R. Sasikala; N. Senthil; D. Sudhakar; S. Robin; Raveendran Muthurajan (Plant Molecular Biology, 2014)

Incidence rates of surgically treated rhegmatogenous retinal detachment among manual workers, non-manual workers and housewives in Tuscany, Italy - Stefania Curti; David Coggon; Alberto Baldasseroni; Robin M. T. Cooke; Michela Fresina; Emilio C. Campos; Francesco Semeraro; Francesca Zanardi; Andrea Farioli; Francesco S. Violante; Stefano Mattioli (International Archives of Occupational and Environmental Health, 2014)

Calibration of a hysteretic model for glass fiber reinforced gypsum wall panels - Maganti Janardhana; P. Robin Davis; S. S. Ravichandran; A. M. Prasad; D. Menon (Earthquake Engineering and Engineering Vibration, 2014)

Can leg ulcer fibroblasts phenotype be influenced by human amniotic membrane extract? - H. Tauzin; S. Robin; P. Humbert; C. Viennet; P. Saas; C. Courderot-Masuyer; P. Muret (Cell and Tissue Banking, 2014)

Temporal evolution and vertical stratification of Microcystis toxic potential during a first bloom event - H. Ait Hammou; D. Latour; M. Sabart; S. Samoudi; Kh. Mouhri; J. Robin; M. Loudiki (Aquatic Ecology, 2014)

Climate rather than geography separates two E uropean honeybee subspecies - Cristian O. Coroian; Irene Muñoz; Ellen A. Schlüns; Orsolya R. Paniti‐Teleky; Silvio Erler; Emilia M. Furdui; Liviu A. Mărghitaş; Daniel S. Dezmirean; Helge Schlüns; Pilar de la Rúa; Robin F. A. Moritz (Molecular Ecology, 2014)
Both climatic and geographical factors play an important role for the biogeographical distribution of species. The C arpathian mountain ridge has been suggested as a natural geographical divide between the two honeybee subspecies A pis mellifera carnica and A . m. macedonica . We sampled one worker from one colony each at 138 traditional apiaries located across the C arpathians spanning from the H ungarian plains to the D anube delta. All samples were sequenced at the mitochondrial t RNA Leu ‐cox2 intergenic region and genotyped at twelve microsatellite loci. The C arpathians had only limited impact on the biogeography because both subspecies were abundant on either side of the mountain ridge. In contrast, subspecies differentiation strongly correlated with the various temperature zones in R omania. A . m. carnica is more abundant in regions with the mean average temperature below 9 °C, whereas A. m. macedonica honeybees are more frequent in regions with mean temperatures above 9 °C. This range selection may have impact on the future biogeography in the light of anticipated global climatic changes.

Large herbivore responses to surface water and land use in an East African savanna: implications for conservation and human-wildlife conflicts - Joseph O. Ogutu; Robin S. Reid; Hans-Peter Piepho; Nicholas T. Hobbs; Michael E. Rainy; Russell L. Kruska; Jeffrey S. Worden; Meshack Nyabenge (Biodiversity and Conservation, 2014)

Resistance reaction of gene introgressed lines against rice blast (Pyricularia oryzae) disease - B. Divya; S. Robin; R. Rabindran; H. Manjunath; P. Valarmathi; A. John Joel (Australasian Plant Pathology, 2014)

Biodiversity in eutrophicated shallow lakes: determination of tipping points and tools for monitoring - J. Robin; A. Wezel; G. Bornette; F. Arthaud; S. Angélibert; V. Rosset; B. Oertli (Hydrobiologia, 2014)

Levisunguis subaequalis n. g., n. sp., a tongue worm (Pentastomida: Porocephalida: Sebekidae) infecting softshell turtles, Apalone spp. (Testudines: Trionychidae) in the southeastern United States - Stephen S. Curran; Robin M. Overstreet; David E. Collins; George W. Benz (Systematic Parasitology, 2014)

The fundamental hominin niche in late Pleistocene Central Asia: a preliminary refugium model - Tyler A. Beeton; Michelle M. Glantz; Anna K. Trainer; Sayat S. Temirbekov; Robin M. Reich (Journal of Biogeography, 2014)
Aim We examine hominin presence in Central Asia during the late Pleistocene in order to identify the abiotic characteristics that best predict site distribution during interglacial and glacial periods. Our goal is to build a preliminary framework for climate‐mediated hominin dispersals in this understudied part of the Old World. Location Tajikistan, Uzbekistan. Methods We developed an ecological niche model using presence‐only data to explain the spatial relationship of abiotic variables and hominin locations ( n = 15) during glacial–interglacial transitions. The model was evaluated using the Cramér–von Mises goodness‐of‐fit statistic and empirical K ‐function. Results Hominin locations were spatially aggregated during both glacial and interglacial periods. Of the abiotic variables analysed on a small scale (30‐m resolution), only distance to water differed significantly between glacial and interglacial periods, although most locations were within 5 km of water. At a coarse scale (5‐km resolution), hominin locations appear to have been constrained by low temperatures during glacial periods, but not during interglacials. Main conclusions Hominin groups did not abandon Central Asia during colder periods. This suggests one of three possibly complementary scenarios: (1) late Pleistocene hominin groups had a more flexible behavioural repertoire than previously anticipated and were able to buffer climatic instability culturally; (2) our study area was not as hostile an environment as traditionally considered; and (3) the area examined here represents a refugium during late Pleistocene glaciations.

Introduction - Robin S. Waples (Conservation Biology, 2013)

Azithromycin Attenuates Fibroblast Growth Factors Induced Vascular Endothelial Growth Factor Via p38MAPK Signaling in Human Airway Smooth Muscle Cells - Anna Willems-Widyastuti; Bart M. Vanaudenaerde; Robin Vos; Ellen Dilisen; Stijn E. Verleden; Stéphanie I. Vleeschauwer; Annemie Vaneylen; Wolter J. Mooi; Willem I. Boer; Hari S. Sharma; Geert M. Verleden (Cell Biochemistry and Biophysics, 2013)

Dynamic coastal dune spit: the impact of morphological change on dune slacks at Whiteford Burrows, South Wales, UK - N. S. Robins; K. Pye; H. Wallace (Journal of Coastal Conservation, 2013)

Otitis media among high-risk populations: can probiotics inhibit Streptococcus pneumoniae colonisation and the risk of disease? - M. John; E. M. Dunne; P. V. Licciardi; C. Satzke; O. Wijburg; R. M. Robins-Browne; S. O’Leary (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Consistency Among Musculoskeletal Models: Caveat Utilitor - David W. Wagner; Vahagn Stepanyan; James M. Shippen; Matthew S. DeMers; Robin S. Gibbons; Brian J. Andrews; Graham H. Creasey; Gary S. Beaupre (Annals of Biomedical Engineering, 2013)

Overexpression of the Polycystin-1 C-Tail Enhances Sensitivity of M-1 Cells to Ouabain - Kyle Jansson; Brenda S. Magenheimer; Robin L. Maser; James P. Calvet; Gustavo Blanco (The Journal of Membrane Biology, 2013)

Pharmacokinetic interactions of CEP-1347 and atazanavir in HIV-infected patients - Qing Ma; Harris A. Gelbard; Sanjay B. Maggirwar; Stephen Dewhurst; Howard E. Gendelman; Derick R. Peterson; Robin DiFrancesco; Jill S. Hochreiter; Gene D. Morse; Giovanni Schifitto (Journal of NeuroVirology, 2013)

Modelled larval dispersal and measured gene flow: seascape genetics of the common cockle Cerastoderma edule in the southern Irish Sea - Ilaria Coscia; Peter E. Robins; Joanne S. Porter; Shelagh K. Malham; Joseph E. Ironside (Conservation Genetics, 2013)

Identifying transboundary aquifers in need of international resource management in the Southern African Development Community region - Jeff Davies; Nick S. Robins; John Farr; James Sorensen; Philip Beetlestone; Jude E. Cobbing (Hydrogeology Journal, 2013)

Peripheral tolerance and autoimmunity: lessons from in vivo imaging - Jordan Jacobelli; Robin S. Lindsay; Rachel S. Friedman (Immunologic Research, 2013)

Interactive effects of methylphenidate and alcohol on discrimination, conditioned place preference and motor coordination in C57BL/6J mice - William C. Griffin; Robin W. McGovern; Guinevere H. Bell; Patrick K. Randall; Lawrence D. Middaugh; Kennerly S. Patrick (Psychopharmacology, 2013)

Megacities and Large Urban Agglomerations in the Coastal Zone: Interactions Between Atmosphere, Land, and Marine Ecosystems - Roland von Glasow; Tim D. Jickells; Alexander Baklanov; Gregory R. Carmichael; Tom M. Church; Laura Gallardo; Claire Hughes; Maria Kanakidou; Peter S. Liss; Laurence Mee; Robin Raine; Purvaja Ramachandran; et al. (Ambio, 2013)

Evaluating Alternative Strategies for Minimizing Unintended Fitness Consequences of Cultured Individuals on Wild Populations - MARISSA L. BASKETT; ROBIN S. WAPLES (Conservation Biology, 2013)
Artificial propagation strategies often incur selection in captivity that leads to traits that are maladaptive in the wild. For propagation programs focused on production rather than demographic contribution to wild populations, effects on wild populations can occur through unintentional escapement or the need to release individuals into natural environments for part of their life cycle. In this case, 2 alternative management strategies might reduce unintended fitness consequences on natural populations: (1) reduce selection in captivity as much as possible to reduce fitness load (keep them similar), or (2) breed a separate population to reduce captive‐wild interactions as much as possible (make them different). We quantitatively evaluate these 2 strategies with a coupled demographic–genetic model based on Pacific salmon hatcheries that incorporates a variety of relevant processes and dynamics: selection in the hatchery relative to the wild, assortative mating based on the trait under selection, and different life cycle arrangements in terms of hatchery release, density dependence, natural selection, and reproduction. Model results indicate that, if natural selection only occurs between reproduction and captive release, the similar strategy performs better. However, if natural selection occurs between captive release and reproduction, the different and similar strategies present viable alternatives to reducing unintended fitness consequences because of the greater opportunity to purge maladaptive individuals. In this case, the appropriate approach depends on the feasibility of each strategy and the demographic goal (e.g., increasing natural abundance, or ensuring that a high proportion of natural spawners are naturally produced). In addition, the fitness effects of hatchery release are much greater if hatchery release occurs before (vs. after) density‐dependent interactions. Given the logistical challenges to achieving both the similar and different strategies, evaluation of not just the preferred strategy but also the consequences of failing to achieve the desired target is critical. Evaluación de Estrategias Alternativas para Minimizar las Consecuencias No Inesperadas en la Adecuación de Individuos Criados en Cautiverio sobre Poblaciones Silvestres

Advanced duodenal disease in familial adenomatous polyposis: how frequently should patients be followed up after successful therapy? - Damian C. Balmforth; Robin K. S. Phillips; Susan K. Clark (Familial Cancer, 2012)

Detecting population recovery using gametic disequilibrium-based effective population size estimates - David A. Tallmon; Robin S. Waples; Dave Gregovich; Michael K. Schwartz (Conservation Genetics Resources, 2012)

Therapeutic potential of MEK inhibition in acute myelogenous leukemia: rationale for “vertical” and “lateral” combination strategies - Maria Rosaria Ricciardi; Maria Cristina Scerpa; Paola Bergamo; Ludovica Ciuffreda; Maria Teresa Petrucci; Sabina Chiaretti; Simona Tavolaro; Maria Grazia Mascolo; Stephen L. Abrams; Linda S. Steelman; Twee Tsao; Antonio Marchetti; et al. (Journal of Molecular Medicine, 2012)

Genetic diversity in the Snake River sockeye salmon captive broodstock program as estimated from broodstock records - Steven T. Kalinowski; Donald M. Van Doornik; Christine C. Kozfkay; Robin S. Waples (Conservation Genetics, 2012)

Population structure of melon‐headed whales ( Peponocephala electra ) in the Hawaiian Archipelago: Evidence of multiple populations based on photo identification - Jessica M. Aschettino; Robin W. Baird; Daniel J. McSweeney; Daniel L. Webster; Gregory S. Schorr; Jessica L. Huggins; Karen K. Martien; Sabre D. Mahaffy; Kristi L. West (Marine Mammal Science, 2012)
Despite the presence of melon‐headed whales in tropical and subtropical waters worldwide, little is known about this species. To assess population structure in Hawai‘i, dedicated field efforts were undertaken from 2000 to 2009. Using only good quality photographs, there were 1,433 unique photo‐identified individuals, of which 1,046 were distinctive. Of these, 31.5% were seen more than once. Resighting data combined with social network analyses showed evidence of two populations—a smaller, resident population, seen exclusively off the northwest region of the island of Hawai‘i, and a larger population, seen throughout all the main Hawaiian Islands (hereafter the “main Hawaiian Islands” population). A Bayesian analysis examining the probability of movements of individuals between populations provided a posterior median dispersal rate of 0.0009/yr (95% CI = 0–0.0041), indicating the populations are likely demographically independent. Depth of encounters with the Hawai‘i Island resident population was significantly shallower (median = 381 m) than those with the main Hawaiian Islands population (median = 1,662 m). Resightings of individuals have occurred up to 22 yr apart for the Hawai‘i Island resident population and up to 13 yr apart for the main Hawaiian Islands population, suggesting long‐term residency to the islands for both populations.

Corrigendum - CLARE D. MARSDEN; ROSIE WOODROFFE; MICHAEL G. L. MILLS; J. WELDON MCNUTT; SCOTT CREEL; ROSEMARY GROOM; MASENGA EMMANUEL; SARAH CLEAVELAND; PIETER KAT; GREGORY S. A. RASMUSSEN; JOSHUA GINSBERG; ROBIN LINES; et al. (Molecular Ecology, 2012)

Popular misconceptions - ROBERT C. VRIJENHOEK; ROBIN S. WAPLES (Molecular Ecology, 2012)

Individual bumblebees vary in response to disturbance: a test of the defensive reserve hypothesis - J. M. Jandt; N. S. Robins; R. E. Moore; A. Dornhaus (Insectes Sociaux, 2012)

Tree growth and death in a tropical gallery forest in Brazil: understanding the relationships among size, growth, and survivorship for understory and canopy dominant species - Eduardo van den Berg; Robin Chazdon; Bruno S. Corrêa (Plant Ecology, 2012)

An Inverse Method for Determining Source Characteristics for Emergency Response Applications - A. C. Rudd; A. G. Robins; J. J. Lepley; S. E. Belcher (Boundary-Layer Meteorology, 2012)

Impact of Residual Stretch and Remodeling on Collagen Engagement in Healthy and Pulmonary Hypertensive Calf Pulmonary Arteries at Physiological Pressures - Lian Tian; Steven R. Lammers; Philip H. Kao; Joseph A. Albietz; Kurt R. Stenmark; H. Jerry Qi; Robin Shandas; Kendall S. Hunter (Annals of Biomedical Engineering, 2012)

Eddies as offshore foraging grounds for melon‐headed whales ( Peponocephala electra ) - Phoebe A. Woodworth; Gregory S. Schorr; Robin W. Baird; Daniel L. Webster; Daniel J. McSweeney; M. Bradley Hanson; Russel D. Andrews; Jeffrey J. Polovina (Marine Mammal Science, 2012)

Phylogenetic diversity and the functioning of ecosystems - Diane S. Srivastava; Marc W. Cadotte; A. Andrew M. MacDonald; Robin G. Marushia; Nicholas Mirotchnick (Ecology Letters, 2012)
Phylogenetic diversity ( PD ) describes the total amount of phylogenetic distance among species in a community. Although there has been substantial research on the factors that determine community PD , exploration of the consequences of PD for ecosystem functioning is just beginning. We argue that PD may be useful in predicting ecosystem functions in a range of communities, from single‐trophic to complex networks. Many traits show a phylogenetic signal, suggesting that PD can estimate the functional trait space of a community, and thus ecosystem functioning. Phylogeny also determines interactions among species, and so could help predict how extinctions cascade through ecological networks and thus impact ecosystem functions. Although the initial evidence available suggests patterns consistent with these predictions, we caution that the utility of PD depends critically on the strength of phylogenetic signals to both traits and interactions. We advocate for a synthetic approach that incorporates a deeper understanding of how traits and interactions are shaped by evolution, and outline key areas for future research. If these complexities can be incorporated into future studies, relationships between PD and ecosystem function bear promise in conceptually unifying evolutionary biology with ecosystem ecology.

Comparative changes in density and demography of large herbivores in the Masai Mara Reserve and its surrounding human-dominated pastoral ranches in Kenya - Nina Bhola; Joseph O. Ogutu; Hans-Peter Piepho; Mohamed Y. Said; Robin S. Reid; N. Thompson Hobbs; Han Olff (Biodiversity and Conservation, 2012)

Loads of housework? Biomechanical assessments of the upper limbs in women performing common household tasks - Pietro Apostoli; Emma Sala; Stefania Curti; Robin M. T. Cooke; Francesco S. Violante; Stefano Mattioli (International Archives of Occupational and Environmental Health, 2012)

A functional screen for recovery of 4′‐phosphopantetheinyl transferase and associated natural product biosynthesis genes from metagenome libraries - J. G. Owen; K. J. Robins; N. S. Parachin; D. F. Ackerley (Environmental Microbiology, 2012)
Summary The single‐module non‐ribosomal peptide synthetase BpsA from Streptomyces lavendulae has the unique ability to autonomously synthesize a coloured product (indigoidine) from a single substrate ( l ‐glutamine), conditional upon activation by a 4′‐phosphopantetheinyl transferase (PPTase) partner. We show that bpsA can be expressed in an entD PPTase gene deleted mutant of Escherichia coli to yield a sensitive reporter strain for recovery of PPTase genes from metagenome libraries. We also show that recombinant bpsA constructs, generated by substitution of the native peptidyl carrier protein domain followed by directed evolution to restore function, can be used to increase the diversity of PPTase genes recovered from a sample. As PPTases are essential for activation of non‐ribosomal peptide synthetase and polyketide synthase enzymes, they are frequently associated with secondary metabolite gene clusters. Nearly half of the PPTases recovered in our screening of two small‐insert soil metagenome libraries were genetically linked to recognizable secondary metabolite biosynthetic genes, demonstrating that PPTase‐targeting functional screens can be used for efficient recovery of natural product gene clusters from metagenome libraries. The plasticity and portability of bpsA reporter genes can potentially be exploited to maximize recovery and expression of PPTase‐bearing clones in a wide range of hosts.

The last glacial cycle: transient simulations with an AOGCM - Robin S. Smith; Jonathan Gregory (Climate Dynamics, 2012)

Cervical Cancer Control: Deaf and Hearing Women’s Response to an Educational Video - Catherine S. Yao; Erin L. Merz; Melanie Nakaji; Kadie M. Harry; Vanessa L. Malcarne; Georgia Robins Sadler (Journal of Cancer Education, 2012)

Analysis of the complete DNA sequence of rice tungro bacilliform virus from southern India indicates it to be a product of recombination - S. Sharma; R. Rabindran; S. Robin; I. Dasgupta (Archives of Virology, 2011)

Movements of two satellite‐tagged pygmy killer whales ( Feresa attenuata ) off the island of Hawai‘i - Robin W. Baird; Gregory S. Schorr; Daniel L. Webster; Dan J. McSweeney; M. Bradley Hanson; Russel D. Andrews (Marine Mammal Science, 2011)

Medium-term fertilization of grassland plant communities masks plant species-linked effects on soil microbial community structure - Stavros D. Veresoglou; Andreas P. Mamolos; Barry Thornton; Olga K. Voulgari; Robin Sen; Demetrios S. Veresoglou (Plant and Soil, 2011)

16S rRNA Gene Sequence Analysis of Drinking Water Using RNA and DNA Extracts as Targets for Clone Library Development - Randy P. Revetta; Robin S. Matlib; Jorge. W. Santo Domingo (Current Microbiology, 2011)

Orchardgrass (Dactylis glomerata L.) EST and SSR marker development, annotation, and transferability - B. Shaun Bushman; Steve R. Larson; Metin Tuna; Mark S. West; Alvaro G. Hernandez; Deepika Vullaganti; George Gong; Joseph G. Robins; Kevin B. Jensen; Jyothi Thimmapuram (Theoretical and Applied Genetics, 2011)

Genetic discontinuity among regional populations of Lophelia pertusa in the North Atlantic Ocean - Cheryl L. Morrison; Steve W. Ross; Martha S. Nizinski; Sandra Brooke; Johanna Järnegren; Rhian G. Waller; Robin L. Johnson; Tim L. King (Conservation Genetics, 2011)

Understanding and Estimating Effective Population Size for Practical Application in Marine Species Management - MATTHEW P. HARE; LEONARD NUNNEY; MICHAEL K. SCHWARTZ; DANIEL E. RUZZANTE; MARTHA BURFORD; ROBIN S. WAPLES; KRISTEN RUEGG; FRISO PALSTRA (Conservation Biology, 2011)
Effective population size (N e ) determines the strength of genetic drift in a population and has long been recognized as an important parameter for evaluating conservation status and threats to genetic health of populations. Specifically, an estimate of N e is crucial to management because it integrates genetic effects with the life history of the species, allowing for predictions of a population's current and future viability. Nevertheless, compared with ecological and demographic parameters, N e has had limited influence on species management, beyond its application in very small populations. Recent developments have substantially improved N e estimation; however, some obstacles remain for the practical application of N e estimates. For example, the need to define the spatial and temporal scale of measurement makes the concept complex and sometimes difficult to interpret. We reviewed approaches to estimation of N e over both long‐term and contemporary time frames, clarifying their interpretations with respect to local populations and the global metapopulation. We describe multiple experimental factors affecting robustness of contemporary N e estimates and suggest that different sampling designs can be combined to compare largely independent measures of N e for improved confidence in the result. Large populations with moderate gene flow pose the greatest challenges to robust estimation of contemporary N e and require careful consideration of sampling and analysis to minimize estimator bias. We emphasize the practical utility of estimating N e by highlighting its relevance to the adaptive potential of a population and describing applications in management of marine populations, where the focus is not always on critically endangered populations. Two cases discussed include the mechanisms generating N e estimates many orders of magnitude lower than census N in harvested marine fishes and the predicted reduction in N e from hatchery‐based population supplementation.

Colorectal cancer: no longer the issue in familial adenomatous polyposis? - Daniel C. Gibbons; Ashish Sinha; Robin K. S. Phillips; Susan K. Clark (Familial Cancer, 2011)

Interacting Effects of Phenotypic Plasticity and Evolution on Population Persistence in a Changing Climate - THOMAS E. REED; DANIEL E. SCHINDLER; ROBIN S. WAPLES (Conservation Biology, 2011)
Climate change affects individual organisms by altering development, physiology, behavior, and fitness, and populations by altering genetic and phenotypic composition, vital rates, and dynamics . We sought to clarify how selection, phenotypic plasticity, and demography are linked in the context of climate change . On the basis of theory and results of recent empirical studies of plants and animals, we believe the ecological and evolutionary issues relevant to population persistence as climate changes are the rate, type, magnitude, and spatial pattern of climate‐induced abiotic and biotic change; generation time and life history of the organism; extent and type of phenotypic plasticity; amount and distribution of adaptive genetic variation across space and time; dispersal potential; and size and connectivity of subpopulations . An understanding of limits to plasticity and evolutionary potential across traits, populations, and species and feedbacks between adaptive and demographic responses is lacking . Integrated knowledge of coupled ecological and evolutionary mechanisms will increase understanding of the resilience and probabilities of persistence of populations and species .

Clostridium perfringens bacteriophages ΦCP39O and ΦCP26F: genomic organization and proteomic analysis of the virions - Bruce S. Seal; Derrick E. Fouts; Mustafa Simmons; Johnna K. Garrish; Robin L. Kuntz; Rebekah Woolsey; Kathleen M. Schegg; Andrew M. Kropinski; Hans-W. Ackermann; Gregory R. Siragusa (Archives of Virology, 2011)

Early detection of population fragmentation using linkage disequilibrium estimation of effective population size - Phillip R. England; Gordon Luikart; Robin S. Waples (Conservation Genetics, 2010)

Trait similarity, shared ancestry and the structure of neighbourhood interactions in a subtropical wet forest: implications for community assembly - María Uriarte; Nathan G. Swenson; Robin L. Chazdon; Liza S. Comita; W. John Kress; David Erickson; Jimena Forero‐Montaña; Jess K. Zimmerman; Jill Thompson (Ecology Letters, 2010)
Ecology Letters (2010) 13: 1503–1514 Abstract The phylogenetic structure and distribution of functional traits in a community can provide insights into community assembly processes. However, these insights are sensitive to the spatial scale of analysis. Here, we use spatially explicit, neighbourhood models of tree growth and survival for 19 tree species, a highly resolved molecular phylogeny and information on eight functional traits to quantify the relative efficacy of functional similarity and shared ancestry in describing the effects of spatial interactions between tree species on demographic rates. We also assess the congruence of these results with observed phylogenetic and functional structure in the neighbourhoods of live and dead trees. We found strong support for models in which the effects of spatial neighbourhood interactions on tree growth and survival were scaled to species‐specific mean functional trait values (e.g., wood specific gravity, leaf succulence and maximum height) but not to phylogenetic distance. The weak phylogenetic signal in functional trait data allowed us to independently interpret the static neighbourhood functional and phylogenetic patterns. We observed greater functional trait similarity in the neighbourhoods of live trees relative to those of dead trees suggesting that environmental filtering is the major force structuring this tree community at this scale while competitive interactions play a lesser role.

Divergent composition but similar function of soil food webs of individual plants: plant species and community effects - T. M. Bezemer; M. T. Fountain; J. M. Barea; S. Christensen; S. C. Dekker; H. Duyts; R. van Hal; J. A. Harvey; K. Hedlund; M. Maraun; J. Mikola; A. G. Mladenov; et al. (Ecology, 2010)
Soils are extremely rich in biodiversity, and soil organisms play pivotal roles in supporting terrestrial life, but the role that individual plants and plant communities play in influencing the diversity and functioning of soil food webs remains highly debated. Plants, as primary producers and providers of resources to the soil food web, are of vital importance for the composition, structure, and functioning of soil communities. However, whether natural soil food webs that are completely open to immigration and emigration differ underneath individual plants remains unknown. In a biodiversity restoration experiment we first compared the soil nematode communities of 228 individual plants belonging to eight herbaceous species. We included grass, leguminous, and non‐leguminous species. Each individual plant grew intermingled with other species, but all plant species had a different nematode community. Moreover, nematode communities were more similar when plant individuals were growing in the same as compared to different plant communities, and these effects were most apparent for the groups of bacterivorous, carnivorous, and omnivorous nematodes. Subsequently, we analyzed the composition, structure, and functioning of the complete soil food webs of 58 individual plants, belonging to two of the plant species, Lotus corniculatus (Fabaceae) and Plantago lanceolata (Plantaginaceae). We isolated and identified more than 150 taxa/groups of soil organisms. The soil community composition and structure of the entire food webs were influenced both by the species identity of the plant individual and the surrounding plant community. Unexpectedly, plant identity had the strongest effects on decomposing soil organisms, widely believed to be generalist feeders. In contrast, quantitative food web modeling showed that the composition of the plant community influenced nitrogen mineralization under individual plants, but that plant species identity did not affect nitrogen or carbon mineralization or food web stability. Hence, the composition and structure of entire soil food webs vary at the scale of individual plants and are strongly influenced by the species identity of the plant. However, the ecosystem functions these food webs provide are determined by the identity of the entire plant community.

How Do Cancer Patients Navigate the Public Information Environment? Understanding Patterns and Motivations for Movement Among Information Sources - Rebekah H. Nagler; Anca Romantan; Bridget J. Kelly; Robin S. Stevens; Stacy W. Gray; Shawnika J. Hull; A. Susana Ramirez; Robert C. Hornik (Journal of Cancer Education, 2010)

Familial adenomatous polyposis (FAP) and gender. Does gender influence the genetic transmission of FAP? - Eriberto Farinella; Ramawad Soobrah; Robin K. S. Phillips; Susan K. Clark (Familial Cancer, 2010)

In-Street Wind Direction Variability in the Vicinity of a Busy Intersection in Central London - Ahmed A. Balogun; Alison S. Tomlin; Curtis R. Wood; Janet F. Barlow; Stephen E. Belcher; Robert J. Smalley; Justin J. N. Lingard; Sam J. Arnold; Adrian Dobre; Alan G. Robins; Damien Martin; Dudley E. Shallcross (Boundary-Layer Meteorology, 2010)

A framework for evaluating regional-scale numerical photochemical modeling systems - Robin Dennis; Tyler Fox; Montse Fuentes; Alice Gilliland; Steven Hanna; Christian Hogrefe; John Irwin; S. Trivikrama Rao; Richard Scheffe; Kenneth Schere; Douw Steyn; Akula Venkatram (Environmental Fluid Mechanics, 2010)

Longevity mutants do not establish any “new science” of ageing - Robin Holliday; Suresh I. S. Rattan (Biogerontology, 2010)

High‐grading bias: subtle problems with assessing power of selected subsets of loci for population assignment - ROBIN S. WAPLES (Molecular Ecology, 2010)
Recognition of the importance of cross‐validation (‘any technique or instance of assessing how the results of a statistical analysis will generalize to an independent dataset ’; Wiktionary, en.wiktionary.org) is one reason that the U.S. Securities and Exchange Commission requires all investment products to carry some variation of the disclaimer, ‘Past performance is no guarantee of future results.’ Even a cursory examination of financial behaviour, however, demonstrates that this warning is regularly ignored, even by those who understand what an independent dataset is. In the natural sciences, an analogue to predicting future returns for an investment strategy is predicting power of a particular algorithm to perform with new data. Once again, the key to developing an unbiased assessment of future performance is through testing with independent data—that is, data that were in no way involved in developing the method in the first place. A ‘gold‐standard’ approach to cross‐validation is to divide the data into two parts, one used to develop the algorithm, the other used to test its performance. Because this approach substantially reduces the sample size that can be used in constructing the algorithm, researchers often try other variations of cross‐validation to accomplish the same ends. As illustrated by Anderson in this issue of Molecular Ecology Resources , however, not all attempts at cross‐validation produce the desired result. Anderson used simulated data to evaluate performance of several software programs designed to identify subsets of loci that can be effective for assigning individuals to population of origin based on multilocus genetic data. Such programs are likely to become increasingly popular as researchers seek ways to streamline routine analyses by focusing on small sets of loci that contain most of the desired signal. Anderson found that although some of the programs made an attempt at cross‐validation, all failed to meet the ‘gold standard’ of using truly independent data and therefore produced overly optimistic assessments of power of the selected set of loci—a phenomenon known as ‘high grading bias.’

Impacts of the invasive plant Fallopia japonica (Houtt.) on plant communities and ecosystem processes - Anna G. Aguilera; Peter Alpert; Jeffrey S. Dukes; Robin Harrington (Biological Invasions, 2010)

Estimating the Density of Honeybee Colonies across Their Natural Range to Fill the Gap in Pollinator Decline Censuses - RODOLFO JAFFÉ; VINCENT DIETEMANN; MIKE H. ALLSOPP; CECILIA COSTA; ROBIN M. CREWE; RAFFAELE DALL’OLIO; PILAR DE LA RÚA; MOGBEL A. A. EL‐NIWEIRI; INGEMAR FRIES; NIKOLA KEZIC; MICHAEL S. MEUSEL; ROBERT J. PAXTON; et al. (Conservation Biology, 2010)
Although pollinator declines are a global biodiversity threat, the demography of the western honeybee ( Apis mellifera ) has not been considered by conservationists because it is biased by the activity of beekeepers. To fill this gap in pollinator decline censuses and to provide a broad picture of the current status of honeybees across their natural range, we used microsatellite genetic markers to estimate colony densities and genetic diversity at different locations in Europe, Africa, and central Asia that had different patterns of land use. Genetic diversity and colony densities were highest in South Africa and lowest in Northern Europe and were correlated with mean annual temperature. Confounding factors not related to climate, however, are also likely to influence genetic diversity and colony densities in honeybee populations. Land use showed a significantly negative influence over genetic diversity and the density of honeybee colonies over all sampling locations. In Europe honeybees sampled in nature reserves had genetic diversity and colony densities similar to those sampled in agricultural landscapes, which suggests that the former are not wild but may have come from managed hives. Other results also support this idea: putative wild bees were rare in our European samples, and the mean estimated density of honeybee colonies on the continent closely resembled the reported mean number of managed hives. Current densities of European honeybee populations are in the same range as those found in the adverse climatic conditions of the Kalahari and Saharan deserts, which suggests that beekeeping activities do not compensate for the loss of wild colonies. Our findings highlight the importance of reconsidering the conservation status of honeybees in Europe and of regarding beekeeping not only as a profitable business for producing honey, but also as an essential component of biodiversity conservation.

Eco‐evolutionary dynamics: fluctuations in population growth rate reduce effective population size in chinook salmon - Robin S. Waples; David W. Jensen; Michelle McClure (Ecology, 2010)
We empirically assess the relationship between population growth rate (λ, a parameter central to ecology) and effective population size ( N e , a key parameter in evolutionary biology). Recent theoretical and numerical studies indicate that in semelparous species with variable age at maturity (such as Pacific salmon, many monocarpic plants, and various other species), differences in mean reproductive success among individuals reproducing in different years leads to variation in λ, and this in turn can reduce N e . However, this phenomenon has received little empirical evaluation. We examined time series of abundance data for 56 populations of chinook salmon ( Onchorhynchus tshawytscha ) from the northwestern United States and compared N e (calculated from demographic data) with the total number of spawners each generation ( N T ). Important results include: (1) The mean multigenerational ratio xÑ e / xÑ T was 0.64 (median = 0.67), indicating that annual variation in λ reduces effective population size in chinook salmon by an average of ∼35%. These reductions are independent of, and in addition to, factors that reduce N e within individual cohorts (uneven sex ratio and greater‐than‐random variance in reproductive success). (2) The coefficient of variation of λ was the most important factor associated with reductions in N e , explaining up to two‐thirds of the variance in xÑ e / xÑ T . (3) Within individual generations, N e was lower when there was a negative correlation between annual N i and λ, i.e., when relatively few breeders produced relatively high numbers of offspring. Our results thus highlight an important and little‐studied eco‐evolutionary trade‐off: density‐dependent compensation has generally favorable ecological consequences (promoting stability and long‐term viability) but incurs an evolutionary cost (reducing N e because a few individuals make a disproportionate genetic contribution). (4) For chinook salmon, Nx^ eH (an estimator based on the harmonic mean number of breeders per year) is generally a good proxy for true N e and requires much less data to calculate.

Neglect of Genetic Diversity in Implementation of the Convention on Biological Diversity - LINDA LAIKRE; FRED W. ALLENDORF; LAUREL C. ARONER; C. SCOTT BAKER; DAVID P. GREGOVICH; MICHAEL M. HANSEN; JENNIFER A. JACKSON; KATHERINE C. KENDALL; KEVIN McKELVEY; MAILE C. NEEL; ISABELLE OLIVIERI; NILS RYMAN; et al. (Conservation Biology, 2010)

Release from bats: genetic distance and sensoribehavioural regression in the Pacific field cricket, Teleogryllus oceanicus - James H. Fullard; Hannah M. ter Hofstede; John M. Ratcliffe; Gerald S. Pollack; Gian S. Brigidi; Robin M. Tinghitella; Marlene Zuk (The Science of Nature, 2010)

Cell yields and fermentation responses of a Salmonella Typhimurium poultry isolate at different dilution rates in an anaerobic steady state continuous culture - Kingsley D. Dunkley; Todd R. Callaway; Corliss O’Bryan; Megan M. Kundinger; Claudia S. Dunkley; Robin C. Anderson; David J. Nisbet; P. G. Crandall; Steven C. Ricke (Antonie van Leeuwenhoek, 2009)

A Review of Climate‐Change Adaptation Strategies for Wildlife Management and Biodiversity Conservation - JONATHAN R. MAWDSLEY; ROBIN O’MALLEY; DENNIS S. OJIMA (Conservation Biology, 2009)
The scientific literature contains numerous descriptions of observed and potential effects of global climate change on species and ecosystems. In response to anticipated effects of climate change, conservation organizations and government agencies are developing “adaptation strategies” to facilitate the adjustment of human society and ecological systems to altered climate regimes. We reviewed the literature and climate‐change adaptation plans that have been developed in United States, Canada, England, México, and South Africa and found 16 general adaptation strategies that relate directly to the conservation of biological diversity. These strategies can be grouped into four broad categories: land and water protection and management; direct species management; monitoring and planning; and law and policy. Tools for implementing these strategies are similar or identical to those already in use by conservationists worldwide (land and water conservation, ecological restoration, agrienvironment schemes, species translocation, captive propagation, monitoring, natural resource planning, and legislation/regulation). Although our review indicates natural resource managers already have many tools that can be used to address climate‐change effects, managers will likely need to apply these tools in novel and innovative ways to meet the unprecedented challenges posed by climate change.

Allopatric origin of cryptic butterfly species that were discovered feeding on distinct host plants in sympatry - CAROLYN S. McBRIDE; ROBIN VAN VELZEN; TORBEN B. LARSEN (Molecular Ecology, 2009)
Surveys of tropical insects are increasingly uncovering cryptic species – morphologically similar yet reproductively isolated taxa once thought to comprise a single interbreeding entity. The vast majority of such species are described from a single location. This leaves us with little information on geographic range and intraspecific variation and limits our ability to infer the forces responsible for generating such diversity. For example, in herbivorous and parasitic insects, multiple specialists are often discovered within what were thought to be single more generalized species. Host shifts are likely to have contributed to speciation in these cases. But when and where did those shifts occur, and were they facilitated by geographic isolation? We attempted to answer these questions for two cryptic species within the butterfly Cymothoe egesta that were recently discovered on different host plants in central Cameroon. We first used mtDNA markers to separate individuals collected on the two hosts within Cameroon and then extended our analysis to incorporate individuals collected across the entire pan‐Afrotropical range of the original taxon. To our surprise, we found that the species are almost entirely allopatric, dividing the original range and overlapping only in the narrow zone of West‐Central Africa where they were first discovered in sympatry. This finding, combined with analyses of genetic variation within each butterfly species, strongly suggests that speciation occurred in allopatry, probably during the Pleistocene. We discuss the implications of our results for understanding speciation among other cryptic species recently discovered in the tropics and argue that more work is needed on geographic patterns and host usage in such taxa.

Sex change and the genetic structure of marine fish populations - Julien Chopelet; Robin S Waples; Stefano Mariani (Fish and Fisheries, 2009)
The interaction between environmental forces and dispersal characteristics is largely responsible for the patterns of population structure in marine fish. Yet, crucial gaps in knowledge on life‐histories and the relative contributions of numerous environmental factors still hinder a thorough understanding of marine population connectivity. One life‐history trait so far overlooked by most fish population geneticists is sequential hermaphroditism, whereby individuals first mature as one sex and later in life reverse into the other sex. Population genetic theory predicts that sex‐changing fish will present a higher potential for more spatially structured populations than gonochoristic species, as a result of their naturally skewed sex ratio, which is expected to reduce effective population size and hence increase genetic drift. We gathered published data on genetic population structure in marine fish, as summarized by the popular F ST index, and – after controlling for several potentially confounding factors – we tested the hypothesis that sex‐changing species are more genetically structured than gonochoristic ones. Although we found no evidence to support the theoretical expectations, our results suggest new working hypotheses that can stimulate new research avenues at the intersection between physiology, genetics and fisheries science.

Military uses of groundwater: a driver of innovation? - N. S. Robins; E. P. F. Rose (Hydrogeology Journal, 2009)

Site fidelity and association patterns of a rare species: Pygmy killer whales ( Feresa attenuata ) in the main Hawaiian Islands - Daniel J. McSweeney; Robin W. Baird; Sabre D. Mahaffy; Daniel L. Webster; Gregory S. Schorr (Marine Mammal Science, 2009)
Most of what we know about cetacean biology and ecology comes from studies of relatively common species. Despite their distribution throughout the tropics and sub‐tropics, pygmy killer whales ( Feresa attenuata ) are rare throughout their range and are one of the most poorly‐known species of odontocetes. During a 22‐yr study of short‐finned pilot whales ( Globicephala macrorhynchus ) off the island of Hawai‘i, we opportunistically photo‐identified pygmy killer whales whenever encountered. As part of a directed multi‐species study throughout the main Hawaiian Islands from 2000 through 2007, we also photo‐identified individuals and obtained information on habitat use and behavior. This species was extremely uncommon (representing only 1.2% of odontocete sightings in directed efforts). Given the low encounter rates, assessing trends of this population cannot be feasibly done with line‐transect surveys. Despite their rarity, 80% of the distinctive individuals within groups documented off the island of Hawai‘i were seen on multiple occasions, individuals were resighted over periods of up to 21 yr, and there was evidence of year‐round use of the area. Association analyses indicate stable long‐term associations in mixed‐sex groups. High resighting rates indicate a small population of island‐associated individuals that may be at risk from anthropogenic impacts.

Prospects for tropical forest biodiversity in a human‐modified world - Toby A. Gardner; Jos Barlow; Robin Chazdon; Robert M. Ewers; Celia A. Harvey; Carlos A. Peres; Navjot S. Sodhi (Ecology Letters, 2009)
The future of tropical forest biodiversity depends more than ever on the effective management of human‐modified landscapes, presenting a daunting challenge to conservation practitioners and land use managers. We provide a critical synthesis of the scientific insights that guide our understanding of patterns and processes underpinning forest biodiversity in the human‐modified tropics, and present a conceptual framework that integrates a broad range of social and ecological factors that define and contextualize the possible future of tropical forest species. A growing body of research demonstrates that spatial and temporal patterns of biodiversity are the dynamic product of interacting historical and contemporary human and ecological processes. These processes vary radically in their relative importance within and among regions, and have effects that may take years to become fully manifest. Interpreting biodiversity research findings is frequently made difficult by constrained study designs, low congruence in species responses to disturbance, shifting baselines and an over‐dependence on comparative inferences from a small number of well studied localities. Spatial and temporal heterogeneity in the potential prospects for biodiversity conservation can be explained by regional differences in biotic vulnerability and anthropogenic legacies, an ever‐tighter coupling of human‐ecological systems and the influence of global environmental change. These differences provide both challenges and opportunities for biodiversity conservation. Building upon our synthesis we outline a simple adaptive‐landscape planning framework that can help guide a new research agenda to enhance biodiversity conservation prospects in the human‐modified tropics.

Prevalence and Acquisition of the Genes for Zoocin A and Zoocin A Resistance in Streptococcus equi subsp. zooepidemicus - Amy S. Gargis; Anna-Lee D. O’Rourke; Gary L. Sloan; Robin S. Simmonds (Journal of Molecular Evolution, 2009)

Effects of the Dicarboxylic Acids Malate and Fumarate on E. coli O157:H7 and Salmonella enterica Typhimurium Populations in Pure Culture and in Mixed Ruminal Microorganism Fermentations - David J. Nisbet; Todd R. Callaway; T. S. Edrington; Robin C. Anderson; N. Krueger (Current Microbiology, 2009)

Modelling evolutionary processes in small populations: not as ideal as you think - ROBIN S. WAPLES; JAMES R. FAULKNER (Molecular Ecology, 2009)
Evolutionary processes are routinely modelled using ‘ideal’ Wright–Fisher populations of constant size N in which each individual has an equal expectation of reproductive success. In a hypothetical ideal population, variance in reproductive success ( V k ) is binomial and effective population size ( N e ) = N . However, in any actual implementation of the Wright–Fisher model (e.g., in a computer), V k is a random variable and its realized value in any given replicate generation ( ) only rarely equals the binomial variance. Realized effective size ( ) thus also varies randomly in modelled ideal populations, and the consequences of this have not been adequately explored in the literature. Analytical and numerical results show that random variation in and can seriously distort analyses that evaluate precision or otherwise depend on the assumption that is constant. We derive analytical expressions for Var( V k ) [4(2 N – 1)( N – 1)/ N 3 ] and Var( N e ) [ N ( N – 1)/(2 N – 1) ≈ N /2] in modelled ideal populations and show that, for a genetic metric G = f ( N e ), Var(Ĝ) has two components: Var Gene (due to variance across replicate samples of genes, given a specific ) and Var Demo (due to variance in ). Var(Ĝ) is higher than it would be with constant N e = N , as implicitly assumed by many standard models. We illustrate this with empirical examples based on F (standardized variance of allele frequency) and r 2 (a measure of linkage disequilibrium). Results demonstrate that in computer models that track multilocus genotypes, methods of replication and data analysis can strongly affect consequences of variation in . These effects are more important when sampling error is small (large numbers of individuals, loci and alleles) and with relatively small populations (frequently modelled by those interested in conservation).

Spatial scales of variance in abundance of intertidal species: effects of region, dispersal mode, and trophic level - Michael T. Burrows; Robin Harvey; Linda Robb; Elvira S. Poloczanska; Nova Mieszkowska; Pippa Moore; Rebecca Leaper; Stephen J. Hawkins; Lisandro Benedetti-Cecchi (Ecology, 2009)
Determination of the pattern of variation in population abundance among spatial scales offers much insight into the potential regulating factors. Here we offer a method of quantifying spatial variance on a range of scales derived by sampling of irregularly spaced sites along complex coastlines. We use it to determine whether the nature of spatial variance depends on the trophic level or the mode of dispersal of the species involved and the role of the complexity of the underlying habitat. A least‐cost distance model was used to determine distances by sea between all pairs of sites. Ordination of this distance matrix using multidimensional scaling allowed estimation of variance components with hierarchical ANOVA at nested spatial scales using spatial windows. By repeatedly moving these spatial windows and using a second set of spatial scales, average variance scale functions were derived for 50+ species in the UK rocky intertidal. Variance spectra for most species were well described by the inverse power law (1/ f β ) for noise spectra, with values for the exponent ranging from 0 to 1.1. At higher trophic levels (herbivores and carnivores), those species with planktonic dispersal had significantly higher β values, indicating greater large‐ than small‐scale variability, as did those on simpler coastlines (southwestern England and Wales vs. western Scotland). Average abundance and proportional incidence of species had the strongest influence on β values, with those of intermediate abundance and incidence having much greater large‐scale variance (β ≈ 0.5) than rare or ubiquitous species (β ≈ 0).

Physical mapping of rDNA and heterochromatin in chromosomes of 16 Coffea species: A revised view of species differentiation - P. Hamon; S. Siljak-Yakovlev; S. Srisuwan; O. Robin; V. Poncet; S. Hamon; A. de Kochko (Chromosome Research, 2009)

Population structure of island-associated dolphins: Evidence from photo-identification of common bottlenose dolphins ( Tursiops truncatus ) in the main Hawaiian Islands - Robin W. Baird; Antoinette M. Gorgone; Daniel J. McSweeney; Allan D. Ligon; Mark H. Deakos; Daniel L. Webster; Gregory S. Schorr; Karen K. Martien; Dan R. Salden; Sabre D. Mahaffy (Marine Mammal Science, 2009)

Trait identification and QTL validation for reproductive stage drought resistance in rice using selective genotyping of near flowering RILs - M. Subashri; S. Robin; K. K. Vinod; S. Rajeswari; K. Mohanasundaram; T. S. Raveendran (Euphytica, 2009)

Long-Term Tsunami Data Archive Supports Tsunami Forecast, Warning, Research, and Mitigation - Paula K. Dunbar; Kelly J. Stroker; Vanita R. Brocko; Jesse D. Varner; Susan J. McLean; Lisa A. Taylor; Barry W. Eakins; Kelly S. Carignan; Robin R. Warnken (Pure and Applied Geophysics, 2008)

Integrating genetic data into management of marine resources: how can we do it better? - Robin S Waples; André E Punt; Jason M Cope (Fish and Fisheries, 2008)
Molecular genetic data have found widespread application in the identification of population and conservation units for aquatic species. However, integration of genetic information into actual management has been slow, and explicit and quantitative inclusion of genetic data into fisheries models is rare. In part, this reflects the inherent difficulty in using genetic markers to draw inferences about demographic independence, which is generally the information of the greatest short‐term interest to fishery managers. However, practical management constraints, institutional structures and communication issues have also contributed to the lack of integration. This paper identifies some of the organizational, conceptual and technical barriers that have hampered full use of genetics data in stock assessment and hence fishery management and outlines how such use could be enhanced.

Editorial - Lorenz Hauser; Robin S. Waples; Gary R. Carvalho (Fish and Fisheries, 2008)

Genomic differences between Campylobacter jejuni isolates identify surface membrane and flagellar function gene products potentially important for colonizing the chicken intestine - Kelli L. Hiett; Alain Stintzi; Tracy M. Andacht; Robin L. Kuntz; Bruce S. Seal (Functional & Integrative Genomics, 2008)

Available instruments for measurement of psychosocial factors in the work environment - Maria Carla Tabanelli; Marco Depolo; Robin M. T. Cooke; Guido Sarchielli; Roberta Bonfiglioli; Stefano Mattioli; Francesco S. Violante (International Archives of Occupational and Environmental Health, 2008)

Factors influencing anthropogenic carbon dioxide uptake in the North Atlantic in models of the ocean carbon cycle - Robin S. Smith; Jochem Marotzke (Climate Dynamics, 2008)

Dormancy and longevity of annual ryegrass (Lolium rigidum) as affected by soil type, depth, rainfall, and duration of burial - Sandeep Narwal; Brian M. Sindel; Robin S. Jessop (Plant and Soil, 2008)

Maintenance of cyanotoxin production by cryopreserved cyanobacteria in the New Zealand culture collection - Susanna A. Wood; Lesley L. Rhodes; Serean L. Adams; Janet E. Adamson; Kirsty F. Smith; John F. Smith; H. Robin Tervit; S. Craig Cary (New Zealand Journal of Marine and Freshwater Research, 2008)
A culture collection of freshwater planktonic and benthic cyanobacteria collected from sites across New Zealand has been established at the Cawthron Institute, Nelson, New Zealand. Limited resources led to uncertainty regarding the long‐term maintenance of this collection. The present study demonstrates cryopreservation to be a viable method for long‐term storage of cyanobacteria. Seventeen of 20 strains evaluated were successfully cryopreserved using the permeating cryopreservation agent dimethyl sulfoxide (Me 2 SO), at a final concentration of 15% (v/v). Cyanotoxin analysis was undertaken on selected strains known to produce microcystins, nodularin, anatoxin‐a, and saxitoxins. All strains retained their ability to produce these toxins following cryopreservation.

The metal binding site of zoocin A - Yinghua Chen; Robin S. Simmonds; Gary L. Sloan; Russell Timkovich (JBIC Journal of Biological Inorganic Chemistry, 2008)

Evaluation of distributed recharge in an upland semi-arid karst system: the West Bank Mountain Aquifer, Middle East - A. G. Hughes; M. M. Mansour; N. S. Robins (Hydrogeology Journal, 2008)

Reproductive strategy of an invasive thistle: effects of adults on seedling survival - Robin G. Marushia; Jodie S. Holt (Biological Invasions, 2008)

Legal Viability, Societal Values, and SPOIR: Response to D'Elia et al. - ROBIN S. WAPLES; PETER B. ADAMS; JAMES BOHNSACK; BARBARA L. TAYLOR (Conservation Biology, 2008)

Site fidelity and association patterns in a deep‐water dolphin: Rough‐toothed dolphins ( Steno bredanensis ) in the Hawaiian Archipelago - Robin W. Baird; Daniel L. Webster; Sabre D. Mahaffy; Daniel J. McSweeney; Gregory S. Schorr; Allan D. Ligon (Marine Mammal Science, 2008)
In the Pacific, rough‐toothed dolphins ( Steno bredanensis ) are typically found in the open ocean and in deep waters around oceanic islands. We examined habitat use, site fidelity, movements, and association patterns of this species in the main Hawaiian Islands. Sighting rates were highest in depths >1,500 m. There were frequent within‐ and between‐year resightings off the island of Hawai'i, indicating a small population size with high site fidelity. Resighting rates were lower off Kaua'i/Ni'ihau, indicating a larger population size, but with some site fidelity. Two individuals were documented moving from Kaua'i to Hawai'i, a distance of 480 km, but were not seen to associate with dolphins off Hawai'i. Observed movements were consistent with at most 2% dispersal per year between these two areas. Differences in group sizes, habitat use, and behavior imply that movements among the islands may be limited. Little is known about the diet of rough‐toothed dolphins in Hawai'i, but they are thought to feed primarily on near‐surface species. High fidelity to deep‐water areas off the island of Hawai'i likely reflects an increase in the predictability of prey associated with upwelling due to the island mass effect, wind stress curl and cyclonic eddies that form off the island.

Diel variation in beaked whale diving behavior - Robin W. Baird; Daniel L. Webster; Gregory S. Schorr; Daniel J. McSweeney; Jay Barlow (Marine Mammal Science, 2008)
We investigate diel variation in beaked whale diving behavior using data from time–depth recorders deployed on six Blainville's ( Mesoplodon densirostris) (255 h) and two Cuvier's ( Ziphius cavirostris ) (34 h) beaked whales. Deep foraging dives (>800 m) occurred at similar rates during the day and night for Blainville's beaked whales, and there were no significant diel differences in ascent rates, descent rates, or mean or maximum depths or durations for deep dives. Dive to mid‐water depths (100–600 m) occurred significantly more often during the day (mean = 1.59 h −1 ) than at night (mean = 0.26 h −1 ). Series of progressively shallower “bounce” dives were only documented to follow the deep, long dives made during the day; at night whales spent more time in shallow ( Orcinus orca ).

False killer whales ( Pseudorca crassidens ) around the main Hawaiian Islands: Long‐term site fidelity, inter‐island movements, and association patterns - Robin W. Baird; Antoinette M. Gorgone; Daniel J. McSweeney; Daniel L. Webster; Dan R. Salden; Mark H. Deakos; Allan D. Ligon; Gregory S. Schorr; Jay Barlow; Sabre D. Mahaffy (Marine Mammal Science, 2008)
Despite their world‐wide distribution throughout the tropics and subtropics, false killer whales ( Pseudorca crassidens ) are one of the lesser‐known large odontocetes. Genetic evidence indicates a demographically isolated population around the main Hawaiian Islands. We examine site fidelity, movements and association patterns in this population using data from directed surveys and opportunistic photographs from 1986 to 2007. This species was only infrequently encountered, and while found in depths from 38 to 4,331 m, sighting rates were greatest in depths >3,000 m. We photo‐identified 152 distinctive individuals. Resighting rates were high, with an average of 76.8% of distinctive individuals within groups documented on more than one occasion. Most (86.6%) were linked by association into a single social network; only one large group (16 distinctive individuals), documented the farthest offshore (42–70 km), did not link by association to that large network, and may be part of an offshore population. Individual movements of up to 283 km were documented, with a large proportion of individuals moving among islands. Individuals were resighted up to 20.1 yr after first being documented, showing long‐term fidelity to the islands. Repeated associations among individuals were documented for up to 15 yr, and association analyses indicate preferred associations and strong bonds among individuals.

Senescence rates are determined by ranking on the fast–slow life‐history continuum - Owen R. Jones; Jean‐Michel Gaillard; Shripad Tuljapurkar; Jussi S. Alho; Kenneth B. Armitage; Peter H. Becker; Pierre Bize; Jon Brommer; Anne Charmantier; Marie Charpentier; Tim Clutton‐Brock; F. Stephen Dobson; et al. (Ecology Letters, 2008)
Comparative analyses of survival senescence by using life tables have identified generalizations including the observation that mammals senesce faster than similar‐sized birds. These generalizations have been challenged because of limitations of life‐table approaches and the growing appreciation that senescence is more than an increasing probability of death. Without using life tables, we examine senescence rates in annual individual fitness using 20 individual‐based data sets of terrestrial vertebrates with contrasting life histories and body size. We find that senescence is widespread in the wild and equally likely to occur in survival and reproduction. Additionally, mammals senesce faster than birds because they have a faster life history for a given body size. By allowing us to disentangle the effects of two major fitness components our methods allow an assessment of the robustness of the prevalent life‐table approach. Focusing on one aspect of life history – survival or recruitment – can provide reliable information on overall senescence.

Isometric handgrip training improves local flow-mediated dilation in medicated hypertensives - Cheri L. McGowan; Adrienne Visocchi; Martha Faulkner; Robin Verduyn; Mark Rakobowchuk; Andrew S. Levy; Neil McCartney; Maureen J. MacDonald (European Journal of Applied Physiology, 2008)

Effects of local and core body temperature on grip force modulation during movement-induced load force fluctuations - Stephen S. Cheung; Luke F. Reynolds; Mark A. B. Macdonald; Constance L. Tweedie; Robin L. Urquhart; David A. Westwood (European Journal of Applied Physiology, 2008)

Evaluation of Conformation and Association Behavior of Multivalent Alanine-Rich Polypeptides - Robin S. Farmer; Ayben Top; Lindsey M. Argust; Shuang Liu; Kristi L. Kiick (Pharmaceutical Research, 2008)

The effect of soil pH on chickpea (Cicer arietinum) genotype sensitivity to isoxaflutole - Avishek Datta; Brian M. Sindel; Paul Kristiansen; Robin S. Jessop; Warwick L. Felton (Plant and Soil, 2008)

Evolutionary responses by native species to major anthropogenic changes to their ecosystems: Pacific salmon in the Columbia River hydropower system - ROBIN S. WAPLES; RICHARD W. ZABEL; MARK D. SCHEUERELL; BETH L. SANDERSON (Molecular Ecology, 2008)
The human footprint is now large in all the Earth's ecosystems, and construction of large dams in major river basins is among the anthropogenic changes that have had the most profound ecological consequences, particularly for migratory fishes. In the Columbia River basin of the western USA, considerable effort has been directed toward evaluating demographic effects of dams, yet little attention has been paid to evolutionary responses of migratory salmon to altered selective regimes. Here we make a first attempt to address this information gap. Transformation of the free‐flowing Columbia River into a series of slack‐water reservoirs has relaxed selection for adults capable of migrating long distances upstream against strong flows; conditions now favour fish capable of migrating through lakes and finding and navigating fish ladders. Juveniles must now be capable of surviving passage through multiple dams or collection and transportation around the dams. River flow patterns deliver some groups of juvenile salmon to the estuary later than is optimal for ocean survival, but countervailing selective pressures might constrain an evolutionary response toward earlier migration timing. Dams have increased the cost of migration, which reduces energy available for sexual selection and favours a nonmigratory life history. Reservoirs are a benign environment for many non‐native species that are competitors with or predators on salmon, and evolutionary responses are likely (but undocumented). More research is needed to tease apart the relative importance of evolutionary vs. plastic responses of salmon to these environmental changes; this research is logistically challenging for species with life histories like Pacific salmon, but results should substantially improve our understanding of key processes. If the Columbia River is ever returned to a quasinatural, free‐flowing state, remaining populations might face a Darwinian debt (and temporarily reduced fitness) as they struggle to re‐evolve historical adaptations.

Normativity Redux - ROBIN S. WAPLES; PETER B. ADAMS; JAMES BOHNSACK; BARBARA L. TAYLOR (Conservation Biology, 2007)

Pacific Salmon Extinctions: Quantifying Lost and Remaining Diversity - RICHARD G. GUSTAFSON; ROBIN S. WAPLES; JAMES M. MYERS; LAURIE A. WEITKAMP; GREGORY J. BRYANT; ORLAY W. JOHNSON; JEFFREY J. HARD (Conservation Biology, 2007)
Widespread population extirpations and the consequent loss of ecological, genetic, and life‐history diversity can lead to extinction of evolutionarily significant units (ESUs) and species. We attempted to systematically enumerate extinct Pacific salmon populations and characterize lost ecological, life history, and genetic diversity types among six species of Pacific salmon (Chinook [ Oncorhynchus tshawytscha ], sockeye [ O . nerka ], coho [ O . kisutch ], chum [ O . keta ], and pink salmon [ O. gorbuscha ] and steelhead trout [ O. mykiss ]) from the western contiguous United States. We estimated that, collectively, 29% of nearly 1400 historical populations of these six species have been lost from the Pacific Northwest and California since Euro‐American contact. Across all species there was a highly significant difference in the proportion of population extinctions between coastal (0.14 extinct) and interior (0.55 extinct) regions. Sockeye salmon (which typically rely on lacustrine habitats for rearing) and stream‐maturing Chinook salmon (which stay in freshwater for many months prior to spawning) had significantly higher proportional population losses than other species and maturation types. Aggregate losses of major ecological, life‐history, and genetic biodiversity components across all species were estimated at 33%, 15%, and 27%, respectively. Collectively, we believe these population extirpations represent a loss of between 16% and 30% of all historical ESUs in the study area. On the other hand, over two‐thirds of historical Pacific salmon populations in this area persist, and considerable diversity remains at all scales. Because over one‐third of the remaining populations belong to threatened or endangered species listed under the U.S. Endangered Species Act, it is apparent that a critical juncture has been reached in efforts to preserve what remains of Pacific salmon diversity. It is also evident that persistence of existing, and evolution of future, diversity will depend on the ability of Pacific salmon to adapt to anthropogenically altered habitats.

A Biological Framework for Evaluating Whether a Species Is Threatened or Endangered in a Significant Portion of Its Range - ROBIN S. WAPLES; PETER B. ADAMS; JAMES BOHNSACK; BARBARA L. TAYLOR (Conservation Biology, 2007)
Under the U.S. Endangered Species Act (ESA), a species can be listed if it is at risk “in all or a significant portion of its range,” but the ESA provides no guidance on how to interpret this key phrase. We propose a simple test to determine whether the areas of a species' range in which it is currently at risk amount to a significant portion: If the species were to become extirpated from these areas, at that point would the entire species be at risk? If so, then these areas represent a significant portion of the species' range. By establishing the species itself as the point of reference for determining significance, this test directs attention to biological risk factors and avoids difficulties inherent in subjective evaluations of importance to humans. For broadly distributed species this framework could provide ESA protection due to cumulative risks before the entire species met the criteria to be considered threatened or endangered. This framework also allows a somewhat broader concept of range to include major components of diversity necessary for long‐term persistence. The concept of a historical template (i.e., conditions under which the species was known to be viable) is important in providing a fixed reference point for evaluating viability. Empirical examples illustrate how these concepts have been applied in recent ESA listing determinations. Most ESA‐listed units of Pacific salmon ( Oncorhynchus spp.) can be divided into multiple strata that differ in terms of ecology, geology, or life‐history traits of the component populations. The goal of ESA recovery planning is to restore viable populations in enough strata that the listed unit as a whole is no longer threatened or endangered in all or a significant portion of its range. In a recent review of Pacific herring ( Clupea pallasii ) in Puget Sound, current status (some populations increasing and others declining) was evaluated in the context of the historical template, and it was concluded that current patterns of distribution and abundance do not depart substantially from what would be expected at any point in time under natural conditions in a large metapopulation. The Canadian lynx ( Lynx canadensis ) is ESA listed in the contiguous United States, where it occurs in four geographic areas. Populations in one region, the Northern Rockies/Cascades, have always been the most important for long‐term persistence of the species in the United States. Because the other regions never contained more than limited amounts of good‐quality lynx habitat, those areas are not considered to represent a significant portion of the species' range.

A potential bias in the temporal method for estimating N e in admixed populations under natural selection - HITOSHI ARAKI; ROBIN S. WAPLES; MICHAEL S. BLOUIN (Molecular Ecology, 2007)
Indirect genetic methods are frequently used to estimate the effective population size ( N e ) or effective number of breeders ( N b ) in natural populations. Although assumptions behind these methods are often violated, there have been few attempts to evaluate how accurate these estimates really are in practice. Here we investigate the influence of natural selection following a population admixture on the temporal method for estimating N e . Our analytical and simulation results suggest that N e is often underestimated in this method when subpopulations differ substantially in allele frequencies and in reproductive success. The underestimation is exacerbated when true N e and the fraction of the low‐fitness group are large. As an empirical example, we compared N b estimated in natural populations of steelhead trout ( Oncorhynchus mykiss ) using the temporal method ( N̂ b[temp] ) with estimates based on direct demographic methods ( N̂ b[demo] ) and the linkage disequilibrium method ( N̂ b[LD] ). While N̂ b[LD] was generally in close agreement with N̂ b [demo] , N̂ b[temp] was much lower in sample sets that were dominated by nonlocal hatchery fish with low reproductive success, as predicted by the analytical results. This bias in the temporal method, which arises when genes associated with a particular group of parents are selected against in the offspring sample, has not been widely appreciated before. Such situations may be particularly common when artificial propagation or translocations are used for conservation. The linkage disequilibrium method, which requires data from only one sample, is robust to this type of bias, although it can be affected by other factors.

Effective population size of steelhead trout: influence of variance in reproductive success, hatchery programs, and genetic compensation between life‐history forms - HITOSHI ARAKI; ROBIN S. WAPLES; WILLIAM R. ARDREN; BECKY COOPER; MICHAEL S. BLOUIN (Molecular Ecology, 2007)
The effective population size is influenced by many biological factors in natural populations. To evaluate their relative importance, we estimated the effective number of breeders per year ( N b ) and effective population size per generation ( N e ) in anadromous steelhead trout ( Oncorhynchus mykiss ) in the Hood River, Oregon (USA). Using demographic data and genetic parentage analysis on an almost complete sample of all adults that returned to the river over 15 years (> 15 000 individuals), we estimated N b for 13 run years and N e for three entire generations. The results are as follows: (i) the ratio of N e to the estimated census population size ( N ) was 0.17–0.40, with large variance in reproductive success among individuals being the primary cause of the reduction in N e / N ; ( ii) fish from a traditional hatchery program ( H trad : nonlocal, multiple generations in a hatchery) had negative effects on N b , not only by reducing mean reproductive success but also by increasing variance in reproductive success among breeding parents, whereas no sign of such effects was found in fish from supplementation hatchery programs ( H supp : local, single generation in a hatchery); and (iii) N b was relatively stable among run years, despite the widely fluctuating annual run sizes of anadromous adults. We found high levels of reproductive contribution of nonanadromous parents to anadromous offspring when anadromous run size is small, suggesting a genetic compensation between life‐history forms (anadromous and nonanadromous). This is the first study showing that reproductive interaction between different life‐history forms can buffer the genetic impact of fluctuating census size on N e .

Evaluating the performance of a multilocus Bayesian method for the estimation of migration rates - PIERRE FAUBET; ROBIN S. WAPLES; OSCAR E. GAGGIOTTI (Molecular Ecology, 2007)
Bayesian methods have become extremely popular in molecular ecology studies because they allow us to estimate demographic parameters of complex demographic scenarios using genetic data. Articles presenting new methods generally include sensitivity studies that evaluate their performance, but they tend to be limited and need to be followed by a more thorough evaluation. Here we evaluate the performance of a recent method, bayesass , which allows the estimation of recent migration rates among populations, as well as the inbreeding coefficient of each local population. We expand the simulation study of the original publication by considering multi‐allelic markers and scenarios with varying number of populations. We also investigate the effect of varying migration rates and F ST more thoroughly in order to identify the region of parameter space where the method is and is not able to provide accurate estimates of migration rate. Results indicate that if the demographic history of the species being studied fits the assumptions of the inference model, and if genetic differentiation is not too low ( F ST ≥ 0.05), then the method can give fairly accurate estimates of migration rates even when they are fairly high (about 0.1). However, when the assumptions of the inference model are violated, accurate estimates are obtained only if migration rates are very low ( m = 0.01) and genetic differentiation is high ( F ST ≥ 0.10). Our results also show that using posterior assignment probabilities as an indication of how much confidence we can place on the assignments is problematical since the posterior probability of assignment can be very high even when the individual assignments are very inaccurate.

Therapeutic potential and mechanism of kinetin as a treatment for the human splicing disease familial dysautonomia - Matthew M. Hims; El Chérif Ibrahim; Maire Leyne; James Mull; Lijuan Liu; Conxi Lazaro; Ranjit S. Shetty; Sandra Gill; James F. Gusella; Robin Reed; Susan A. Slaugenhaupt (Journal of Molecular Medicine, 2007)

Isometric handgrip training improves local flow-mediated dilation in medicated hypertensives - Cheri L. McGowan; Adrienne Visocchi; Martha Faulkner; Robin Verduyn; Mark Rakobowchuk; Andrew S. Levy; Neil McCartney; Maureen J. MacDonald (European Journal of Applied Physiology, 2007)

The changing role of hydrogeology in semi-arid southern and eastern Africa - N. S. Robins; J. Davies; J. L. Farr; R. C. Calow (Hydrogeology Journal, 2006)

Ossicular density in golden moles (Chrysochloridae) - Matthew J. Mason; Sarah J. Lucas; Erica R. Wise; Robin S. Stein; Melinda J. Duer (Journal of Comparative Physiology A, 2006)

Expressed Sequence Tags from loblolly pine embryos reveal similarities with angiosperm embryogenesis - John Cairney; Li Zheng; Allison Cowels; Joseph Hsiao; Victoria Zismann; Jia Liu; Shu Ouyang; Francoise Thibaud-Nissen; John Hamilton; Kevin Childs; Gerald S. Pullman; Yiting Zhang; et al. (Plant Molecular Biology, 2006)

Isometric handgrip training improves local flow-mediated dilation in medicated hypertensives - Cheri L. McGowan; Adrienne Visocchi; Martha Faulkner; Robin Verduyn; Mark Rakobowchuk; Andrew S. Levy; Neil McCartney; Maureen J. MacDonald (European Journal of Applied Physiology, 2006)

A maternal hypomethylation syndrome presenting as transient neonatal diabetes mellitus - D. J. G. Mackay; S. E. Boonen; J. Clayton-Smith; J. Goodship; J. M. D. Hahnemann; S. G. Kant; P. R. Njølstad; N. H. Robin; D. O. Robinson; R. Siebert; J. P. H. Shield; H. E. White; et al. (Human Genetics, 2006)

Surveillance and management of upper gastrointestinal disease in Familial Adenomatous Polyposis - Michelle C. Gallagher; Robin K. S. Phillips; Steffen Bulow (Familial Cancer, 2006)

Effects of Ractopamine HCl on Escherichia coli O157:H7 and Salmonella In Vitro and on Intestinal Populations and Fecal Shedding in Experimentally Infected Sheep and Pigs - Thomas S. Edrington; Todd R. Callaway; David J. Smith; Ken J. Genovese; Robin C. Anderson; David J. Nisbet (Current Microbiology, 2006)

Functional studies of two novel and two rare mutations in the 21-hydroxylase gene - M. Barbaro; L. Baldazzi; A. Balsamo; S. Lajic; T. Robins; L. Barp; P. Pirazzoli; E. Cacciari; A. Cicognani; A. Wedell (Journal of Molecular Medicine, 2006)

The Effects of Habitat on Dispersal Patterns of an Invasive Thistle, Cynara Cardunculus - Robin G. Marushia; Jodie S. Holt (Biological Invasions, 2006)

Effects of caloric restriction are species-specific - Robin J. Mockett; T. Michael Cooper; William C. Orr; Rajindar S. Sohal (Biogerontology, 2006)

INVITED REVIEW: What is a population? An empirical evaluation of some genetic methods for identifying the number of gene pools and their degree of connectivity - ROBIN S. WAPLES; OSCAR GAGGIOTTI (Molecular Ecology, 2006)
We review commonly used population definitions under both the ecological paradigm (which emphasizes demographic cohesion) and the evolutionary paradigm (which emphasizes reproductive cohesion) and find that none are truly operational. We suggest several quantitative criteria that might be used to determine when groups of individuals are different enough to be considered ‘populations’. Units for these criteria are migration rate ( m ) for the ecological paradigm and migrants per generation ( Nm ) for the evolutionary paradigm. These criteria are then evaluated by applying analytical methods to simulated genetic data for a finite island model. Under the standard parameter set that includes L = 20 High mutation (microsatellite‐like) loci and samples of S = 50 individuals from each of n = 4 subpopulations, power to detect departures from panmixia was very high (∼100%; P Nm = 25). A new method, comparing the number of correct population assignments with the random expectation, performed as well as a multilocus contingency test and warrants further consideration. Use of Low mutation (allozyme‐like) markers reduced power more than did halving S or L . Under the standard parameter set, power to detect restricted gene flow below a certain level X (H 0 : Nm X ) can also be high, provided that true Nm ≤ 0.5 X . Developing the appropriate test criterion, however, requires assumptions about several key parameters that are difficult to estimate in most natural populations. Methods that cluster individuals without using a priori sampling information detected the true number of populations only under conditions of moderate or low gene flow ( Nm ≤ 5), and power dropped sharply with smaller samples of loci and individuals. A simple algorithm based on a multilocus contingency test of allele frequencies in pairs of samples has high power to detect the true number of populations even with Nm = 25 but requires more rigorous statistical evaluation. The ecological paradigm remains challenging for evaluations using genetic markers, because the transition from demographic dependence to independence occurs in a region of high migration where genetic methods have relatively little power. Some recent theoretical developments and continued advances in computational power provide hope that this situation may change in the future.

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

A bias correction for estimates of effective population size based on linkage disequilibrium at unlinked gene loci* - Robin S. Waples (Conservation Genetics, 2006)

Genetic estimates of contemporary effective population size: to what time periods do the estimates apply? - ROBIN S. WAPLES (Molecular Ecology, 2005)
Although most genetic estimates of contemporary effective population size ( N e ) are based on models that assume N e is constant, in real populations N e changes (often dramatically) over time, and estimates (N̂ e ) will be influenced by N e in specific generations. In such cases, it is important to properly match N̂ e to the appropriate time periods (for example, in computing N e / N ratios). Here I consider this problem for semelparous species with two life histories (discrete generations and variable age at maturity — the ‘salmon’ model), for two different sampling plans, and for estimators based on single samples (linkage disequilibrium, heterozygote excess) and two samples (temporal method). Results include the following. Discrete generations : (i) Temporal samples from generations 0 and t estimate the harmonic mean N e in generations 0 through t − 1 but do not provide information about N e in generation t ; (ii) Single samples provide an estimate of N e in the parental generation, not the generation sampled; (iii) single‐sample and temporal estimates never provide information about N e in exactly the same generations; (iv) Recent bottlenecks can downwardly bias estimates based on linkage disequilibrium for several generations. Salmon model : (i) A pair of single‐cohort (typically juvenile) samples from years 0 and t provide a temporal estimate of the harmonic mean of the effective numbers of breeders in the two parental years ( N b (0) and N b ( t ) ), but adult samples are more difficult to interpret because they are influenced by N b in a number of previous years; (ii) For single‐cohort samples, both one‐sample and temporal methods provide estimates of N b in the same years (contrast with results for discrete generation model); (iii) Residual linkage disequilibrium associated with past population size will not affect single‐sample estimates of N b as much as in the discrete generation model because the disequilibrium diffuses among different years of breeders. These results lead to some general conclusions about genetic estimates of N e in iteroparous species with overlapping generations and identify areas in need of further research.

Phylogeny of nereidids (Polychaeta, Nereididae) with paragnaths - Torkild Bakken; Robin S. Wilson (Zoologica Scripta, 2005)
A phylogenetic analysis was conducted of the Nereidinae — those members of the Nereididae (Polychaeta) with pharyngeal paragnaths. We had two objectives: to test the monophyly of currently accepted genera, subgenera and informal subgeneric groupings within the Nereidinae, and, if warranted, to propose a more natural classification of the Nereidinae. Parsimony analyses were undertaken, including 52 terminal taxa from all genera and informal groupings from the large heterogeneous genera Nereis , Ceratonereis , Neanthes and Perinereis . Analyses of a character set of 52 informative characters yielded more than 10 000 equally parsimonious trees with a length of 176 steps (consistency index [CI] = 0.34, retention index [RI] = 0.66). Reweighting three times resulted in 445 most parsimonious trees with length 54.62 (CI = 0.59, RI = 0.79). Many characters widely used in nereidid systematics were found to exhibit high levels of homoplasy. The most parsimonious trees could not be rooted such that the selected ingroup, ‘Nereididae with paragnaths’, was monophyletic, causing us to reject the monophyly of the Nereidinae as currently defined. The following genera were well supported by the parsimony analyses and are newly diagnosed: Alitta , Ceratonereis , Pseudonereis , Simplisetia , Solomononereis and Unanereis . Alitta succinea , Pseudonereis cortezi , Pseudonereis noodti and Pseudonereis pseudonoodti are proposed as new combinations. The parsimony analysis supported the monophyly of neither Composetia , Neanthes , Nereis and Perinereis nor of any new groupings of remaining species presently placed in those genera. It is these poorly supported genera that comprise most species of Nereididae.

A Microstructural Hyperelastic Model of Pulmonary Arteries Under Normo- and Hypertensive Conditions - Yanhang Zhang; Martin L. Dunn; E. S. Drexler; C. N. McCowan; A. J. Slifka; D. D. Ivy; Robin Shandas (Annals of Biomedical Engineering, 2005)

Remote sensing of heterogeneity in photosynthetic efficiency, electron transport and dissipation of excess light in Populus deltoides stands under ambient and elevated CO 2 concentrations, and in a tropical forest canopy, using a new laser‐induced fluorescence transient device - Gennady Ananyev; Zbigniew S. Kolber; Dennis Klimov; Paul G. Falkowski; Joseph A. Berry; Uwe Rascher; Robin Martin; Barry Osmond (Global Change Biology, 2005)
Determining the spatial and temporal diversity of photosynthetic processes in forest canopies presents a challenge to the evaluation of biological feedbacks needed for improvement of carbon and climate models. Limited access with portable instrumentation, especially in the outer canopy, makes remote sensing of these processes a priority in experimental ecosystem and climate change research. Here, we describe the application of a new, active, chlorophyll fluorescence measurement system for remote sensing of light use efficiency, based on analysis of laser‐induced fluorescence transients (LIFT). We used mature stands of Populus grown at ambient (380 ppm) and elevated CO 2 (1220 ppm) in the enclosed agriforests of the Biosphere 2 Laboratory (B2L) to compare parameters of photosynthetic efficiency, photosynthetic electron transport, and dissipation of excess light measured by LIFT and by standard on‐the‐leaf saturating flash methods using a commercially available pulse‐modulated chlorophyll fluorescence instrument (Mini‐PAM). We also used LIFT to observe the diel courses of these parameters in leaves of two tropical forest dominants, Inga and Pterocarpus , growing in the enclosed model tropical forest of B2L. Midcanopy leaves of both trees showed the expected relationships among chlorophyll fluorescence‐derived photosynthetic parameters in response to sun exposure, but, unusually, both displayed an afternoon increase in nonphotochemical quenching in the shade, which was ascribed to reversible inhibition of photosynthesis at high leaf temperatures in the enclosed canopy. Inga generally showed higher rates of photosynthetic electron transport, but greater afternoon reduction in photosynthetic efficiency. The potential for estimation of the contribution of outer canopy photosynthesis to forest CO 2 assimilation, and assessment of its response to environmental stress using remote sensing devices such as LIFT, is briefly discussed.

Indices of bird‐habitat preference from field surveys of birds and remote sensing of land cover: a study of south‐eastern England with wider implications for conservation and biodiversity assessment - Robin M. Fuller; Bernard J. Devereux; Simon Gillings; Gabriel S. Amable; Ross A. Hill (Global Ecology and Biogeography, 2005)
Aim This paper describes the development of novel indices of bird‐habitat preference to examine bird species’ use of habitats and their distributions relative to habitats. It assesses the implications for bird conservation regionally and the scope for biodiversity assessments generally. Location A 200 km by 400 km area of farmland with seminatural and urban areas, covering south‐eastern England. Methods Cluster analysis was used to link birds to landscapes. Cluster centroid coordinate values were processed to derive indices of bird‐habitat preference. Further developments assessed the relative values of individual habitats for birds. Results Clustering objectively linked birds to landscapes. Maps of the clusters showed strong regional patterns associated with distinctive habitat assemblages. Derived indices related bird species directly to individual habitats and habitats to birds. Even rare species and scarce habitats showed successful linkages, often to each other. Objective corroboration strongly supported the associations of coastal, wetland, urban and woodland birds and habitats; but, it suggested that farmland birds, whose numbers have nearly halved since 1977, may prefer alternative habitats. Main conclusions Land cover maps from remote sensing provide an effective way to link birds to habitats and vice versa . Thus, generalized habitat maps might be used to extrapolate localized or sample‐based bird observations or the results of autecological studies, helping to predict and understand bird distributions in the wider countryside. The weak links between farmland birds and farmland habitats in a region dominated by farming, suggests that reasons for the decline in farmland birds may be deep seated and thus hard to reverse. The procedures described are repeatable elsewhere and applicable more generally to evaluate landscapes and biodiversity. It is suggested that remote sensing could rarely be bettered as a means of assessing habitats, comprehensively, over wide areas, in most parts of the world.

Mercury Bioaccumulation in Northern Two-lined Salamanders from Streams in the Northeastern United States - Michael S. Bank; Cynthia S. Loftin; Robin E. Jung (Ecotoxicology, 2005)

Validation of an ELISA test kit for the detection of total aflatoxins in grain and grain products by comparison with HPLC - Zhongming Zheng; Craig W. Humphrey; Robin S. King; John L. Richard (Mycopathologia, 2005)

Validation of an ELISA test kit for the detection of ochratoxin A in several food commodities by comparison with HPLC - Zhongming Zheng; Jonne Hanneken; Donna Houchins; Robin S. King; Peter Lee; John L. Richard (Mycopathologia, 2005)

Occurrence and distribution of Phytophthora species in European chestnut stands, and their association with Ink Disease and crown decline - A. M. Vettraino; O. Morel; C. Perlerou; C. Robin; S. Diamandis; A. Vannini (European Journal of Plant Pathology, 2005)

A comparison of wind-tunnel experiments and numerical simulations of neutral and stratified flow over a hill - A.N. Ross; S. Arnold; S.B. Vosper; S. D. Mobbs; N. Dixon; A. G. Robins (Boundary-Layer Meteorology, 2004)

Influence of dry diets on reproductive performance and egg lipid composition during the first spawning season of captive pollack - M. H. Omnes; S. Recek; H. Barone; H. Le Delliou; A. Schmitz; A. Mutelet; M. Suquet; J. H. Robin (Journal of Fish Biology, 2004)
Four‐year‐old pollack Pollachius pollachius L., previously fed on dry pellets since their juvenile stage, were divided into three experimental groups two months prior their first spawning season. They were fed a commercial broodstock pellet enriched with 6% added oils, either: (1) capelin oil (control), (2) capelin oil plus arachidonic acid, or (3) DHA rich tuna oil. Spawning performance was determined in each group and egg lipids were analysed. During the vitellogenic period, the estradiol levels in plasma increased with oocyte enlargement, indicating that captivity and pelleted feed did not affect reproductive capacity. Females from each group spawned spontaneously between February and May. Egg production per kg of female was highest in the control group. Fertilization rate was highest (39%) in the group fed on diet enhanced in DHA. Lipid content in eggs reached 16% of dry mass, containing mainly phospholipids (75%). Egg fatty acid profiles showed few differences between dietary treatments. There was no significant difference in the concentration of Docosahexaenoic acid (22:6n − 3) between groups. Arachidonic acid (20:4n − 6) was lower in neutral and polar lipids of eggs from the control group than in the other groups. Tuna oil diet induced the highest DHA/EPA ratio in eggs and seemed to provide sufficient arachidonic acid for pollack broodstock. Egg fatty acid profiles are compared with 6 year‐old pollack broodstock fed on fish, and with other cultured and wild fish species.

Expansion of human settlement in Kenya's Maasai Mara: what future for pastoralism and wildlife? - Richard H. Lamprey; Robin S. Reid (Journal of Biogeography, 2004)
Aim Wildlife and pastoral peoples have lived side‐by‐side in the Mara ecosystem of south‐western Kenya for at least 2000 years. Recent changes in human population and landuse are jeopardizing this co‐existence. The aim of the study is to determine the viability of pastoralism and wildlife conservation in Maasai ranches around the Maasai Mara National Reserve (MMNR). Location A study area of 2250 km 2 was selected in the northern part of the Serengeti‐Mara ecosystem, encompassing group ranches adjoining the MMNR. Emphasis is placed on Koyake Group Ranch, a rangeland area owned by Maasai pastoralists, and one of Kenya's major wildlife tourism areas. Methods Maasai settlement patterns, vegetation, livestock numbers and wildlife numbers were analysed over a 50‐year period. Settlement distributions and vegetation changes were determined from aerial photography and aerial surveys of 1950, 1961, 1967, 1974, 1983 and 1999. Livestock and wildlife numbers were determined from re‐analysis of systematic reconnaissance flights conducted by the Kenya Government from 1977 to 2000, and from ground counts in 2002. Corroborating data on livestock numbers were obtained from aerial photography of Maasai settlements in 2001. Trends in livestock were related to rainfall, and to vegetation production as indicated by the seasonal Normalized Difference Vegetation Index. With these data sets, per capita livestock holdings were determined for the period 1980–2000, a period of fluctuating rainfall and primary production. Results For the first half of the twentieth century, the Mara was infested with tsetse‐flies, and the Maasai were confined to the Lemek Valley area to the north of the MMNR. During the early 1960s, active tsetse‐control measures by both government and the Maasai led to the destruction of woodlands across the Mara and the retreat of tsetse flies. The Maasai were then able to expand their settlement area south towards MMNR. Meanwhile, wildebeest ( Connochaetes taurinus ) from the increasing Serengeti population began to spill into the Mara rangelands each dry season, leading to direct competition between livestock and wildlife. Group ranches were established in the area in 1970 to formalize land tenure for the Maasai. By the late 1980s, with rapid population growth, new settlement areas had been established at Talek and other parts adjacent to the MMNR. Over the period 1983–99, the number of Maasai bomas in Koyake has increased at 6.4% per annum (pa), and the human population at 4.4% pa. Over the same period, cattle numbers on Koyake varied from 20,000 to 45,000 (average 25,000), in relation to total rainfall received over the previous 2 years. The rangelands of the Mara cannot support a greater cattle population under current pastoral practices. Conclusions With the rapid increase in human settlement in the Mara, and with imminent land privatization, it is probable that wildlife populations on Koyake will decline significantly in the next 3–5 years. Per capita livestock holdings on the ranch have now fallen to three livestock units/reference adult, well below minimum pastoral subsistence requirements. During the 1980s and 90s the Maasai diversified their livelihoods to generate revenues from tourism, small‐scale agriculture and land‐leases for mechanized cultivation. However, there is a massive imbalance in tourism incomes in favour of a small elite. In 1999 the membership of Koyake voted to subdivide the ranch into individual holdings. In 2003 the subdivision survey allocated plots of 60 ha average size to 1020 ranch members. This land privatization may result in increased cultivation and fencing, the exclusion of wildlife, and the decline of tourism as a revenue generator. This unique pastoral/wildlife system will shortly be lost unless land holdings can be managed to maintain the free movement of livestock and wildlife.

Brain penetration of methadone (R)- and (S)-enantiomers is greatly increased by P-glycoprotein deficiency in the blood?brain barrier of Abcb1a gene knockout mice - Jun-Sheng Wang; Ying Ruan; Robin M. Taylor; Jennifer L. Donovan; John S. Markowitz; C. Lindsay DeVane (Psychopharmacology, 2004)

Making sense of predator scents: investigating the sophistication of predator assessment abilities of fathead minnows - Robin C. Kusch; Reehan S. Mirza; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2004)

Is it possible to mitigate greenhouse gas emissions in pastoral ecosystems of the tropics? - Robin S. Reid; Philip K. Thornton; Graeme J. McCrabb; Russell L. Kruska; Fred Atieno; Peter G. Jones (Environment, Development and Sustainability, 2004)

A small molecule antagonist of the α v β3 integrin suppresses MDA-MB-435 skeletal metastasis - John F. Harms; Danny R. Welch; Rajeev S. Samant; Lalita A. Shevde; Mary E. Miele; Geetha R. Babu; Steven F. Goldberg; Virginia R. Gilman; Donna M. Sosnowski; Dianalee A. Campo; Carol V. Gay; Lynn R. Budgeon; et al. (Clinical & Experimental Metastasis, 2004)

Influence of maize mucilage on the diversity and activity of the denitrifying community - E. Mounier; S. Hallet; D. Chèneby; E. Benizri; Y. Gruet; C. Nguyen; S. Piutti; C. Robin; S. Slezack‐Deschaumes; F. Martin‐Laurent; J.C. Germon; L. Philippot (Environmental Microbiology, 2004)
Summary In order to understand the effect of the maize rhizosphere on denitrification, the diversity and the activity of the denitrifying community were studied in soil amended with maize mucilage. Diversity of the denitrifying community was investigated by polymerase chain reaction (PCR) amplification of total community DNA extracted from soils using gene fragments, encoding the nitrate reductase ( narG ) and the nitrous oxide reductase ( nosZ ), as molecular markers. To assess the underlying diversity, PCR products were cloned and 10 gene libraries were obtained for each targeted gene. Libraries containing 738 and 713 narG and nosZ clones, respectively, were screened by restriction fragment analysis, and grouped based on their RFLP (restriction fragment length polymorphism) patterns. In all, 117 and 171 different clone families have been identified for narG and nosZ and representatives of RFLP families containing at least two clones were sequenced. Rarefaction curves of both genes did not reach a clear saturation, indicating that analysis of an increasing number of clones would have revealed further diversity. Recovered NarG sequences were related to NarG from Actinomycetales and from Proteobacteria but most of them are not related to NarG from known bacteria. In contrast, most of the NosZ sequences were related to NosZ from α, β, and γ Proteobacteria . Denitrifying activity was monitored by incubating the control and amended soils anaerobically in presence of acetylene. The N 2 O production rates revealed denitrifying activity to be greater in amended soil than in control soil. Altogether, our results revealed that mucilage addition to the soil results in a strong impact on the activity of the denitrifying community and minor changes on its diversity.

Introduced and cryptogenic species in Port Phillip Bay, Victoria, Australia - Ronald E. Thresher; Richard B. Martin; Sue Boyd; Brian F. Cohen; David R. Currie; Martin F. Gomon; Michael J. Keough; John A. Lewis; Matthew M. Lockett; Nicole Mays; Matthew A. McArthur; Tim D. O'Hara; et al. (Marine Biology, 2004)

Mapping osmotic adjustment in an advanced back-cross inbred population of rice - S. Robin; M. S. Pathan; B. Courtois; R. Lafitte; S. Carandang; S. Lanceras; M. Amante; H. T. Nguyen; Z. Li (Theoretical and Applied Genetics, 2003)

Effects of ultraviolet radiation on toad early life stages - Edward E. Little; Robin D. Calfee; David L. Fabacher; Cynthia Carey; Vicki S. Blazer; Elizabeth M. Middleton (Environmental Science and Pollution Research, 2003)

Chromosomal differentiation and genome size in three European mountain Lilium species - S. Siljak-Yakovlev; S. Peccenini; E. Muratovic; V. Zoldos; O. Robin; J. Valls (Plant Systematics and Evolution, 2003)

Fluid compositions in equilibrium with silica-undersaturated magmas in the system Na2O–Al2O3–SiO2–H2O: clues to the composition of fenitizing fluids - Robin F. Preston; Gary Stevens; Terence S. McCarthy (Contributions to Mineralogy and Petrology, 2003)

An Analysis of Fish Species Richness in Natural Lakes - Upali S. Amarasinghe; Robin L. Welcomme (Environmental Biology of Fishes, 2002)

Trans-complementation of an endonuclease-defective tagged I element as a tool for the study of retrotransposition in Drosophila melanogaster - S. Robin; S. Chambeyron; C. Brun; A. Bucheton; I. Busseau (Molecular Genetics and Genomics, 2002)

Bolbophorus damnificus n. sp. (Digenea: Bolbophoridae) from the channel catfish Ictalurus punctatus and American white pelican Pelecanus erythrorhynchos in the USA based on life-cycle and molecular data - Robin M. Overstreet; Stephen S. Curran; Linda M. Pote; D. Tommy King; Charles K. Blend; Walter D. Grater (Systematic Parasitology, 2002)

Evaluating the effect of stage‐specific survivorship on the N e / N ratio - Robin S. Waples (Molecular Ecology, 2002)
Evaluating effective population size ( N e ) and the effective size to census size ratio ( N e / N ) in species with Type III survivorship curves is complicated when key demographic parameters [mean ( k̄ ) and variance ( V k ) of family size] are measured during early life stages. The method of Crow & Morton (1955 ) for scaling demographic data collected at a juvenile stage to expected values at adulthood is extended to consider sequential episodes of random and family correlated survival. Results show the following: (i) The order in which the episodes of random and family‐correlated survival occur does not affect N e or N e / N ; (ii) If a population experiences an episode of family‐correlated survival, N e / N scaled to its expected value in a population of constant size ( k̄ = 2) is simply the survival rate during the family‐correlated stage. If multiple such stages occur, scaled N e / N is the product of the survivals during all family‐correlated life stages; (iii) Under the assumption of random post‐enumeration survival, adjusting the variance effective size to its expected value at k̄ = 2 is equivalent to computing the inbreeding effective size at the earlier life stage. Application to experimental data for hatchery populations of Pacific salmon ( Oncorhynchus spp.) indicates that nonrandom survival during the marine phase led to estimated reductions in effective size of 0–62% (mean 19%) in 12 different cohorts. This approach can provide insights into N e / N in highly fecund species, including some marine species in which N e has been estimated to be several orders of magnitude less than N .

Assimilation and retention of selenium and other trace elements from crustacean food by juvenile striped bass ( Morone saxatilis ) - Stephen B. Baines; Nicholas S. Fisher; Robin Stewart (Limnology and Oceanography, 2002)
Estimates of the assimilation and retention of trace elements from food by fish are useful for linking toxicity with the biogeochemical cycling of these elements through aquatic food webs. Here we use pulse‐chase radiotracer techniques to estimate the assimilation and retention of Se and four trace metals, Ag, Am, Zn, and Cd, by 43‐ and 88‐d‐old juvenile striped bass, Morone saxatilis, from crustacean food. Brine shrimp nauplii, Artemia franciscana , or adult copepods, Acartia tonsa , were fed radiolabeled diatoms and then fed to juvenile striped bass. Assimilation efficiencies (AEs ± SD) for 43‐d‐old fish were 18 ± 2%, 6 ± 1%, 23 ± 4%, 33 ± 3%, and 23 ± 2% for Ag, Am, Cd, Se, and Zn, respectively. For 88‐d‐old fish, the AEs were 28 ± 1%, 42 ± 5%, and 40 ± 5% for Cd, Se, and Zn, respectively. The higher AEs in the older fish may result from longer gut passage times for larger fish. The 44‐d‐old fish excreted 5 ± 0.8%, 4 ± 2.0%, 7 ± 0.3%, 9 ± 0.4%, and 1.3 ± 0.9% of the Ag, Am, Cd, Se, and Zn, respectively, they ingested from food per day, whereas the 88‐d‐old fish excreted 3 ± 1.0%, 8 ± 0.5%, and 3 ± 0.5% of the assimilated Cd, Se, and Zn per day, respectively. Predictions of steady state Se concentrations in juvenile striped bass tissues made using a biokinetic model and the measured AE and efflux rates ranged from 1.8 to 3.0 mg Se g −1 dry wt for muscle tissue and 6.8 to 11.6 mg Se g −1 dry wt for gut tissue. These predictions agreed well with average values of 2.1 and 13 mg Se g −1 dry wt measured independently in North San Francisco Bay, where elevated Se concentrations are of concern. The model results imply that the planktonic food web, including juvenile striped bass, does not transfer Se as efficiently to top consumers as does the benthic food web.

Relationship of Effective to Census Size in Fluctuating Populations - Steven T. Kalinowski; Robin S. Waples (Conservation Biology, 2002)
The effective size of a population ( N e ) rather than the census size ( N ) determines its rate of genetic drift. Knowing the ratio of effective to census size, N e / N , is useful for estimating the effective size of a population from census data and for examining how different ecological factors influence effective size. Two different multigenerational ratios have been used in the literature based on either the arithmetic mean or the harmonic mean in the denominator. We clarify the interpretation and meaning of these ratios. The arithmetic mean N e / N ratio compares the total number of real individuals to the long‐term effective size of the population. The harmonic mean N e / N ratio summarizes variation in the N e / N ratio for each generation. In addition, we show that the ratio of the harmonic mean population size to the arithmetic mean population size provides a useful measure of how much fluctuation in size reduced the effective size of a population. We discuss applications of these ratios and emphasize how to use the harmonic mean N e / N ratio to estimate the effective size of a population over a period of time for which census counts have been collected.

Three-Dimensional Modelling of Concentration Fluctuations in Complicated Geometry - S. Andronopoulos; D. Grigoriadis; A. Robins; A. Venetsanos; S. Rafailidis; J.G. Bartzis (Environmental Fluid Mechanics, 2001)

Evaluation of near-isogenic lines of rice introgressed with QTLs for root depth through marker-aided selection - L. Shen; B. Courtois; K. L. McNally; S. Robin; Z. Li (Theoretical and Applied Genetics, 2001)

Locating genomic regions associated with components of drought resistance in rice: comparative mapping within and across species - J. Zhang; H. G. Zheng; A. Aarti; G. Pantuwan; T. T. Nguyen; J. N. Tripathy; A. K. Sarial; S. Robin; R. C. Babu; Bay D. Nguyen; S. Sarkarung; A. Blum; et al. (Theoretical and Applied Genetics, 2001)

Effects of weather on activity and sleep in brooding king penguins ( Aptenodytes patagonicus ) - Dewasmes G.; Côté S.; Y. Le Maho; Groscolas R.; Robin J.; Vardon G.; Libert J. (Polar Biology, 2001)

A molecular approach to dominance in hypophosphatasia - A. Lia-Baldini; F. Muller; A. Taillandier; J. Gibrat; M. Mouchard; B. Robin; B. Simon-Bouy; J. Serre; A. Aylsworth; E. Bieth; S. Delanote; P. Freisinger; et al. (Human Genetics, 2001)

Boron efficiency in oilseed rape: I. Genotypic variation demonstrated in field and pot grown Brassica napus L. and Brassica juncea L. - James C. R. Stangoulis; Harsharn S. Grewal; Richard W. Bell; Robin D. Graham (Plant and Soil, 2000)

QTLs for cell-membrane stability mapped in rice (Oryza sativa L.) under drought stress - J. N. Tripathy; Jingxian Zhang; S. Robin; Thuy T. Nguyen; H. T. Nguyen (Theoretical and Applied Genetics, 2000)

Resistance to septoria nodorum blotch in the Aegilops tauschii accession RL5271 is controlled by a single gene - Noel E.A. Murphy; Robert Loughman; Robin Wilson; Evans S. Lagudah; Rudi Appels; Michael G.K. Jones (Euphytica, 2000)

Molecular ecology and biological control: the mating system of a marsupial pest - S. D. Sarre; N. Aitken; M. N. Clout; W. Ji; J. Robins; D. M. Lambert (Molecular Ecology, 2000)
Many studies in molecular ecology have focused on the use of repeat DNA markers to determine the nature of mating systems in a wide variety of animal species. Whilst these studies typically have focused on important issues such as the evolutionary consequences of fitness variation among males, genetic studies of mating systems are potentially also important because they can generate information of significance to wider issues in wildlife management. For example, genetically modified, sexually transmitted viral diseases have been suggested as potential agents for the control of vertebrate pest species. An understanding of the epidemiology of such agents requires an intimate knowledge of the sexual contact rates between individuals of the target species. Here, we report the use of minisatellite DNA profiling to reveal the mating system in two New Zealand populations of the introduced Australian brushtail possum. The brushtail possum is New Zealand’s most important mammalian pest and a species for which control by a sexually transmitted immunocontraceptive has been proposed. Encouragingly, we report considerable variation in the reproductive success of males at both study sites, with one male siring offspring from four females in one year (mean no. of offspring/reproductively successful male/year at the two sites is 1.95–2.15), while many sired none. This bias in the pattern of reproductive success among males will probably facilitate the spread of an immunocontraceptive agent and thereby increase the power of this approach to biological control.

Growth limitation in young Euphausia superba under field conditions - Robin M. Ross; Langdon B. Quetin; Karen S. Baker; Maria Vernet; Raymond C. Smith (Limnology and Oceanography, 2000)
Growth rates of late furcilia and juvenile Antarctic krill ( Euphausia superba Dana) in the spring and summer were related to food quantity and quality. The 4 yr covered by this study (1991–1992, 1993–1994, 1994–1995, and 1995–1996) were part of the seasonal time series of the Palmer Long‐Term Ecological Research program. Chlorophyll a concentrations represented food quantity, and accessory photosynthetic pigments represented phytoplank‐ton community composition or food quality. Instantaneous growth rates reflected the in situ nutritional history of the previous intermolt period. The response of krill to the food environment was seen on temporal scales of days to weeks. Percent growth per intermolt period (percentage growth IMP −1 ( varied significantly both within and between years, ranging from ∼2 to 10% IMP −1 . Percent growth IMP −1 increased with increasing chlorophyll a (Chl a ), reaching a maximum of 9.3% IMP −1 above a critical concentration of about 3.5 mg m 23 . Maximum growth was reached in only 2 yr, 1991–1992 and 1995–1996. In a multiple regression analysis, total Chl a and prymnesiophyte‐Chl a explained over 71% of the temporal variance in growth. In general, highest growth was found toward the end of diatom blooms and lowest during periods of low phytoplankton biomass or blooms dominated by cryptophytes and prymnesiophytes. The results of this study support the hypothesis that maximum growth rates are only possible during diatom blooms and that production in Antarctic krill is limited by both food quantity and quality.

Inheritance of root regrowth as an indicator of apparent aluminum tolerance in triticale - Xianguang Zhang; Robin S. Jessop; Frank Ellison (Euphytica, 1999)

Distribution and diversity of mtDNA lineages among southern right whales ( Eubalaena australis ) from Australia and New Zealand - C. S. Baker; N. J. Patenaude; J. L. Bannister; J. Robins; H. Kato (Marine Biology, 1999)

An Aquifer Management Case Study – The Chalk of the English South Downs - N. S. Robins; H. K. Jones; J. Ellis (Water Resources Management, 1999)

Combined effect of the growth temperature and salinity of the medium on the accumulation of compatible solutes by Rhodothermus marinus and Rhodothermus obamensis - Zélia Silva; Nuno Borges; Lígia O. Martins; Robin Wait; Milton S. da Costa; H. Santos (Extremophiles, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Prioritizing Pacific Salmon Stocks for Conservation: Response to Allendorf et al. - Thomas C. Wainwright; Robin S. Waples (Conservation Biology, 1998)

Molecular characterization and delineation of subtle deletions in de novo “balanced” chromosomal rearrangements - Arun Kumar; Laurie A. Becker; Theresa W. Depinet; J. Marie Haren; C. Lisa Kurtz; Nathaniel H. Robin; Suzanne B. Cassidy; Daynna J. Wolff; S. Schwartz (Human Genetics, 1998)

A sequential culture approach to study osteoclast differentiation from nonadherent porcine bone marrow cells - Ben A. A. Scheven; John S. Milne; Simon P. Robins (In Vitro Cellular & Developmental Biology - Animal, 1998)

Implantable stimulation system dedicated for neural selective stimulation - S. Robin; M. Sawan; M. Abdel-Gawad; T. M. Abdel-Baky; M. M. Elhilali (Medical & Biological Engineering & Computing, 1998)

Analysis of genetic variability of aluminium tolerance response in triticale - Xianguang Zhang; Robin S. Jessop (Euphytica, 1998)

Evolutionarily Significant Units, Distinct Population Segments, and the Endangered Species Act: Reply to Pennock and Dimmick - Robin S. Waples (Conservation Biology, 1998)

Evolutionarily Significant Units, Distinct Population Segments, and the Endangered Species Act: Reply to Pennock and Dimmick - Robin S. Waples (Conservation Biology, 1998)

Bone tissue resorption markers in metastatic involvement of the skeleton - N. V. Lyubimova; N. E. Kushlinskii; S. P. Robins (Bulletin of Experimental Biology and Medicine, 1998)

Structure and floristics of secondary and old-growth forest stands in lowland Costa Rica - Manuel R. Guariguata; Robin L. Chazdon; Julie S. Denslow; Juan M. Dupuy; Laura Anderson (Plant Ecology, 1997)

Exploring the Error Structure of Taper Equations - Michael S. Williams; Robin M. Reich (Forest Science, 1997)
Much work has been done fitting taper equations to specific tree bole shapes, but few researchers have investigated what effect the correlated error structure has on the fit of a taper equation. The Max and Burkhart (1976) taper equation was used in conjunction with a number of equations which modeled the covariance structures. The equations proposed were continuously differentiable, which simplifies the fitting process, and selected to minimize the number of parameters. A maximum likelihood method was proposed to fit these equations and test the statistical significance of the correlated errors. Accounting for the correlated errors structure in the equation fitting process significantly improved fit. Tests showed a small, but significant, bias of 1.05% (± 0.143%) when the correlated errors were ignored. For. Sci. 43(3):378-386.

Effects of Land‐Use and Tsetse Fly Control on Bird Species Richness in Southwestern Ethiopia - Cathleen J. Wilson; Robin S. Reid; Nancy L. Stanton; Brian D. Perry (Conservation Biology, 1997)
Successful control of tsetse (Glossina spp.)‐transmitted trypanosomiasis in the Ghibe Valley, Ethiopia, appears to have accelerated conversion of wooded grassland into cropland. Land conversion, in turn, may have fragmented wildlife habitat. Our objective was to assess the influence of the expansion of agricultural land‐use, brought about by tsetse control, on ecological properties by using bird species richness and composition as indicators of environmental impacts. We sampled bird species richness and composition (using Timed‐Species counts) and habitat structure (using field sampling and remote sensing) in four land cover/land‐use types in areas subjected to tsetse fly control and adjacent areas without control. At the height of the growing season bird species numbers and vegetative complexity were greater in the small‐holder, oxen‐plowed fields and riparian woodlands than in wooded grasslands or in large‐holder, tractor‐plowed fields. Species composition was highly dissimilar (40–70% dissimilarity) comparing among land‐use types, with many species found only in a single type. This implies that trypanosomiasis control that results in land conversion from wooded grasslands to small‐holder farming in this region may have no adverse impacts on bird species numbers but will alter composition. These results also suggest that moderate land‐use by humans (e.g., small‐holder field mosaics) increases habitat heterogeneity and bird species richness relative to high levels of use (e.g., tractor‐plowed fields). Tsetse control may be indirectly maintaining species richness in the valley by encouraging the differential spread of these small‐scale, heterogeneous farms in place of large‐scale, homogeneous farms. Nevertheless, if the extent of small‐holder farms significantly exceeds that of present levels, negative impacts on bird species richness and large shifts in species composition may occur.

Bacteriophage 105clz induces the GroEL-homologue protein inBacillus subtilis - Robin R. Staples; Brian S. Miller; Uldis N. Streips (Antonie van Leeuwenhoek, 1992)

Dynamic response of the intact canine adrenal to infused ACTH - Robin B. Lake; Donald S. Gann (Annals of Biomedical Engineering, 1972)